Protective effect of melatonin against age-related ischemia-reperfusion injury is associated with the NLRP3 inflammasome pathway - Ikram Ben Jeddou; Ángela Berlana; Esther Rey; Hassen Ben Abdennebi; Wassim Y. Almawi; Abdelwahab Omri; Ángela M. Valverde; Águeda González-Rodriguez; Mohamed Amine Zaouali (Journal of Physiology and Biochemistry, 2026)

An event-related potentials account of brain predictive coding - Carlos M. Gómez; Antonio Arjona; Francisco J. Ruíz-Martínez; Manuel Muñoz-Caracuel; Vanesa Muñoz; Elena I. Rodriguez-Martinez (Cognitive Neurodynamics, 2026)
Predictive coding is a theory that tries to account for how the brain processes in an anticipatory manner the expected stimuli, and reorganizes the underlying neural networks as a consequence of the outcome of predictions: Correct or incorrect. EEG has the advantage of making a continuous and almost instantaneous record of brain activity. The present report summarizes work on Event-Related Potentials (ERPs) and reviews the neural validity of Predictive processing as a mechanism to predict future events, assess the validity of predictions, and then update the probabilities associated with future events. Using two experimental models: predictive tone sequences and central cue Posner paradigms and Bayesian modelling, the report suggests that Contingent Negative Variation (CNV) would be related to prior expectation, Mismatch negativity (MMN) and P300 to Bayesian surprise and/or prediction error, and Post Imperative Negative Variation (PINV) to the assessment of trial outcome in uncertainty situations. The review tends to support predictive coding as a theory consistent with brain operations indexed by ERPs.

Models based on urbanization and environmental heterogeneity jointly explain the distribution of plant species diversity and composition in urban green spaces - Armando Navarrete-Segueda; Jorge Cortés-Flores; Elizabeth Chávez-García; M. Lourdes González-Arqueros; Guadalupe Cornejo-Tenorio; Diana Santillán-Gaona; Abril Soria-Nambo; Iván Leonardo Ek-Rodriguez; Guillermo Ibarra-Manríquez (Urban Forestry & Urban Greening, 2026)

Forest conversion is more strongly associated with soil microbial functioning than chronic trace element exposure in an industrialized coastal mediterranean ecosystem - S. Fabian Plaza; F. Gonzalo Tortella; Giovanni Larama; Rodrigo Rodriguez; Thierry Lebeau; Clémentine Lapie; Walter Valdivia; Eros Fajardo; M. Fernández-Baldo; Juan Hirzel; Gustavo Santoyo; Mauricio Schoebitz (Environmental Pollution, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Detection of Sarcocystis aucheniae DNA in placental and umbilical cord tissues suggests possible vertical transmission in domestic South American camelids - Monica Florin-Christensen; Juan Reategui-Ordoñez; Cesar Vargas Tacuri; Luisa Neyra; Carlos V. Enriquez; Evelyn Diaz; Halley Rodriguez Huanca; Ximena Barriga Marcapura; Luis V.M. Olivera; Susana M. Giuliano (Veterinary Parasitology, 2026)

When things go wrong: The detrimental interplay of environmental factors on bioturbation in a Jurassic shallow-marine system from western Argentina - Debora M. Campetella; Maximiliano N. Rodriguez; Juan José Ponce; Ainara Irastorza; Martin N. Rogel; Noelia B. Carmona; Nerina Canale; Luis A. Buatois; M. Gabriela Mángano (Journal of South American Earth Sciences, 2026)

A hybrid physics-machine learning framework for improving simulations of urban air-conditioning electricity consumption - Xiangwen Deng; Jed J. Cohen; Justin Rodriguez; Bohumil M. Svoma; Chris Gonzales; Matei Georgescu (Energy and Buildings, 2026)

The first complete chloroplast genome of Peruvian “chila” identified as Solanum lasiocarpum: comparative plastomics and phylogenomic insights - Pedro M. Rodriguez-Grados; Angel David Hernández-Amasifuen; Raul Vargas; Carlos I. Arbizu (Genetic Resources and Crop Evolution, 2026)

Shrimp (sub-)national traceability and retail fraud detection using stable isotopes and multi-element profiling - V. Deklerck; R.P. Davis; A. Rodriguez-Zunino; S. Khongtanakrittakorn; S. Hofem; J. Jungkeit; A. Leyton; M. Osorto-Nuñez; C. Podmore; L. Prior; C.C. Smith; B. Soule; et al. (Food Control, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Coevolving landforms, soils and vegetation: Insights into spatial patterns, feedback loops and ecosystem stability thresholds - Mariano Moreno de las Heras; José F. Rodriguez; Patricia M. Saco; Omer Yetemen; Jantiene E.M. Baartman (CATENA, 2026)

First report of phthalate acid esters (plasticizers) in blubber of southern right whales (Eubalaena australis) from Península Valdés, Argentina - Luciana Gallo; Melina Paola Michlig; Maria Rosa Repetti; Agustina Donini; Adrian E. Rodriguez; Mariano Sironi; Marcela M. Uhart (Polar Biology, 2026)
Phthalate acid esters (PAEs) are widely used plastic additives that have become ubiquitous contaminants in marine environments. Filter-feeding baleen whales may be exposed to these pollutants through water, prey or ingested plastic debris. While macroplastics have been reported in the gut of a southern right whale (SRW, Eubalaena australis ), exposure to PAEs has not been assessed. Here, we quantified three lipophilic PAEs, dimethyl phthalate (DMP), dibutyl phthalate (DBP), and di-2-ethylhexyl phthalate (DEHP), in the blubber of 13 SRWs (three calves, three juveniles and seven adults) stranded in 2021 at Península Valdés, Argentina. More than 90% of samples contained detectable PAE levels, and 46.2% were above quantification limits. DEHP and DBP were the most prevalent compounds (61.5% and 30.8%, respectively), although the biological significance of the detected concentrations remains uncertain. This is the first report of PAEs in SRW blubber and suggests potential mother-calf transfer, highlighting exposure of Southern Hemisphere mysticetes to plastic-derived chemicals.

Seasonal changes in the impact of infauna on sediment physical properties - Chesna E. Cox; Kelly M. Dorgan; Nina Stark; Adrian Rodriguez-Marek; Grace Massey; Carl Friedrichs; Md Rejwanur Rahman (Geo-Marine Letters, 2026)

Which soil health indicators best track diversification benefits in tropical agroecosystems? - Anna M. Visscher; Simon Fonteyne; Mirjam Pulleman; Anna Alekseeva; Martin Hartmann; Jose M. Rodriguez-Castellanos; Pankaj Trivedi; Rodolfo Vilchis-Ramos; Sergio Zapata-Martínez; Bruce G. Ferguson; Helda Morales; Steven Vanek; et al. (Applied Soil Ecology, 2026)

High protein diets early in life improve survival, reduce cannibalism, and increase growth and yield in farmed yellow mealworms - N. Dobrowolski; C.D. Perl; J. Brumfield; J. Christie; R. Rodriguez-Guevara; S.O. Durosaro; M. Barrett (Applied Animal Behaviour Science, 2026)

Use of recombinant gonadotropins in goat MOET programs - Shara D.E. Silva; Lucas M. Figueira; Mariana G.K. Rodriguez; Maria Eduarda A. Teixeira; Bruna W. Freitas; Ribrio Ivan T.P. Batista; Felipe Z. Brandão; Joanna M.G. Souza-Fabjan; Luiz Gustavo B. Siqueira; Jeferson F. Fonseca (Animal Reproduction Science, 2026)

A low-cost imaging platform for quantitative characterisation of scaffold surface macrotopography with potential application in craniofacial tissue engineering - X. Marimon; E. Saman-Sakkal; R. Rodriguez; A. Portela; M. Cerrolaza; M. A. Mateos; R. Pérez (Medical & Biological Engineering & Computing, 2026)

A human PBMC-based new approach method reveals PFAS-driven T-cell proliferation and immune dysregulation - Allison Loan; Lauren M. Bradford; Andrée Nunnikhoven; Gong Zhang; Emily Dupuis; Eunnara Cho; Matthew J. Meier; Rocio Aranda-Rodriguez; Azam Tayabali; Kristin M. Eccles; David Prescott (Archives of Toxicology, 2026)
Immunotoxicity has emerged as a key health concern for per- and polyfluoroalkyl substances (PFAS), with animal studies showing reduced T-dependent antibody responses (TDAR) and epidemiological studies reporting decreased vaccine antibody titres. Notably, immunotoxicity is considered one of the most sensitive endpoints for PFAS exposure and has been used to inform regulatory guidance and health-based values. Given that more than 14,000 PFAS exist and are highly environmentally persistent, evaluating the immunotoxicity of individual compounds is critical but impractical, highlighting the need for efficient, human-relevant test systems that provide mechanistically informative, immune-relevant endpoints. Here, we assessed immunomodulatory effects of six PFAS analogues using an in vitro human peripheral blood mononuclear cell (PBMC) model. Two immune stimuli were applied, including lipopolysaccharide (LPS) to trigger innate responses and phytohemagglutinin (PHA) to simulate T-cell-mediated adaptive immune activation. Critically, several PFAS analogues enhanced T-cell proliferation following PHA activation, while a non-inclusive but overlapping subset of analogues suppressed cytokine secretion in response to PHA and LPS. Transcriptomic analyses indicate reduced B-cell identity and immunoglobulin gene expression alongside increased expression of genes associated with T-cell activation and proliferation. These findings implicate a dysregulated coordination between T- and B-cell responses as a potential mechanism underlying PFAS-associated immunotoxicity. Overall, the human PBMC model demonstrated that it is a cost-effective and ethical method for identifying and characterizing key events (KEs) in the adverse outcome pathway (AOP) for PFAS-induced immunotoxicity and has the potential to be refined and incorporated into a robust new approach method (NAM) to assess the next generation of commercial PFAS.

Hydroactive stomata: a key innovation underpinning angiosperm ecological dominance - Javier Pichaco; Celia M. Rodriguez-Dominguez; Antonio Diaz-Espejo (Trends in Plant Science, 2026)

Low-dose inorganic arsenic exposure reprograms macrophages differentiation and function toward tumor-promoting phenotypes - Emily J. Illingworth; Sylvia S. Sanchez; Kristal A. Rychlik; Andre Kleensang; Jason Laird; Gabriel A. Lopez-Cecetaite; M. Carolina Rodriguez Steube; Aakriti Mathur; Pritam Sadhukhan; Daniel A. Medina-Cleghorn; Daniel Nomura; Martyn T. Smith; et al. (Environmental Research, 2026)

Prevalent detection of multiclass environmental chemicals in paired CSF and plasma samples and their potential associations with postpartum depressive symptoms in pregnant women - Bushra Amreen; Corina Lesseur; Ravikumar Jagani; Hiraj Patel; Daniel Katz; Joshua Hamburger; Noel Strong; Leah Habersham; Anna-Sophie Rommel; Lotje D. de Witte; Chris Gennings; M Mercedes Perez-Rodriguez; et al. (Environmental Research, 2026)

The occurrence and removal of antibiotic residues and antibiotic resistance genes in the largest European constructed wetland at Orhei (Moldova) - Mikolaj Wolacewicz; Przemyslaw Decewicz; Maria Eugenia Valdes; Oana-Simina Iaconi; Mihail Todiras; Alina Ferdohleb; Sara Rodriguez-Mozaz; Carles M. Borrego; Lukasz Dziewit (Environmental Pollution, 2026)

Mitral annular plane systolic excursion to left atrial volume ratio as a novel index to assess ventricular filling pressure in dogs with myxomatous mitral valve disease - Jeff M. Perez; Jorge Isidoro Matos; Oscar Monge-Utrilla; Pablo Fernandez-Rodriguez; Soraya Falcon-Cordon; Javier Engel-Manchado (Veterinary Research Communications, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Leveraging outstanding first records to advance invasion science - A. Bortolus; L. A. Meyerson; M. A. Rodriguez-Cabal; E. Schwindt (Biological Invasions, 2026)

Beyond Coverage: A Systematic Review and Thematic Analysis of Delivery, Compliance, Equity and Impact in Mass Deworming for Soil-Transmitted Helminths - Harley M. Rodriguez; Angelica Marie B. Rostata; Jan Joseph Rainer Christorey Maria Salgado; Timothy Liam D. Rivera; Jose Ma. M. Angeles (Acta Parasitologica, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Towards a European small-scale fishing vessel tracking programme: Overview, challenges and opportunities - Tania Mendo; Anna Mujal-Colilles; Einar Hjorleifsson; Pamela Lattanzi; Luca Marsaglia; Mark James; Marta M. Rufino; Helen Holah; Oliver Tully; Jose Rodriguez-Gutierrez; Patrik Jonsson; Estanis Mugerza; et al. (Marine Policy, 2026)

A GIS–AHP Framework for Sustainable Well Placement: Application for Natural Gas and Hydrogen Exploration in the Eastern Cordillera Basin, Colombia - Salim A. Salon; Sebastian S. Rodriguez; Jhon M. Muñoz-Barrera; Fabián Gallego; Cesar Mora; Deysi P. Forero; Jose F. Osorno; Cristian Peñafort (Natural Resources Research, 2026)

An assessment of hypertemporal Sentinel-2 and hyperspectral PRISMA imagery for indirect soil organic matter and pH mapping in a forested Mediterranean area - Francisco M. Canero; Victor Rodriguez-Galiano (CATENA, 2026)

Influence of dietary linoleic acid inclusion on fatty acid composition in barrows and gilts and its relationship to fat accumulation - Deysi Guevara-Freire; Rosa M. Escudero; Luis Calvo; Ana I. Rodriguez; Raquel Reina; José Ignacio Morales; Álvaro Olivares; Clemente López-Bote (Meat Science, 2026)

Age at menarche and exposure to non-persistent pesticides in Spanish girls from the INMA (environment and childhood) project - Carmen Freire; Alicia Olivas-Martinez; Francesca Castiello; Alba Jimeno-Romero; Sara Lopez de Calle; Beatriz Suárez; Adonina Tardón; Marta M. Rodriguez-Suarez; Mònica Guxens; Martine Vrijheid; Andrea Beneito; Maria-Jose Lopez-Espinosa (Environmental Research, 2026)

Per- and polyfluoroalkyl substances and pesticides in black bears (Ursus americanus) and grizzly bears (Ursus arctos horribilis) from Montana's Cabinet-Yaak ecosystem: A baseline assessment of emerging and legacy contaminants - Brian C. Balmer; Marina D. Rodriguez; Justin E. Teisberg; Michelle L. Hladik; Wayne F. Kasworm; Amber Kornak; Thomas G. Radandt; Landon M. Keele; Erin L. Pulster (Environmental Pollution, 2026)

Bioactive Extracts from Yucatán Marine Invertebrates as Modulators of Microalgal Dynamics - Dawrin Pech-Puch; Rita Pires; Bárbara A. Rebelo; Diana Grilo; Carlos Gonzáles-Salas; Susana Eunice Calva-Pérez; Susana M. Gomes; Harold Villegas-Hernández; Sergio Guillén-Hernández; Abel M. Forero; Jaime Rodriguez; Carlos Jiménez; et al. (Marine Biotechnology, 2026)
The marine environment is a rich source of bioactive compounds with a wide range of applications. In this study, 65 extracts from sponges, ascidians, and a gorgonian collected from the Yucatán Peninsula, Mexico, were evaluated for their modulatory effects on the growth of four microalgal species. Some extracts were found to exhibit pronounced algicidal activity, while others promoted growth. Bioassay-guided fractionation of the extract from Haliclona (Rhizoniera) curacaoensis led to the identification of arenosclerins A and C as potent algicidal agents, active across all tested microalgae. In contrast, the extract from Halichondria melanadocia enhanced microalgal growth, and chemical analysis revealed the presence of medelamine A and B as putative growth-promoting compounds. This study provides a new report on microalgae-modulating activities of marine sponge metabolites. The dual activity observed, both inhibitory and stimulatory, not only contributes to our understanding of marine compound diversity but also underscores the potential of these marine-derived compounds for sustainable environmental management practices.

Plant domestication influences the distribution and host-location behavior of entomopathogenic nematodes - Monique J. Rivera; Albrecht M. Koppenhöfer; Cesar Rodriguez-Saona; Rubén Blanco-Pérez (Applied Soil Ecology, 2026)

Palynostratigraphic analysis of lower Cretaceous sediments in the Golfo San Jorge Basin, central Patagonia, Argentina - V.S. Perez Loinaze; N. Ortiz Ruffinelli; R. Rodriguez; M. Cevallos (Cretaceous Research, 2026)

Optimism predicts future economic mobility among hurricane maria migrants - Maria Duque; Yara Acaf; Christopher P. Salas-Wright; Mildred M. Maldonado-Molina; Pablo Montero-Zamora; Evelyn Gualdron; Mia Cisco; Sumeyra Sahbaz; Carolina Scaramutti-Gladfelter; Lawrence G. Watkins; Duyen H. Vo; Seo Woo Lee; et al. (Climate and Development, 2026)

Transcriptomic response of Acropora cervicornis following transplantation to a marginal, nearshore environment - Allyson DeMerlis; Colin Foord; Dalton J. Hesley; Richard F. Karp; Lys M. Isma; Natalia Andrade-Rodriguez; Kevin H. Wong; Michael S. Studivan; Mike Jankulak; Andrew C. Baker; Diego Lirman; Nikki Traylor-Knowles; et al. (Frontiers in Marine Science, 2026)
As reef-building coral cover has declined worldwide, coral restoration has become a widespread response towards repopulating degraded reefs. In-situ nurseries have provided refugia for the regrowth of several coral species, yet long-term success following outplanting remains highly variable, particularly when corals are introduced into novel or marginal environments. Additionally, while growth and survivorship are commonly used to evaluate restoration success, molecular responses may also provide critical insights into the capacity of corals to acclimatize following transplantation. Here, we examined host and algal symbiont gene expression in the critically endangered reef-building coral Acropora cervicornis following transplantation from an offshore nursery in Key Biscayne, Florida to a nearshore, urbanized habitat in the Port of Miami, Florida. Three nursery-propagated genotypes were outplanted in June 2021 and sampled after four months at both sites for transcriptomic analysis ( n =12 after quality filtering). Transplanted corals exhibited significant shifts in host gene expression relative to nursery controls, with 961 host and symbiont genes significantly upregulated and 165 significantly downregulated. Upregulated host genes were predominantly associated with the environmental stress response, including heat shock proteins, unfolded protein binding, apoptotic processes, detoxification pathways, and innate immune signaling. Weighted gene co-expression network analysis identified two host modules positively associated with the nearshore outplant site and were enriched for pathways related to protein folding, immune activity, and cellular reorganization. These results demonstrate that A. cervicornis outplanted to a nearshore, urbanized environment exhibits sustained activation of stress- and immune-related molecular pathways months after transplantation, which is consistent with a stress-response profile that may reflect ongoing acclimatization. Integrating molecular diagnostics with environmental monitoring may refine genotype and site selection to enhance restoration outcomes.

Non-Candida fungal cholecystitis - an uncommon occurrence even in the right host - Mitchell G. Dumais; Mary M. Czech; Mustafa A. Hyder; Rachel R. Lee; Juan C. Gea-Banacloche; Christopher G. Kanakry; Sun A. Kim; Bindu Adhikari; Matthew D. Surette; Adrian M. Zelazny; Amir Seyedmousavi; Jennifer M. Cuellar-Rodriguez (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Invasive fungal infections (IFI) are a significant cause of morbidity and mortality in hematologic malignancy patients and hematopoietic cell transplant (HCT) recipients. Mold cholecystitis has rarely been described. We present a case of disseminated Lomentospora prolificans , that had recrudescence of symptoms with acute cholecystitis. Treatment included a temporary cholecystostomy and administration of the novel antifungal fosmanogepix. At 6 weeks post-HCT, the patient underwent cholecystectomy and completed a course of fosmanogepix, leading to resolution of her infection. Here we review the published literature on non- Candida fungal cholecystitis, underlying risk factors and treatment.

Comparative evaluation of sperm quality assessment methods in purebred spanish horses - N. Latorre; C. Gómez-Cuétara; E. Cañizares; F. Crespo; V. Pérez-Aguilera; M. Iniesta Cuerda; J.A. Laborda-Gomariz; A.J. Soler; E.R.S. Roldan; A. Sanchez-Rodriguez (Journal of Equine Veterinary Science, 2026)

Ground level enhancement GLE #77 on 11 November 2025: a data summary - A.L. Mishev; B. Heber; K.-L. Klein; R. Vainio; H. Mavromichalaki; O. Raukunen; N. Larsen; N. Petrov; N. Nikonov; S. Masson; M. Pesce-Rollins; B.T. Kress; et al. (Advances in Space Research, 2026)

Innovative 3D-Image Analysis of Cerebellar Vascularization Highlights Angiogenic Gene Dysregulations in a Murine Model of Apnea of Prematurity - A. Rodriguez-Duboc; C. Racine; M. Basille-Dugay; D. Vaudry; B. Gonzalez; D. Burel (The Cerebellum, 2026)
Apnea of prematurity (AOP) affects 50% of preterm infants causing intermittent hypoxia (IH), which can lead to long-term neurodevelopmental deficits. Cerebellar abnormalities have been observed in AOP but the relationship between vascular alterations and neural development remains unclear. This study investigates how IH affects cerebellar angiogenesis using a murine model of AOP. We developed an innovative 3D imaging workflow combining Imaris and VesselVio software to quantitatively analyze cerebellar vascularization at different postnatal stages (P4, P8, P12, P21, and P70). We correlated these results with a transcriptomic analysis of 23 angiogenesis-related genes in the same stages to uncover the associated molecular pathways. We found that IH induced significant vascular changes, particularly at P4, with a global increase in vascular-network dimensions. By P8, the vascular network normalized, but genes were downregulated in all pathways studied. After P12, at the end of the IH protocol, transcriptional regulations had varied but persisted long-term. Moreover, differential analysis showed distinct effects on superficial versus deep vascular networks, allowing for a more precise understanding of remodeling patterns throughout development. Overall, transcriptomic changes were associated with morphological alterations in a time-dependent manner, suggesting a multiphasic IH response through development with lasting effects. Key regulations included VEGF, angiopoietin, and matrix metalloprotease signaling. These findings demonstrate that IH disrupts cerebellar angiogenesis in parallel with neurogenesis, potentially contributing to the neurodevelopmental deficits observed in AOP. Thus, the interconnected nature of angio- and neurogenesis during cerebellar development makes it crucial to take vascular aspects into account in therapeutic approaches to neurodevelopmental disorders.

Deacetylation and Mechanical Refining Pathway for the Bioconversion of Sugarcane Bagasse - Fernando Roberto Paz Cedeno; Gustavo R. Gomes; Jessica J. Silva; Fabricia F. Menezes; Viviane M. Nascimento; George J. M. Rocha; Renata P. Rodriguez; Xiaowen Chen; Antonio Bonomi; Carlos Driemeier (BioEnergy Research, 2026)
Advancing lignocellulose biorefining is imperative for the deployment of cellulosic (2G) biofuels. This work investigates the tailoring of the alkaline deacetylation and mechanical refining (DMR) pathway for the bioconversion of sugarcane bagasse. Experiments are conducted at laboratory and pilot scales, varying the pretreatment conditions (70–92 °C; 48–100 g NaOH /kg) and the mechanical refining technologies (PFI and disk refining). The pretreatments selectively solubilize acetyl groups (> 86%) and lignin (10–63%) while mostly preserving structural carbohydrates in the solid phase. Enzymatic hydrolysis generates hydrolysates of clean sugars (glucose and xylose), with sugar yields increasing up to 81% for glucose and 89% for xylose in response to delignification and mechanical refining. Biochemical methane potential assays reveal specific methane productions of up to 568 NmL CH₄ gVS⁻¹ for alkaline liquor monodigestion and 344 NmL CH₄ gVS⁻¹ for co-digestion with sugarcane vinasse from the conventional (1G) sugarcane ethanol, indicating a strong potential for bioenergy recovery from this process stream. Synergies are identified in integrating 1G ethanol, 2G DMR processing of bagasse, and anaerobic co-digestion of 1G vinasse and 2G DMR alkaline liquor. This technology enables sugarcane biorefineries to enhance the co-production of ethanol, methane, and concentrated streams of CO 2 .

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Interspecific SCNT in yak followed by embryo aggregation improves early in vitro developmental parameters without restoring pluripotent gene expression - M. Yauri Felipe; M. Duque Rodriguez; A. De Stefano; L.D. Ratner; V. Alberio; D.F. Salamone (Theriogenology, 2026)

Mapping soil heavy metals in a geologically complex Mediterranean forested area: an interpretable machine learning approach - Francisco M. Canero; Maria Paula Mendes; Victor Rodriguez-Galiano (Remote Sensing Applications: Society and Environment, 2026)

Cytotoxic Edema and Intra-parenchymal Hemorrhage: A Mediated Pathway to Mortality and Functional Outcome in Cerebral Venous Sinus Thrombosis- A sub-analysis of the CLOT-VENUS Registry - Nashwa Abdelhakim; Milagros Galecio-Castillo; Piyush Kalakoti; Leonardo Cruz-Criollo; Aaron Rodriguez-Calienes; Anderson Brito; Jorge Cespedes; Amir Shaban; Anish Venkatesan; Vanessa Cano Nigenda; Andres Alberto Mercado Pompa; Nicholas M. Mohr; et al. (Translational Stroke Research, 2026)
Cytotoxic edema (CE) is a radiographic marker of early tissue injury in cerebral venous thrombosis (CVT) associated with poor outcomes, yet its mechanistic pathway remains unclear. We investigated whether intraparenchymal hemorrhage (IPH) mediates the association between CE and outcomes. We conducted a retrospective cohort study using the multicenter CLOT-VENUS registry, including acute CVT patients treated at two Comprehensive Stroke Centers in the USA and Mexico (2004–2024). CE was defined as hyperintensities around IPH or venous infarct with DWI restricted diffusion and corresponding low ADC, confirming true restricted diffusion. IPH was defined as hemorrhagic transformation of venous infarction or intracerebral hemorrhage on GRE MRI and/or NCCT. Mediation analyses assessed whether IPH mediated CE associations with in-hospital mortality and functional outcomes. Among 394 patients (mean age 42.7 years; 65.5% female), 128 (32.5%) demonstrated CE and 111(30.2%) IPH. CE was associated with in-hospital mortality (aOR 2.63, 95% CI 1.01–7.12) and poor 6-month mRS (aOR 1.71, 95% CI 1.06–2.74). CE was associated with IPH, which in turn was associated with mortality (aOR 8.73, 95% CI 2.93–30.45) and poor mRS (aOR 1.96, 95% CI 1.18–3.25). Adjustment for IPH rendered the CE-outcome associations non-significant. IPH accounted for 76.8% of CE’s effect on mortality and 83.8% on 6-month mRS. Our findings suggest that IPH likely mediates the effect of CE on outcomes in CVT. Although the temporal sequence could not be confirmed, the results underscore the value of early CE detection for timely intervention.

Spatial Modeling of Sugarcane Yield Using Machine Learning Approaches - Diego A. Socadagui-Casas; Andres F. Rodriguez-Vasquez; Yolanda Rubiano-Sanabria; Daniel M. Jimenez-Gutierrez; Sonia R. Socadagui-Casas (Sugar Tech, 2026)
Sustainable precision agriculture and artificial intelligence (AI) are transforming modern farming by enhancing resource efficiency, addressing climate challenges, and fostering sustainability. In Colombia, sugarcane cultivation is pivotal in the agricultural economy, particularly in the Cauca River Valley, a region grappling with climate variability and resource optimization challenges. This study introduces an innovative methodology that combines machine learning (ML) techniques with geospatial data to predict sugarcane yields accurately. The research employs the CatBoost, random forest, and XGBoost ML algorithms, integrating historical data on climate, soil characteristics, and agricultural management practices to develop spatially detailed predictive models. The findings demonstrate that ML-based approaches outperform traditional methods like linear and penalized regressions, offering more precise agricultural planning and resource management predictions. Focused on the municipality of La Candelaria, this work underscores the potential of ML technologies to enhance productivity while promoting sustainable agriculture.

Petiole Nitrate Analysis: A Diagnostic Method for Optimizing Nitrogen Management in Potato - C. M. Giletto; W. Carciochi; S. E. Silva; M. N. Cassino; S. Rodriguez; J. C. Laborde Amador; E. C. Zamuner; N. I. Reussi Calvo (Potato Research, 2026)

Using genomic tools to evaluate assumptions in a conservation breeding program for endangered red siskins (Spinus cucullatus) - Karen M. Holm; Kathryn M. Rodriguez-Clark; Brian J. Coyle; Rebecca M. Gooley; Erica Royer; Emperatriz Gamero García; Haw Chuan Lim (Conservation Genetics, 2026)
Ex situ conservation breeding programs can provide essential support for recovering endangered species. However, breeding recommendations and strategies may be suboptimal due to untested or incorrect assumptions about conservation units, hybrid ancestry, inbreeding history and family relationships. While genomic approaches have been used to address specific questions in ex situ programs, they are not yet routinely used to test and adjust assumptions, often due to limitations in sample availability and quality particularly at the start of a new program. Using a new conservation breeding program for the endangered red siskin ( Spinus cucullatus ) as an example, we demonstrate how genomic data from a relatively small number of samples, of uneven quality, may be employed to critically examine fundamental assumptions. Using genetic data from 72 individuals, we confirmed strong differentiation between birds from Venezuela and Guyana, supporting an assumption that they should not be mixed in a conservation breeding program. Molecular estimates of genetic diversity and inbreeding also aligned with assumptions that widespread historical illegal trade had introduced the species’ Venezuelan wild diversity into U.S. avicultural flocks. We found no evidence of hybrid ancestry with canaries, which would have resulted from intentional crosses to produce red-colored canaries. Finally, while observational pedigree data were generally reliable, molecular relationship assignments and kinship estimates had high accuracy only for first-degree relatives, limiting our ability to evaluate assumptions about relatedness. Our results highlight the utility of constrained but informative datasets for developing conservation breeding programs, supporting effective management for the long-term survival of endangered species.

Decoupled Climatic Drivers of Tree and Ground‐Layer Carbon Uptake in Mountain Ecosystems Around the World - Max Mallen‐Cooper; Maja K. Sundqvist; David A. Wardle; Radim Šarlej; Rose E. Brinkhoff; Aimée T. Classen; Eliška Kuťáková; Daniel B. Metcalfe; M. Noelia Barrios‐Garcia; Julie R. Deslippe; Kobayashi Makoto; Jane Mallen‐Cooper; et al. (Global Change Biology, 2026)
One of the key ecological processes affected by climate change is plant carbon uptake. However, there is substantial uncertainty about how plant carbon uptake will respond to warming in mountain ecosystems, which are known for sharp temperature gradients and abrupt shifts in vegetation structure. Specifically, we lack an understanding of whether these response trajectories over time will be linear or non‐linear, and how they might vary among mountain ecosystems globally. Here, we measured ecosystem Gross Primary Productivity (GPP) along forest‐tundra elevational gradients in the mountain regions of five countries (Argentina, Australia, France, Sweden, USA) to infer future trajectories of carbon uptake, and whether any non‐linear changes might occur. We also examined the role of microclimate in driving GPP responses. We found that whole‐ecosystem GPP increased with increasing macroclimatic temperature (decreasing elevation), but this response was dominated by a sharp non‐linear increase at the transition from tundra to forest (i.e., the treeline). In contrast, ground‐layer GPP was largely independent of macroclimate, but often responded strongly, and linearly, to microclimate (growing degree days > 5°C, mean growing season temperature). This pattern reflected a frequent decoupling of microclimate from the expected temperature‐elevation relationship, likely driven by such processes as cold‐air drainage, limited near‐surface air mixing, and shading by trees. The contrasting responses of GPP among global temperature gradients indicates strong context dependence at both local and continental scales, although in a few cases, biomass and leaf nitrogen were important moderators. These findings suggest that future shifts in carbon uptake in mountains will be mainly controlled by tree range expansion. Our results highlight the need to consider species responses on different spatial scales, and to increase representation of undersampled regions to capture the full breadth of ecological responses to climate change.

Expanding the arsenal: non-conventional insecticides for managing pyrethroid-resistant Aedes aegypti - Daniela Cerda-Apresa; Selene M. Gutierrez-Rodriguez; Jesus A. Davila-Barboza; Iram P. Rodriguez-Sanchez; Victoria Pando-Robles; Beatriz Lopez-Monroy; Humberto Quiroz-Martinez; Guadalupe Rojas-Verde; Adriana E. Flores (International Journal of Tropical Insect Science, 2026)

Rethinking nature-based solutions in informal settlements: community perceptions of urban risk in Durán, Ecuador - Margot Mattson; Isabella Pacenza; Shruti Jadala; Carlos Romero; Addison Martin; Marta Berbes-Blazquez; Elizabeth M. Cook; Mathieu Feagan; Mercy Borbor-Cordova; Pilar Cornejo-Rodriguez; Nancy B. Grimm (Climate and Development, 2026)

Assessment of the efficacy of percussive stunning in the industrial slaughter of turbot: New evidence from electroencephalography - C.A. Ramirez-Rodriguez; A. Verde; M.A. López-Patiño; M. Conde-Sieira; M. Alborja-Valado; O. González -Barreiro; A. Riaza; M. Chivite; J.M. Míguez (Aquaculture, 2026)

From potato peels to power: Evaluation and scale-up simulation of hydrochar as catalyst for water splitting - Aida M. Díez; Miguel A. Rodriguez; Adrián Cabarcos; Sergio Chapela; M.Ángeles Sanromán; Marta Pazos (Fuel, 2026)

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Carbon source-induced changes in the transcriptional landscape of Novacetimonas hansenii - Bashir A. Akhoon; Jordan Corley; Jia W. Tan; Roberta Magnani; Rachel R. Schendel; Andrew Lipton; Carlos M. Rodriguez Lopez; Kendall R. Corbin (Bioresource Technology, 2026)

Hydraulic Fracture Propagation in Pre-structured Media: Stress Field and Fracture Network Topology - Adrian V. Garcia; Rached M. Rached; Carlos D. Rodriguez-Hernandez; J. Carlos Santamarina (Rock Mechanics and Rock Engineering, 2026)

Contributions to the knowledge of DNA barcodes and diversity of intertidal and shallow-water mollusks in the Beagle Channel - L. D. Chiberry; J. Sánchez; V. M. Núñez; S. Rodriguez; M. Pellegrino; S. Poljak (Polar Biology, 2026)

Governance Arrangements That Fit Social‐Ecological Context Are Associated With Fishery Sustainability - Mateja Nenadović; Alfredo Giron; Timothy Frawley; Adrian Munguia‐Vega; Kara E. Pellowe; Erica Ferrer; David Gill; Blanca González‐Mon; Andrew F. Johnson; Emilie Lindkvist; Fiorenza Micheli; Amy H. Weaver; et al. (Fish and Fisheries, 2026)
In many parts of the world, natural resources are primarily managed by governance arrangements at the local level. Those arrangements range from collective, such as cooperatives and associations, to individualistic, such as patrons and owner‐operators. A key question is how such arrangements influence resource use and associated social and ecological outcomes. We hypothesize that sustainable resource use is not associated with a specific governance arrangement, but instead that every type of arrangement has a certain set of social and ecological conditions under which sustainable resource use is feasible. This hypothesis was empirically investigated using fisheries landings data from Mexico. We found that sustainable resource use can be achieved through multiple governance arrangements provided that they are matched to appropriate social‐ecological contexts. Our findings help identify which governance arrangements are best suited to particular contexts and provide the initial building blocks for developing a theory of governance contextual fit in social‐ecological fishing systems.

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Natal homing in male green turtles (Chelonia mydas) from two neotropical islands - Marco A. Garcia-Cruz; Kathryn M. Rodriguez-Clark; Karen A. Bjorndal; Alan B. Bolten; Eugenia Naro-Maciel; Claudio Bellini; Brian Shamblin; Carlos Carreras (Frontiers in Marine Science, 2026)
Studying the origins of male green turtles is critical for assessing their poorly understood natal homing behavior, compared to that of females, which have a high degree of fidelity to their nesting beach of their birth. Between 2005 and 2012, we collected 379 tissue samples from male and female green turtles ( Chelonia mydas ) to test the hypothesis that there is no difference in natal homing between the sexes in two tropical Island mating areas of the western Atlantic: Isla de Aves, Venezuela, and Atol das Rocas, Brazil. We sequenced an ~800bp fragment of the mtDNA control region from each individual and characterized their haplotype profiles. Comparisons between males and females from rookeries and their closely associated offshore courtship areas revealed no significant genetic differentiation between males and females at either site, suggesting that males also return to their hatching site to breed. To examine fidelity of males to their natal region in more depth, we combined our results with published data from 2,350 individuals from 31 green turtle rookeries in the Gulf of Mexico, Caribbean Sea, Atlantic Ocean, and the Mediterranean Sea. Considering contributions of 1% or more, a mixed stock analysis of four regional haplotype groups revealed that adult males sampled at Isla de Aves originated from rookeries in the eastern Caribbean, mainly from Isla de Aves itself (95.3%). Also, haplotype frequencies indicated that adult males sampled at Atol das Rocas originated mainly from Atol das Rocas (74.5%), possibly with small (on average 4%) contributions from five other regional rookeries. These combined results also suggest that males from both Isla de Aves and Atol das Rocas return to their natal regions to reproduce, as do females. This study provides the first direct evidence of male natal homing in green turtles in two populations of the western Atlantic and confirms that this phenomenon, previously observed in Australian green turtles, also occurs there. Understanding the factors that contribute to varying degrees of homing to courtship areas is essential for evaluating the demographic independence of populations. It further allows for a more accurate assessment of their vulnerability to regional threats.

Aquaculture shapes antibiotic resistance in Mediterranean gilthead sea bream farming: From hatcheries to offshore cages - Marco Basili; Eleni Nikouli; Frederik D. Møller; Konstantinos A. Kormas; Gian Marco Luna; Veronica Tolosa-Enguís; Sonia M. Rodriguez-Ruano; Yolanda Sanz; Marco Candela; Grazia Marina Quero; Frank M. Aarestrup; Pimlapas Leekitcharoenphon (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Nationwide integrative analysis of pyrethroid resistance in Aedes aegypti from Mexico - Kevin A. Ontiveros-Zapata; Alan E. Juache-Villagrana; Selene M. Gutierrez-Rodriguez; Jesus A. Davila-Barboza; Iram P. Rodriguez-Sanchez; Beatriz Lopez-Monroy; Magaly Romero-Villarreal; Emma Gomez-Ruiz; Adriana E. Flores (Pesticide Biochemistry and Physiology, 2026)

Developing a cost and time efficient strategy for assessing novel materials for wastewater treatment with non-target screening analysis - Alba Rodriguez-Otero; Selina Tisler; Lisa M. Reinhardt; Mathias B. Jørgensen; David I. Pattison; Brice Bouyssiere; Jan H. Christensen (Journal of Hazardous Materials, 2026)

Hydrologic connectivity as a predictor of degradation thresholds across semiarid sites with different vegetation patterns - Samira Azadi; Patricia M. Saco; Mariano Moreno-de las Heras; Jose F. Rodriguez (CATENA, 2026)

Quantifying Time-Lagged Vegetation Responses to Hydroclimatic Factors in Dam-Influenced Arid Regions Using VAR Modeling and Remote Sensing - Raid Almalki; Mehdi Khaki; Patricia M. Saco; Jose F. Rodriguez (Environmental Management, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Changes in Key Biodiversity Area networks following national comprehensive assessments - Andrew J. Plumptre; Zoltan Waliczky; Daniele Baisero; Olivia Crowe; Jeannot Kivono; Cecilia Tobar; Maria Gabriela Toscano; Natalia Boulad; Hugo Costa; Camila Davila; Sophie Dirou; Eleuterio Duarte; et al. (Conservation Biology, 2026)
Key Biodiversity Areas (KBAs) are sites of significance for the global persistence of biodiversity. Based on the Global Standard for the Identification of Key Biodiversity Areas (KBA Standard), published in 2016, sites are currently being assessed for KBA designation in a growing number of countries across the world. For these assessments, the KBA criteria are applied to all species and ecosystems with available data. We reviewed the first comprehensive assessments of 11 countries and compared the KBA network before and after assessments. The mean (SD) number of KBAs per country increased by 69.6% (102.1), and the mean total extent of KBAs per country increased by 164.2% (150.7). More than half of the KBAs in 2024 had >50% of their area outside the 2019 KBAs, indicating a substantial increase in KBA extent (54.0% [18.8] of KBAs). The mean proportion of each KBA covered by protected or conserved areas decreased from 56.2% (20.2) to 44.5% (15.5), owing to the incorporation of unprotected sites in the KBA network. On average, 41.1% (14.0) of sites in each country (mean 44.5 [46.4] sites per country) and 47.2% (20.5) of new KBA area after the assessment were completely unprotected, indicating that many of the new sites were not recognized in national protected area networks as significant for biodiversity before the assessment. Making a comprehensive assessment of KBAs increased the combined coverage of protected and conserved area networks from 25.4% (10.6) to 32.0% (13.1) in each country and thus contributed to reducing biodiversity loss. Therefore, comprehensive assessments of KBAs led to a substantially increased number and extent of recognized sites of importance for biodiversity published in the World Database of KBAs. Where such assessments have not been made, many important areas for biodiversity may be overlooked. We therefore encourage other nations to update their KBA networks to inform efforts to meet the goals and targets of the Kunming–Montreal Global Biodiversity Framework.

First Detection of the L1014F kdr Mutation in Triatoma dimidiata, a Vector of Chagas Disease in Mexico - Jesus A. Davila-Barboza; Selene M. Gutierrez-Rodriguez; Iram P. Rodriguez-Sanchez; Adriana E. Flores (Neotropical Entomology, 2026)

Impacts of Diverse Stakeholder Participation on Fisheries Management - Sangeeta Mangubhai; S. L. Smith; Z. Davis; N. Koedyker; J. Augustyn; D. Durholtz; S. Fulton; Harlisa; M. T. Hidayat; L. Hiriart-Bertrand; M. Khazali; E. Litsinger; et al. (Coastal Management, 2026)

High frequency of plastic-derived contaminants (phthalate acid esters) in the preen gland of dead procellariiform seabirds from the Patagonian Sea - Luciana Gallo; María Rosa Repetti; Melina Paola Michlig; Leandro L. Tamini; Leandro N. Chavez; Ruben F. Dellacasa; C. Karina Alvarez; Sergio A. Rodriguez Heredia; Ralph Eric Thijl Vanstreels; Patricia Pereira Serafini; Marcela M. Uhart (Marine Pollution Bulletin, 2026)

“Fulfilling the hunger”: A qualitative study to understand the etiology of binge eating in adolescents experiencing food insecurity - Vivienne M. Hazzard; Moraima Rodriguez; Dianne Neumark-Sztainer; Jerica M. Berge; Marian Tanofsky-Kraff; Melissa N. Laska (Appetite, 2026)

River and sea imprinting of toxic trace elements in Iberian wild Salmo salar. Implications for environmental health - Paula M. Joseph; Alvaro Gutierrez-Rodriguez; Gonzalo Machado-Schiaffino; Sara Fernandez; Eva Garcia-Vazquez (Science of The Total Environment, 2026)

The rhythms of environmental conditions, particles dynamics, and barnacle activity captured by underwater imaging in sub-Antarctic kelp forests of the Beagle Channel - E. Trudnowska; P. Balazy; M. Bagur; P. Kuklinski; J. Kaminsky; K. Balazy; M. Rodriguez; Z. Derwich; G. Lovrich (Progress in Oceanography, 2026)

The effect of clay minerals on Li in martian groundwater simulant - Rachel Y. Sheppard; Jessica M. Weber; Laura E. Rodriguez; Cathy Trejo; Elisabeth M. Hausrath; Laura M. Barge (Icarus, 2026)

Impact of high-amylose starch addition on the resistant starch content and the physicochemical properties of maize (Zea mays L.) cookies - Ludy M. Martinez-Rubio; Ivan Luzardo-Ocampo; Oscar Y. Barrón-García; Mario E. Rodriguez-García; Guadalupe Loarca-Piña; Marcela Gaytán-Martínez (Food Chemistry, 2026)

Occupants’ willingness to share information for improved comfort and energy efficiency in offices - Marcel Schweiker; Dimitris Potoglou; Farah AlAtrash; Eleni Ampatzi; Maíra André; Elie Azar; Karol Bandurski; Leonidas Bourikas; Carolina Buonocore; Bin Cao; Giorgia Chinazzo; Rania Christoforou; et al. (Building and Environment, 2026)

Biochar enhances nitrogen use efficiency in lettuce by promoting its metabolic assimilation - Alvaro F. Garcia-Rodriguez; Francisco J. Moreno-Racero; Rosario Álvarez; José M. Colmenero-Flores; Heike Knicker; Miguel A. Rosales (Plant and Soil, 2026)
Background and aims Peat replacement with biochar (BC) offers a sustainable strategy in horticultural substrates but its effects on plant nitrogen (N) metabolism and N use efficiency (NUE) remain unclear. This study tested whether vineyard-pruning-derived BC can boost NUE and metabolic activity in lettuce, providing a pathway toward more productive and sustainable horticulture. Methods Plant substrates (BC, peat and vermiculite) were prepared in the following proportions (v:v:v): B0 (0:70:30), B15 (15:55:30) and B30 (30:40:30) for growing lettuce (Lactuca sativa L. var. Batavia) under greenhouse conditions for 31 days. We assessed plant growth and physiological traits, quantified N species and calculated NUE parameters and the activities of key N assimilation enzymes. Results B30 plants produced 44.2% more biomass and 23.2% larger leaf area than B0, resulting in lower specific leaf area and greater succulence. BC addition decreased available NO₃⁻ and NH₄⁺ in substrate and roots without causing any plant stress symptoms, as chlorophyll content and PSII efficiency remained stable. B30 increased N uptake flux, N utilization efficiency, partial N balance, and N productivity by 31.8%, 34.8%, 27.8%, and 13.8%, respectively, relative to B0, coinciding with enhanced N-assimilation enzymatic activity. Despite lower total N in roots and shoots, protein accumulation increased, indicating more efficient N conversion into organic compounds. Conclusion These findings demonstrate the potential of BC-based substrates (especially 30% BC) to enhance lettuce productivity by improving NUE through the stimulation of N assimilation pathway, offering a promising strategy to optimize N-fertilizer needs to support more sustainable agriculture and soil management practices.

Citral impairs intestinal changes caused by ulcerative colitis through modulation of antioxidant, anti-inflammatory and healing activities - Maycon T. Emílio-Silva; Vinícius P. Rodrigues; Antonio J. Ruiz-Malagon; Isabela G. Guidolin; Felipe L. Dario; Mariana M. Fioravanti; Alba Rodriguez-Nogales; Julio Gálvez; Clelia A. Hiruma-Lima (Inflammopharmacology, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Integrative systematics of the Brazilian tree “sucupira”: morphological, cytogenetic and genomic boundaries of Pterodon emarginatus Vogel and P. pubescens (Benth.) Benth. (Leguminosae, Papilionoideae) - Victória B. Albernaz; Yennifer Mata-Sucre; Mariela A. Sader; Pablo E. Rodriguez; Cíntia P. Targueta; Adriana M. Antunes; Rafael B. Pinto; André Marques; Dulce Maria Sucena D. A. Rocha; Gustavo Souza; Thannya N. Soares (Systematics and Biodiversity, 2025)

A single injection of a long-acting oxytocin analog (carbetocin) at estrus onset synchronizes ovulations and enhances ovulation rate in ewes - Bottino JP; Rodriguez MGK; Santos JDR; Vazquez MI; Ratto M; Ungerfeld R (Theriogenology, 2025)

Covalent organic framework-coated alumina for the removal of geosmin from water in recirculating aquaculture systems - Ana Vieira; Joana Araújo; Pablo Blanco Canella; Silvia Escudero-Curiel; Soraia P.S. Fernandes; Laura Rodriguez-Lorenzo; Juliana P.S. Sousa; Liliana P.L. Gonçalves; Salomé G.P. Soares; Marta Pazos; M. Ángeles Sanromán; Yury V. Kolen’ko; et al. (Journal of Environmental Chemical Engineering, 2025)

Comparison of the efficacy of a biocompatible and a distillable solvent for pretreatment of mixed bioenergy feedstocks - Md Maksudur Rahman; Matteo Ceriani; Seontae Kim; Venkataramana R. Pidatala; Hemant Choudhary; Blake A. Simmons; John M. Gladden; Alberto Rodriguez (Biomass and Bioenergy, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Multi-objective optimization of glutathione production by Saccharomyces cerevisiae in a mini-bubble column reactor via a multifactorial batch-design approach - Isabella Giraldo-Rodriguez; Ángela M. Ossorio-Tróchez; Isabella M. Giraldo-Castro; Carlos A. Diaz; Andres Ceballos-Bermudez; Carlos A. Alvarez-Vasco; Colomba M. Dazzarola; José R. Perez-Correa; Nelson H. Caicedo-Ortega (Bioresource Technology Reports, 2025)

The CALHM1 blocker CGP37157 increases seizure severity during status epilepticus in adult mice - Meghma Mitra; Amaya Sanz Rodriguez; Norman Delanty; Alan Beausang; Francesca M. Brett; Michael A. Farrell; Jane Cryan; Donncha F. O’Brien; David Henshall; Maria F. Cano-Abad; Tobias Engel (Purinergic Signalling, 2025)
Epilepsy is one of the most common chronic brain diseases affecting up to 70 million people worldwide. Major challenges of epilepsy treatment include the high pharmacoresistance in patients and the lack of disease-modification. Extracellular adenosine 3’triphosphate (ATP), a key neurotransmitter in the activation of the purinergic signalling system, is increasingly recognized to contribute to pathological brain hyperexcitability in epilepsy. Consequently, targeting ATP-release mechanisms may constitute a new therapeutic strategy for seizure control and epilepsy. The calcium channel, Calcium Homeostasis Modulator 1 (CALHM1), a voltage-gated, non-selective ion channel that permits the passage of various cations and small molecules, is expressed in neurons and plays an essential role during neuronal excitability and neurotransmission. In addition to ions, CALHM1 also allows the passage of ATP into the extracellular space, activating thereby purinergic receptors. Here, we tested if the pharmacological blocking of CALHM1 via CGP37157 (7-chloro-5-(2-chlorophenyl)-3,5-dihydro-4,1-benzothiazepin-2-(1H)-one) alters the severity of intra-amygdala kainic acid-induced status epilepticus. Our results show that CGP37157 increased the severity of seizures during status epilepticus. In addition, CALHM1 protein levels are down-regulated in the hippocampus in epileptic mice and Temporal Lobe Epilepsy (TLE) patients. In summary, our results identify CALHM1 as a new contributor to seizures and suggest targeting of CALHM1 as new treatment strategy for epilepsy.

Probiotic Potential of Yeast, Mold, and Intermediate Morphotypes of Geotrichum candidum in Modulating Gut Microbiota and Body Physiology in Mice - Madeeha Gohar; Nida Shaheen; Sagar M. Goyal; Sunil Kumar Mor; Luis M. Rodriguez-R; Muhammad Imran (Probiotics and Antimicrobial Proteins, 2025)

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Integrative metabolomic and transcriptomic analysis reveals CYP450-driven biosynthesis of pentacyclic triterpene acids in Cecropia angustifolia - Juan E. Vivas-Moncayo; Paula C. Muñoz-Bonilla; Laura M. Rodriguez-Santa; Adrián C. Rodriguez-Ararat; Guillermo Montoya (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)
Pentacyclic triterpene acids (PTAs) are specialized plant metabolites known for their anti-inflammatory and antidiabetic preclinical reports. Cecropia angustifolia , a prominent species in the Andean montane forests, produces a variety of PTAs in its roots, but little is known about enzymes responsible for their oxidative structural decorations. In this study, we explored the biosynthetic route of PTAs oxidation by cytochrome P450 (P450s) enzymes, comparing wild-collected and in-vitro cultivated root tissues. Chemical profiling was carried out using targeted metabolomics to assess PTAs in both types of extracts. Oxidation patterns differed between the samples, suggesting distinct enzyme activity depending on growth conditions. To support these findings, we assembled a de novo transcriptome based on publicly available Cecropia RNA-seq data and predicted over 26,000 open reading frames. Four P450 families (CYP716A, CYP716C, CYP72A, and CYP71D) are potential contributors to triterpene oxidation, which were identified by homology-based annotation. Gene expression was examined by RT-qPCR, revealing differential transcriptional activity between wild and in-vitro roots. Nevertheless, these differences link the gene expression profile of P450s involved in this pathway to the TPAs metabolic expression. Notably, despite changes in expression, the capacity to generate oxidized PTAs was retained under both conditions. Our results indicate that the oxidative metabolism of triterpenes in C. angustifolia is largely conserved and responsive to environmental cues. This study enhances the current understanding of PTA biosynthesis and supports the use of in-vitro systems as a practical strategy to obtain valuable metabolites while minimizing ecological impact.

Cause-effect relationship between volcanism and travertine-tufa deposition: the case study of Barranco de Azuaje, Gran Canaria, revisited - F. J. Perez-Torrado; M. C. Cabrera; A. Rodriguez-Gonzalez; Á. Marrero-Rodríguez; C. Ravazzi; P. Vidal-Matutano; J. L. Fernandez-Turiel (Journal of Iberian Geology, 2025)

Correction to: Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

Hydrogeochemical Evaluation of an Urban Aquifer Under Stress: Rare Earth Elements Fractionation and Human Health Implications - K. M. Ochoa-Guerrero; P. F. Rodriguez-Espinosa; E. Martinez-Tavera; V. Balaram; M. P. Jonathan (Environmental Management, 2025)

Tracking Aeromonas caviae and Pseudomonas aeruginosa in a mixed-use catchment with source attribution, health hazards, and microbial mixing assessments - Adrien C. M. Pozzi; Angélique Dominguez-Lage; Baptiste Luton; Laurence Marjolet; Delphine Mouniée; Emmanuelle Bergeron; Matthieu Masson; Cécile Miège; Marina Coquery; Pauline Dusseux; Nicolas Robinet; Véronica Rodriguez-Nava; et al. (Environmental Science and Pollution Research, 2025)

Changes in gut microbiota signatures associated with the epidemiological dynamics of wild European rabbits facing haemorrhagic disease outbreaks - Carlos Rouco; Xavier Triadó-Margarit; Joana Abrantes; Ana M. Lopes; Tereza Almeida; Julio Isla; Gabriela de la Fuente; Oscar Rodriguez; Emilio O. Casamayor (Veterinary Microbiology, 2025)

Evaluation of potassium bromate as a positive control in the in vivo Fpg-modified comet assay for the detection of oxidised bases - E. Saenz-Martinez; M. Collia; A. Rodriguez-Garraus; A.G. Gil; A. Lopez de Cerain; A. Azqueta (Food and Chemical Toxicology, 2025)

A comprehensive analysis of the nitrogen synchrony between cover crops release and maize uptake - Walter D. Carciochi; Francisco Cafaro La Menza; Denis G. Terwissen Gjerloff; Nahuel I. Reussi Calvo; Guillermo A. Divito; Oscar R. Avila Manotoa; María P. Rodriguez; Sergio Tovar Hernández; Adrian M. Lapaz Olveira; Hernán R. Sainz Rozas; Pablo A. Barbieri (Plant and Soil, 2025)

Discovery of Latissimia ningalooensis: a new invasive soft coral species in Puerto Rico - Daniel A. Toledo-Rodriguez; Catherine S. McFadden; Nilda M. Jimenez Marrero; J. David Muñoz-Maravilla; Alex J. Veglia; Ernesto Weil; Nikolaos V. Schizas (Biological Invasions, 2025)

The key mechanisms associated with the survival of Gulf toadfish, Opsanus beta , when in severe hypoxia - Anastasiya Plotnikova; Isabelle R. Nelson; Shara Y. Sookhoo; Jacob M. Belkin; Vanessa P. Lima; Ross D. Bronfman Bunch; Athena M. Santomero; Sophia A. Santomero; Emily C. Rodriguez; Jayda K. Rodriguez; Kathleen M. Davis; Amanda J. Kaplan; et al. (Journal of Fish Biology, 2025)
Florida's shallow seagrass beds experience daily diurnal fluctuations in environmental oxygen, leading to hypoxic episodes (PO 2 −1 , ~6 kPa) that have increased in frequency and intensity in recent decades. The native Gulf toadfish ( Opsanus beta ) have been shown to employ a suite of adaptive cardiovascular, ventilatory and metabolic adjustments to survive moderate hypoxia, but little is known of the mechanisms used to survive severe hypoxia. The objective of this study was to characterize the acute response of Gulf toadfish to severe hypoxia ( 2 ~0.4 kPa for 3 h followed by 1 h recovery). Heart rate, pulse pressure, caudal arterial blood pressure, ventilation frequency and ventilation amplitude were monitored and blood samples were taken from both groups and analysed for pH, glucose, lactate and other endpoints. Hypoxia‐exposed fish experienced a statistically significant 70% decrease in heart rate and a 32% decrease in ventilation frequency during hypoxia exposure. Moreover, plasma glucose concentrations increased 5‐fold and plasma lactate concentrations increased 6‐fold, with a minimal reduction in pH. Our findings support our hypothesis that Gulf toadfish are highly hypoxia tolerant and survive severe hypoxia by reducing energy expenditure and switching to anaerobic metabolism. It is important to understand how the Gulf toadfish deal with severe hypoxia due to the increasing prevalence of severe hypoxia in its natural environment.

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Managing fisheries and ecosystems: current good practices and the EcoScope project experience - Georgi M. Daskalov; Santiago de la Puente; Marco Scotti; Stefania Klayn; Marie Briguglio; Gianpaolo Coro; Gideon Gal; Johanna J. Heymans; Ana Rodriguez-Perez; Jeroen Gerhard Steenbeek; Georgios Sylaios; Athanassios C. Tsikliras (Frontiers in Marine Science, 2025)
Ecosystem Based Management (EBM) is a comprehensive way of managing fisheries and marine resources. As such, it needs a large and complex suite of concepts and tools to address a variety of problems ranging from climate change, through various forms of water pollution, to trophic interactions and social-economic sustainability. Industry, scientists, managers, and policy makers involved in the fisheries sector are the main actors in EBM. EBM objectives based on policy needs, legal requirements, and ecosystem considerations may target specific fish stocks, or encompass several ecosystem components aiming for balanced fisheries, but they need to address the trade-offs between maximizing economic gains versus sustainable fisheries and healthy ecosystems. Fishing at Maximum Sustainable Yield (MSY), setting ecosystem reference points, discards ban, avoiding bycatch of protected species, habitat protection, accounting for the effects of climate change, achieving good environmental status, setting effective marine protected areas, and considering ecosystem effects from marine spatial planning, are all examples of EBM objectives. The EcoScope project aimed to address ecosystem degradation, anthropogenic impacts, and unsustainable fisheries by developing an efficient, holistic, ecosystem-based approach to sustainable fisheries management that can easily be used by policy makers and advisory bodies. The EcoScope consortium reflects an interdisciplinary advisory team of biologists, modelers, economists, and social scientists. It performed comprehensive reviews of data, data gaps, and various tools (models, indicators, management evaluation procedures). An online platform, toolbox, academy, and a mobile application are end products delivered and maintained by EcoScope to facilitate knowledge sharing, communication, and education. The EcoScope project has built modules ready to be used in the implementation of EBM, but a more direct approach by the responsible organizations, such as ICES, FAO, GFCM and the EC, is needed to set explicit and formal research and managerial frameworks for implementing and coordinating the EBM activities.

Determination of flowering stage based on artificial intelligence and the daily weight of bee hives - Andrés Gersnoviez; Francisco J. Rodriguez-Lozano; María Brox; José Moreno-Carbonell; Manuel Ortiz-Lopez; José M. Flores (Computers and Electronics in Agriculture, 2025)

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Optimizing thrombospondin function through repositioning: Implications for injury and diabetic foot ulcer management - Juan Valentin Trujillo-Paez; Yolanda M. Jacobo-Delgado; Camelia Felix-Arellano; Adrian Rodriguez-Carlos; Irma Gonzalez-Curiel; Oscar Gonzalez-Muñiz; Bruno Rivas-Santiago (Tissue and Cell, 2025)

Open minds, open -slab- windows - Federico M. Dávila; Melisa Rodriguez; Juan M. Dagert; Gastón Pennacchio; Adeline Clutier; Pilar Ávila; Federico Martina; Miguel Ezpeleta; Claudia M. Herrera (Journal of South American Earth Sciences, 2025)

Biogenic nanoparticles: Synthesis, characterization, applications and scaling up limitations in water treatment - Alejandra Ortiz-Tirado; Luisa F. Medina-Ganem; Erick R. Bandala; Alain S. Conejo-Davila; Alejandro Vega-Rios; Ashantha Goonetilleke; Oscar M. Rodriguez-Narvaez (Journal of Environmental Chemical Engineering, 2025)

Disease prevalence in confiscated exotic and indiginous birds and reptiles housed in a cites-authorized rescue center in Spain - M. Jimenez Martinez; A. Martin; A. Rabanal Soto; V. Hidalgo Martinez; A. Rodriguez Luis; M. Aranda Vazquez; J. De Andres Gamazo (Journal of Comparative Pathology, 2025)

Evaluating the role of physical mechanisms as possible triggers for turbidity currents in a deep ocean seamount - Susana M. Lebreiro; Álvaro Peliz; Laura Antón; Sílvia Nave; M. Isabel Reguera; Rocío Lozano-Luz; Claire Waelbroeck; Simon Crowhurst; Belen Martrat; Jordi F. Lopez; Raphaël Hebert; Alejandra Lopez-Rodriguez (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Flexible feeding strategy for high-yield PHA bioprocessing in Cupriavidus necator H16 from anaerobically fermented industrial wastewater - Natalia Hernández-Herreros; Alberto Rodriguez; Virginia Rivero-Buceta; Antonia Rojas; M. Auxiliadora Prieto (Bioresource Technology, 2025)

Time-dependent post-mortem histomorphological changes in Penaeus vannamei following humane euthanasia - Rodolfo Lozano-Olvera; Karla G. Aguilar-Rendón; Sergio Cervantes; Selene M. Abad-Rosales; Sonia A. Soto-Rodriguez; María C. Chávez-Sánchez (Veterinary Research Communications, 2025)

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Gene dysregulation impairs placental angiogenesis in allogeneic pig pregnancies - Cristina A. Martinez-Serrano; Josep M. Cambra; Manuel Alvarez-Rodriguez; Inmaculada Parrilla; Cristina Cuello; Maria A. Gil; Emilio A. Martinez; Heriberto Rodriguez-Martinez (Animal Reproduction Science, 2025)

Multi-wavelength internal standardization using inductively coupled plasma optical emission spectrometry - Reagan Elia; Thomas J. Johnston; Alberto D. Figueroa; Emily M. Curbow; Mayra S. Gonzalez Guzman; Leah C. Rodriguez Cabrera; Marisa M. Morcom; Willis B. Jones (Analytica Chimica Acta, 2025)

Nutritional Ecology of Lactation in Franciscana Dolphins ( Pontoporia blainvillei ) From Argentina - Pablo Denuncio; M. Candela Macagno; Antonella D. Padula; M. Agustina Mandiola; Juan P. Loureiro; María Julieta Olocco Diz; M. Fernanda Zapata; Diego Rodriguez; Gabriel E. Machovsky‐Capuska (Marine Mammal Science, 2025)
Milk production strategies, duration, and composition vary among mammals. Odontocete cetaceans exhibit a long lactation strategy characterized by high parental investment and prolonged nutritional dependence. Understanding the nutritional demands of these offspring during lactation is complex, particularly due to their aquatic lifestyle. This study examines the nutritional dynamics of endangered Franciscana dolphins ( Pontoporia blainvillei ) during their first year of life. Our findings indicate that Franciscana milk is energy‐rich, with proteins and lipids as primary energy sources, varying in proportion throughout lactation. Summer milk has a higher protein‐to‐lipid ratio and lower energy density, while winter milk is more energy‐dense, with a greater lipid proportion and increased variability in composition. Calves over 80 cm consume a combination of low protein‐to‐lipid ratio milk with high protein‐to‐lipid ratio prey. Artificial milk formulas used in rehabilitation closely resemble the macronutrient composition of wild milk. This study provides valuable insights into the critical life stage of this vulnerable species and contributes to developing nutritional protocols for rehabilitating live‐stranded individuals.

Effect of hCG administration on corpus luteum development and plasma progesterone concentration in llamas - M. Florencia Gallelli; Carolina Bianchi; Enzo Zampini; Marcelo Aba; Marcelo Rodriguez; Debora Neild; M. Ignacia Carretero; Marcelo Miragaya (Theriogenology, 2025)

A practical guide on environmental genomics for prokaryotic systematics - Nathan M. Ernster; Luis M. Rodriguez-R (Systematic and Applied Microbiology, 2025)

Understanding urban tree heat and drought stress by tracking growth and recovery following an extreme year - Renée M. Marchin; Manuel Esperon-Rodriguez; Mark G. Tjoelker; David S. Ellsworth (Landscape and Urban Planning, 2025)

Assessment of the polyphenol recovery from white wine lees via non-ionic polymeric resins - Martina Gaglianò; Antonio D. Rodriguez-Lopez; Carmela Conidi; Alfredo Cassano; Giuseppina De Luca; Esperanza M. Garcia-Castello (Journal of Food Engineering, 2025)

Optimizing forest planning: Balancing timber production and carbon sequestration through a multi-objective disjunctive formulation - Frank Piedra-Jimenez; Diego Broz; Juan M. Novas; Ignacio E. Grossmann; Maria Analia Rodriguez (Forest Policy and Economics, 2025)

Adventively established Leptopilina japonica: a new opportunity for augmentative biocontrol of Drosophila suzukii - Marco Valerio Rossi-Stacconi; Paul K. Abram; Gianfranco Anfora; Elizabeth Beers; Antonio Biondi; Nicolas Borowiec; Juli Carrillo; Jana Collatz; Asia Colmagro; Benjamin Crossman Johnson; Kent Daane; Giovanni Dal Zotto; et al. (Journal of Pest Science, 2025)
The invasive spotted-wing drosophila, Drosophila suzukii , has emerged as a significant global pest over the past decade, threatening fruit production worldwide. The parasitoid Leptopilina japonica , presumed native to East Asia, has established adventive populations in Europe and North America and is increasingly recognized for its ability to parasitize substantial proportions of D. suzukii larvae across diverse habitats. Here, we provide a broad review of the biology, establishment, distribution, and potential impacts of L. japonica . Using field data from international monitoring programs, we document the seasonal dynamics of plant–host–parasitoid associations and assess evidence for L. japonica ’s impact on D. suzukii and non-target organisms. Findings indicate that L. japonica has successfully established in several areas where D. suzukii is present in Europe and North America, showing promise as a biological control agent to support sustainable pest management. Current data suggest it provides some suppression of D. suzukii populations with minimal non-target effects. However, long-term studies are necessary to clarify its food web interactions and efficacy as a biological control agent. In areas where L. japonica has been established, we propose its use in augmentative biological control programs to enhance its impacts in specific agricultural settings. Case-specific evaluations of its ecological effects and role in integrated pest management, supported by continued monitoring, are essential. The case of L. japonica illustrates the need for clear, research-informed policies to guide the use of adventively established non-indigenous natural enemies in pest management.

Phylogenetic, phenotypic, and symbiotic characterization of Bradyrhizobium isolated from nodules of cowpea grown on the Peruvian desert coast - Renzo A. Valdez-Nuñez; Sayumi M. Melendre-Rodriguez; Anderson R. Calixto-Garcia; Celia C. Silvera-Pablo; Antonio Castellano-Hinojosa; Ernesto Ormeño-Orrillo; Mariangela Hungria (Symbiosis, 2025)

Soil functions are shaped by aridity through soil properties and the microbial community structure - Anna Doménech-Pascual; Luciana Chavez Rodriguez; Xingguo Han; Joan Pere Casas-Ruiz; Joan Ferriol-Ciurana; Jonathan Donhauser; Karen Jordaan; Steven D. Allison; Aline Frossard; Anders Priemé; Jean-Baptiste Ramond; Anna M. Romaní (Applied Soil Ecology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Host‐Microbiome Associations in Livebearing Fishes Adapted to Toxic Environments Rich in Hydrogen Sulfide - Elizabeth J. Wilson; Sonny T. M. Lee; Lydia H. Zeglin; Lenin Arias Rodriguez; Michael Tobler (Molecular Ecology, 2025)
Organisms inhabiting extreme environments must tolerate a variety of physiochemical stressors. In some cases, host‐associated microbial communities facilitate the survival of their hosts in extreme environments, but extremophile symbioses have not been identified in vertebrates. We used 16S rRNA amplicon sequencing to investigate commonalities and differences in the gut bacterial communities of livebearing fishes ( Poecilia mexicana species complex, Poeciliidae) that have repeatedly colonised toxic sulfide streams in southern Mexico. We found shared gut microbial taxa across habitat types and drainages but also differences in the microbiomes between sulfidic and nonsulfidic populations, both in terms of patterns of diversity and community composition. Most importantly, we documented convergent changes in microbiome composition across evolutionarily independent sulfide spring lineages. These patterns were consistent when we analysed the gut microbiomes as well as primarily host‐associated microbiomes that excluded taxa that are commonly found in the environment. Our analyses also revealed several microbial taxa associated with sulfide spring coloniation that have previously been implicated in symbioses and may influence the host's tolerance to the extreme environmental conditions. Our study sheds light on how shared environmental pressures can give rise to convergent host‐microbiome associations in fishes, and it provides a foundation for investigating the role of host‐microbiome interactions in vertebrate adaptation to extreme environments.

Seasonal variation of trifluoroacetic acid (TFA) in Antarctic ice cores analysed by direct injection non-suppressed ion chromatography-mass spectrometry (nsIC-MS) - Estrella Sanz Rodriguez; Mingxia Lai; Harrison Stevens; Meredith K. Nation; Christopher T. Plummer; Lenneke M. Jong; Jason L. Roberts; Andrew D. Moy; Andrew R. Bowie; Mark A. Curran; Brett Paull (Science of The Total Environment, 2025)

Reconstructing the Holocene volcanic past of El Hierro, Canary Islands - C. Prieto-Torrell; J.L. Fernandez-Turiel; A. Rodriguez-Gonzalez; M. Aulinas; E. Beamud; M.C. Cabrera; C. Criado; H. Guillou; P. Vidal-Matutano; F.J. Perez-Torrado (Quaternary Geochronology, 2025)

Tree survival and growth in the highlands of central Argentina: Impact of wildfires and land management - Daniel Renison; Iván Barberá; Ana M. Cingolani; Juan Manuel Rodriguez; Isabell Hensen (Forest Ecology and Management, 2025)

Intact glycoconjugates from Taenia crassiceps excreted/secreted products ameliorate chemically induced colitis by modulating inflammation and strengthening adherens junctions - Yadira Ledesma-Soto; Ilse Chávez-Soto; Marissa Calderón-Torres; Andrea Monserrat Rodríguez-Lozoya; Jonadab E. Olguin; Luis B. Hernández-Portilla; César M. Flores-Ortíz; Fernando Candanedo; Miriam Rodriguez-Sosa; Sonia E. Hernández-Navia; Luis I. Terrazas (Inflammopharmacology, 2025)
Background Ulcerative colitis (UC) is a chronic inflammatory disease that is increasing in prevalence worldwide. Notably, helminth infections, known for their immunoregulatory properties, are inversely related to inflammatory conditions such as UC. Research has indicated that Taenia crassiceps infection can improve inflammatory-mediated diseases, including type 1 diabetes, experimental autoimmune encephalomyelitis, and colitis. Subsequent studies revealed that helminth-derived products can replicate the effects of complete infection in the context of inflammatory diseases; however, the mechanisms underlying these effects remain unclear. This study examined the impact of intact glycans from T. crassiceps excreted/secreted products (TcES) on host responses to dextran sodium sulfate (DSS)-induced colitis. Methods UC was induced by administering 4% DSS in the drinking water for 9 days. The mice were treated with intact TcES, glycan-depleted TcES, or protein-depleted TcES 2 days after colitis induction. Symptoms of the disease, along with immunologic and histopathological evaluations, were performed. Results Colitic mice that received intact TcES presented fewer disease symptoms and less histopathological damage. Intact TcES reduced the proinflammatory response while increasing the production of IL-4, IL-22, IL-31, and MCP-1 and promoting M2 macrophage polarization via PD-L2 expression. Furthermore, intact TcES diminished neutrophil infiltration, inhibited NF-κB and p38 phosphorylation in the colon, and suppressed reactive oxygen species and 3-nitrotyrosine levels, thus protecting the colon. These effects were accompanied by increased expression of E-cadherin and β-catenin, indicating improved epithelial barrier integrity. Conversely, mice treated with glycan-depleted or protein-depleted TcES exhibited exacerbated colitis characterized by disruption of colon tissue architecture, extensive inflammation, and epithelial damage, including loss of E-cadherin and β-catenin and a lack of M2 macrophage polarization. Conclusions Glycoconjugates on TcES play a significant role in mediating the immunomodulatory effects that alleviate DSS-induced colitis.

Chloroplast-based molecular markers for discrimination of economically important Vaccinium species - Maura Flynn Gallagher; Felix E. Enciso-Rodriguez; Edson Mario de Andrade Silva; Annette M. Fahrenkrog; Juan Zalapa; Juliana Benevenuto; Karina Lima Reis Borges; Patricio Munoz (Genetic Resources and Crop Evolution, 2025)

Shadows over Caribbean reefs: occurrence of a new invasive soft coral species, Xenia umbellata, in southwest Puerto Rico - Daniel A. Toledo-Rodriguez; Alex J. Veglia; Nilda M. Jimenez Marrero; Joyce M. Gomez-Samot; Catherine S. McFadden; Ernesto Weil; Nikolaos V. Schizas (Coral Reefs, 2025)

Paragonimiasis in Southeast Asia: A 60-Year Bibliometric Analysis (1963–2023) - Harley M. Rodriguez; Jose Ma. M. Angeles (Acta Parasitologica, 2025)

Leveraging Remote Sensing and Theory to Predict Tree Size Abundance Distributions Across Space - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; J. Marcos Rodriguez; Ben Weinstein; David A. Orwig; Sydne Record (Global Ecology and Biogeography, 2025)
Background Remote sensing (RS) technologies provide unprecedented opportunities to assess forest structure at broad spatial scales. Light detection and ranging (LiDAR) is a powerful tool that offers detailed vertical information, but its consistent high‐resolution coverage can be limited across vast areas and quantifying understory vegetation remains challenging due to occlusion. Conversely, while high‐resolution RGB imagery is more accessible and valuable for large‐scale analyses, it comes with higher uncertainty and only captures canopy‐level information. Integrating RGB data with ecological theory and existing LiDAR‐derived products (e.g., canopy height models, CHM) allows us to enhance predictions and broaden the applicability of forest size structure mapping from the understory to the canopy, particularly through tree size–abundance relationships. Theory Tree size and abundance generally follow known distributions, where smaller trees are exponentially more common than larger trees. This pattern emerges from fundamental ecological constraints, including volume packing, metabolic scaling and light competition, which collectively govern forest self‐organisation across spatial scales. Proposed Approach We present a workflow that integrates size‐abundance scaling theory with RGB data and CHMs to improve predictions of forest structure. By estimating tree size distributions from RGB imagery, we extend the applicability of ecological scaling models to broader spatial scales and offer an approach that complements traditional methods. Assessment We apply this approach to forest monitoring networks, including NEON and ForestGEO, to assess its accuracy and generalisability across a range of forests (e.g., subtropical pine, boreal, low and dry, tall and dense) in North America. Our results show that RGB‐based estimates can successfully recover size‐abundance distributions from the understory to the canopy. Future Directions Further refinement of our approach could enhance predictions by incorporating species classifications from hyperspectral data and using more spatially or taxonomically specific allometric equations. These additions would enable more precise scaling of tree diameter from remote sensing data.

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

Observations of Sargassum carbon influx and biogeochemical impact in La Parguera Marine Reserve - Priscilla N. Molina-Cora; Julio M. Morell; Loraine Martell-Bonet; Luis R. Rodriguez-Matos; Julián E. Morell; Maribel Vélez-Rivera (Frontiers in Marine Science, 2025)
The massive influx of pelagic Sargassum spp. species, also known as Sargassum inundation events (SIEs), first arrived at the Caribbean’s coastal waters in 2011. These events have been linked to hypoxia, among other ecological disturbances. Here, we report data from 2022 on (1) an assessment of the relative magnitude of particulate organic carbon (POC) load arising from SIEs into the La Parguera Marine Reserve (LPMR) basin off the southwest coast of Puerto Rico and (2) the biogeochemical impact of SIE in a nearshore mangrove key within the reserve, Monsio Jose Key Bay (MJKB). Our analysis yields that the carbon influx increased by 20% in the LPMR basin and by 103% in MJKB. Weekly observations of Sargassum input, along with the collection and analysis of water samples in MJKB, evidenced a cause-effect relation between Sargassum carbon loading and frequency of hypoxic (DO < 2 mg·L -1 ) and critically acidic conditions (Aragonite saturation, Ω < 2.0). During the 2022 Sargassum season, hypoxic conditions were detected in 43% of samples collected in MJKB. Considering the modulation of biogeochemical parameters by changes in tide height (Δh) and wind speed (m·s -1 ), stepwise multiple regression analyses (RDA-AIC model selection) showed that significant parameters influencing DO, pH, and Ω include the Sargassum carbon influx and Δh ( p < 0.05). These findings strongly support the hypothesis that the additional input of POC influx enhances microbial mineralization rates responsible for depressed oxygen concentrations and acidic conditions, which could be detrimental to coastal ecosystems. This is particularly concerning in areas prone to SIEs where geomorphological features facilitate the entrainment of floating materials. Proper management requires the identification of vulnerable sites and Sargassum removal. Ongoing efforts towards that goal are underway for LPMR.

Correction: Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Mitochondrial bioenergetics analysis on SLC-selected boar spermatozoa during liquid storage - Estibaliz Lacalle; Beatrice Mislei; Cristina Algieri; Marcella Spinaci; Felipe Martinez Pastor; Salvatore Nesci; Jane M. Morrell; Jose M. Ortiz-Rodriguez; Diego Bucci (Animal Reproduction Science, 2025)

Exploring Nutritional Condition of Merluccius hubbsi During Early Life Stages: Environmental Drivers and Possible Implications on Subsequent Recruitment - Julieta Rodriguez; Nadia M. Alves; Harold Fenco Chavesta; Gustavo J. Macchi; Agustin Schiariti; Rosana Di Mauro; Marina V. Diaz (Fisheries Oceanography, 2025)
The early life stages of fish represent a period of high energy requirements due to profound changes that characterize the passage to adulthood, crucial for fisheries recruitment. This study focuses on the North Patagonian Frontal System (NPFS) that guarantees successful larval development and fulfills the three postulates of Bakun's “fundamental triad” in regards to nutrients, concentration of food, and retention of eggs and larvae inside the favorable area. The objective was to evaluate the nutritional condition of Merluccius hubbsi larvae and juveniles, from the Patagonian stock in January during austral summer (2010–2021). The standardized RNA/DNA index (RDs) was used. Interannual variation in the larval condition was observed in relation to NPFS features. RDs were positively linked to the stratification of the water column in the stratified zone. An opposite trend was observed between larval condition and potential egg production that might indicate the existence of density‐dependent mechanisms. On the other hand, the positive relation between larval condition and egg production of older females (≥7 years) supports the idea of a maternal effect on larval survival. There was also a positive relationship between juveniles condition, body size, and recruitment, but no relationship was observed with the stratification of the water column. The high sensitivity of the RDs index links physiological state with survival probability, informing on factors affecting eggs, larvae, and juveniles until their posterior recruitment. This study identified the stratified area of the NPFS as a favorable nursery zone, providing crucial information for managing populations under high fishing pressure.

Lignin hydrotreatment to aromatics products on metallic phosphides carbon-based catalysts produced from lignin - M. García-Rollán; S. Bertran-Llorens; M.A. Palazzolo; P.J. Deuss; H.J. Heeres; R. Ruiz-Rosas; J.M. Rosas; J. Rodriguez-Mirasol; T. Cordero (Fuel, 2025)

Synergies Between Agricultural Production and Shorebird Conservation With Climate Change in the Central Valley, California, With Optimized Water Allocation and Multi‐Benefit Land Use - Liying Li; Spencer Cole; José M. Rodriguez‐Flores; Erin Hestir; Daniel Fink; Joshua H. Viers; Josue Medellin‐Azuara; Martha Conklin; Thomas Harmon (Global Change Biology, 2025)
Conservation planning that enhances the resiliency of biodiversity to climate change requires adaptive water and land use decision‐making in the most cost‐efficient way. This has many challenges since landscapes with high biodiversity can embrace intense human production activities, particularly agriculture. Conventionally, water and land used for conservation are often regarded as tradeoffs to agricultural productivity. However, this study found that agricultural water and land use synergize with shorebird conservation in the Central Valley, California. If informed decisions are made to guide strategic land use, landscapes can adapt to climate change and offer multiple benefits. This study used a coupled economic optimization model with a species distribution model to consider human factors in ecological impacts. The objective was to assess the impacts of agricultural water and land use decisions under different climate change scenarios on 10 shorebird species populations in California's Central Valley. Our results showed that strategic water and land management can offer favorable habitats to targeted shorebirds with a land composition including diversified crop categories complementary to wetlands. This study demonstrates that agricultural lands can be as important as wetlands to shorebirds to sustain their migratory stages throughout the year. Wetland restoration without species habitat preference information can lead to population shrinkage since wetland types vary in habitat importance to the shorebird species studied in this research. Business as usual, along with land use and climate change, will decrease shorebirds' breeding season and population to the same degree as they impact non‐breeding populations. The synergies between agricultural production and shorebird conservation were found in the scenarios that favor agricultural production water use but also favor habitat provisioning to shorebirds in the Central Valley, California, under climate change.

Deciphering immune tolerance in allogeneic pig pregnancy - Josep M. Cambra; Cristina A. Martinez-Serrano; Heriberto Rodriguez-Martinez; Juan M. Vazquez; Cristina Cuello; Maria A. Gil; Emilio A. Martinez; Inmaculada Parrilla (Theriogenology, 2025)

Extreme marine heatwave linked to mass fish kill in the Red Sea - Matthew D. Tietbohl; Lily G.C. Genevier; Erik C. Krieger; Alexander Kattan; Yixin Wang; Elamurugu Alias Gokul; Lucia M. Rodriguez Bravo; Lea Palm; Gage Mele; Ibrahim Hoteit; Maggie D. Johnson (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Evaluating Airborne Hyperspectral Scanner (AHS) for the mapping of soil organic matter and clay in a Mediterranean forest ecosystem - Francisco M. Canero; Victor Rodriguez-Galiano; Sabine Chabrillat (CATENA, 2025)

Nutritional ketosis modulates the methylation of cancer-related genes in patients with obesity and in breast cancer cells - Paula M Lorenzo; Andrea G Izquierdo; Gemma Rodriguez-Carnero; Nicolas Costa-Fraga; Angel Díaz-Lagares; Cristina Porca; Daniel de Luis; Cristina Tejera; Laura De Paz; Juan Cueva; Diego Bellido; Ana B Crujeiras (Journal of Physiology and Biochemistry, 2025)
Scientific evidence demonstrates that a very low-calorie ketogenic diet (VLCKD) is effective and beneficial in the treatment of obesity, capable of reversing the methylome associated with obesity and has immunomodulatory capacity. This effect is in part promoted by nutritional ketosis and could be involved in counteracting obesity-related cancer. The aim of this study was to evaluate the effect of nutritional ketosis on the methylation of genes related to tumor processes in patients with obesity and in breast cancer cells. Based on methylome data (Infinium MethylationEPIC BeadChip, Illumina) from patients with obesity treated with a VLCKD for weight loss ( n = 10; n = 5 women, age = 48.8 ± 9.20 years, BMI = 32.9 ± 1.4 kg/m2), genes belonging to cancer-related pathways were specifically evaluated and further validated in vitro in MDA-MB-231 (triple negative) and MCF7 (RE positive) breast tumor cells pretreated for 72 h with βOHB, the main ketone body, secretome from visceral (VATs) or subcutaneous (SATs) adipose tissue of patients with obesity. The cell tumoral phenotype was evaluated by proliferation assay and expression of cancer-related genes. VLCKD-induced nutritional ketosis promoted changes in the methylation of 18 genes (20 CpGs; 17 hypomethylated, 3 hypermethylated) belonged to cancer-related pathways with MAPK10, CCN1, CTNNA2, LAMC3 and GLI2 being the most representative genes. A similar pattern was observed in the MDA-MB-231 cells treated with β-OHB, without changes in MCF7. These epigenetic changes paralleled the tumoral phenotype modulated by the treatments. Taking together these results highlight the potential role of VLCKD as an adjuvant to anticancer treatment in groups more susceptible to the development of cancer such as patients with obesity, exerting epigenetic regulation through nutritional ketosis and weight loss.

Benefits and trade-offs from the diversification of rangeland farms in Northern Queensland, Australia - Lipy Adhikari; Peter de Voil; M. Fernanda Dreccer; Daniel Rodriguez (Agricultural Systems, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Earth's most needed uncultivated aquatic prokaryotes - Sophie A. Simon; Vera Aschmann; Annika Behrendt; Michael Hügler; Lisa M. Engl; Marion Pohlner; Sönke Rolfes; Thorsten Brinkhoff; Bert Engelen; Martin Könneke; Luis M. Rodriguez-R; Till L.V. Bornemann; et al. (Water Research, 2025)

Climate-growth relationships and paleoclimate potential of Austrocedrus chilensis revisited by extending its tree-ring network in Argentina - Eugenia Marcotti; Ricardo Villalba; Milagros Rodriguez-Caton; Ana M. Srur; José A. Boninsegna; Mariano M. Amoroso (Dendrochronologia, 2025)

Biocontrol and plant growth-promoting activities of airborne bacteria - Beatriz G. Guardado-Fierros; Miguel A. Lorenzo-Santiago; Manuel R. Kirchmayr; Olga A. Patrón-Soberano; Jacobo Rodriguez-Campos; Silvia M. Contreras-Ramos (World Journal of Microbiology and Biotechnology, 2025)

Safety Outcomes of Antiplatelet Therapy During Endovascular Treatment of Tandem Lesions in Acute Ischemic Stroke Patients - Mudassir Farooqui; Afshin A. Divani; Milagros Galecio-Castillo; Ameer E. Hassan; Mouhammad A. Jumaa; Marc Ribo; Michael Abraham; Nils Petersen; Johanna Fifi; Waldo R. Guerrero; Amer M. Malik; James E. Siegler; et al. (Translational Stroke Research, 2025)

Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

INIA 333 – CHUGAYNA new Potato Variety Resilient to Climate Change for the Family Farming System with Tolerance to Frost, Resistant to Late Blight and high Quality for Fresh Consumption - Héctor Cabrera; Ronal Otiniano; Rosemeri Pando; Henry Sánchez Garcia; Willian Huamanchay Rodriguez; Juan M. Pérez; Stef de Haan; Manuel Gastelo (American Journal of Potato Research, 2025)
The new potato variety INIA 333–CHUGAYNA, is the result of the joint work of the NGO Asociación Pataz, INIA and the International Potato Center, it was generated through traditional breeding and the use of the participatory varietal selection methodology, as a variety resilient to climate change with frost tolerance, resistance to late blight, compared to the improved variety INIA 302-Amarilis and the native varieties, Huevo de Indio. This new variety is also resilient to climate change, tolerant to frost, with field resistance to late blight, high tuber yield, low glycoalkaloid content and high quality for fresh consumption, adapted up to 4000 m above sea level. It was released in 2023 and officially registered in the national registry of commercial varieties of Peru. The new variety INIA 333-CHUGAYNA requires minimal use of fungicides and has a high economic profitability that will improve the living standards of small and medium-sized farmers in Peru. It can also be used as a parent in breeding programs in other countries in development, to confront climate change, especially frost.

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

Feed intake, preferences, in vivo digestibility, and nutritional value of tedera (B. bituminosa var. bituminosa) and maralfalfa (Pennisetum purpureum) in Canary sheep - M. Barbera; V. Mendoza-Grimón; J. Espinosa; E. Rodriguez-Ponce; A. Gracia; E. SanJuán; M. R. Ventura (Tropical Animal Health and Production, 2025)
This study evaluated the nutritional value and energy content of tedera ( B. bituminosa var. bituminosa ) and maralfalfa ( Pennisetum purpureum ) through analyses of chemical composition, digestibility, intake, and preference trials. Tedera was compared with maralfalfa and alfalfa hay ( Medicago sativa ). Tedera showed higher crude protein (193 g CP/kg DM) and estimated energy (10.5 MJ DE/kg DM) but lower dry matter (286.3 g DM/kg) and neutral detergent fiber (373 g NDF/kg DM) than both maralfalfa and alfalfa hay. The in vitro organic matter digestibility (IVOMD) of tedera was 61.7%, compared to 51.0% for alfalfa hay and 66.3% for maralfalfa. Digestible organic matter (DOM) ranged from 467 g/kg DM in alfalfa hay to 566.4 g/kg DM in tedera. Four Canary sheep with a mean body weight (BW) of 42.2 ± 5.0 kg were used for digestibility and preference trials. The live weights of the sheep were recorded at the start and end of the 12-day trial. Feed offered and refusals were weighed and recorded daily for eight days, while feces were collected for four days to calculate apparent in vivo digestibility. For tedera, the apparent in vivo OM digestibility, estimated digestible energy, and digestible organic matter were 69.4%, 11.8 MJ/kg DM, and 637.7 g/kg DM, respectively. Preference and feed intake were compared between tedera, maralfalfa and alfalfa hay. Total DM consumption was 1091.3 g/day (tedera + maralfalfa + alfalfa hay), with alfalfa hay intake representing 40.8%, maralfalfa 37.3%, and tedera 21.9% of the total DM consumed. However, no significant differences were observed in the ratio of forages consumed/offered (44.8% for tedera and 51.8% for maralfalfa) or in the total grams of DM, CP, and MJ/kg of DE consumed by the sheep with both forages. The sheep adopted different feeding strategies in response to the chemical composition and nutritive value of the forages. Preferences and intake in this trial were associated with high NDF content in maralfalfa and alfalfa hay and with the high CP content in tedera rather than digestibility results. This may be due to the complementarity of the three forages and the higher CP content in tedera affecting intake. Nevertheless, tedera and marafalfa could be a good forage considering its nutritive value, digestibility, and proven growth performance in herbivores.

Perceptions and Attitudes of Drinking Water Supply Systems Staff Towards Climate Change Adaptation for Drinking Water Quality Management - S. M. Cynthia Compaoré; Ianis Delpla; Sonja Behmel; Manuel J. Rodriguez (Environmental Processes, 2025)

18S rRNA Metagenomic Analysis of Nodular Gill Disease in Swiss Rainbow Trout ( Oncorhynchus mykiss ) - James W. Wynne; Chloe J. English; Stefania M. Vannetti; Megan Rigby; Petra R. Quezada‐Rodriguez; Ralph Knüsel; Christine Huynh; Heike Schmidt‐Posthaus (Journal of Fish Diseases, 2025)
Nodular gill disease (NGD) is a serious proliferative gill condition that affects farmed salmonids, particularly in Europe. While the cause of NGD remains unknown (and maybe multifactorial), various amoebae are often isolated from the gills of affected fish and can in some cases be seen associated with lesions by histopathology. The present study aimed to quantify the abundance of different amoeba species directly from the gills of rainbow trout affected by NGD and healthy controls. An 18S rRNA amplicon metagenomic approach was employed to profile the diversity and abundance of micro‐eukaryotes (including amoebae) while suppressing the amplification of host DNA using a salmonid‐specific C3 spacer blocking primer. The 18S rRNA metagenomics approach identified a diversity of micro‐eukaryotes on the gills of rainbow trout, including the phylum's Amoebozoa , Diatomea , Platyhelminthes and Ciliophora . Rainbow trout clinically affected by NGD had a significantly higher abundance of a specific sequence (zOTU2) classified as Vannella sp. compared to healthy controls. A quantitative PCR assay was then developed and validated which accurately quantified the abundance of this Vannella sp. sequence from a NGD outbreak in a Swiss rainbow trout farm. Additional PCR and Sanger sequencing analysis of the zOTU2 sequence demonstrated that this sequence is most likely derived from Vannella mustalahtiana . Our study highlights the potential role of Vannella mustalahtiana in NGD in Switzerland and further describes a specific and validated diagnostic PCR assay for accurate detection of this Vannella species.

Exploring the potential of hydrolytic enzymes combined with antibacterial agents to disrupt pathogenic biofilms and disinfect released cells - Patricia Palafox-Rivera; Melvin R. Tapia-Rodriguez; Julio Cesar Lopez-Romero; Marco A. Lugo-Flores; Karen P. Quintero-Cabello; Brenda A. Silva-Espinoza; M. Reynaldo Cruz-Valenzuela; Filomena Nazzaro; J. Fernando Ayala-Zavala (Biofouling, 2025)

Optimizing activated carbon production from chontaduro seeds via physical activation with steam for ibuprofen removal: A factorial design and multi-attribute utility theory approach - L. Angel; A. Villot; M. Rodriguez Susa; J. Plazas-Tuttle; Y. Andres; C. Gerente (Journal of Water Process Engineering, 2025)

Evaluation of intra- and inter-rater agreement on ultrasound measurements of dairy cow teats by operators with different experience levels - I. Nocera; G. Sala; C. Orsetti; J. M. Rodriguez-Lopez; M. Sgorbini; F. Bonelli (Veterinary Research Communications, 2025)

Understanding Environmental Factors Influencing Vegetation Cover Downstream of Dams - Raid Almalki; Mehdi Khaki; Patricia M. Saco; Jose F. Rodriguez (International Journal of Environmental Research, 2025)

Bridges monitoring and assessment using an integrated bim methodology - D. Rodriguez Polania; F. Tondolo; A. Osello; M. Piras; V. Di Pietra; N. Grasso (Innovative Infrastructure Solutions, 2025)
Risk assessment of long-existing infrastructure has become one of the main challenges in civil engineering. Major efforts have been made in recent years to develop new techniques for rapid damage identification and ensure proper management of these structures. This paper presents a data management approach utilizing BIM methodology to create a digital database for bridge monitoring procedures. Initially, two BIM methodologies for creating a damage database are introduced, focusing on beams from a dismantled urban viaduct. Subsequently, the most suitable methodology is applied to an existing bridge in Turin, Italy. Through the chosen methodology a damage identification and classification process based on a triangular mesh is performed, assisted by a convolutional neural network (CNN) for automatic damage detection. Additionally, the paper outlines a digitalization process within a BIM environment, integrating official guidelines for bridge risk evaluation, classification, and monitoring in Italy. By employing programming tools, all data required by the guidelines is efficiently incorporated into the database. The outcomes demonstrate the effectiveness of remote sensing applications for bridge inspection and the possibility of merging BIM methodology into the inspection process to enhance the damage assessment of existing structures.

A new species of Myxobolus (Cnidaria: Myxosporea: Myxobolidae) from the gills of the green sunfish, Lepomis cyanellus (Perciformes: Centrarchidae), from the Ouachita River Drainage of Western Arkansas - Chris T. McAllister; Eric M. Leis; Donald G. Cloutman; Alvin C. Camus; Irvin Arroyo-Torres; Lana Gretebeck; Michael R. Rodriguez; Henry W. Robison (Systematic Parasitology, 2025)

Annular solar eclipse effects observed over Mexico on October 14, 2023: A multi-instrument study - M.A. Sergeeva; J.A. Gonzalez-Esparza; O.A. Maltseva; J.H. Castro-Chacon; V.J. Gatica-Acevedo; A. Melgarejo-Morales; I.D. Orrala Legorreta; X. Chiappa; R. Bonifaz; M.E. González-Álvarez; A. Vesnin; P. Corona-Romero; et al. (Advances in Space Research, 2025)

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Microplastics in the digestive tract of an endangered cetacean of the Southwest Atlantic Ocean: The franciscana dolphin - Antonella D. Padula; Ana C. Ronda; Lucas S. Rodríguez Pirani; A. Lorena Picone; Rosana M. Romano; Gisela V. Giardino; Juan Pablo Seco Pon; Rodrigo Machado; Marcela Gerpe; Diego Rodriguez; Pablo Denuncio (Marine Pollution Bulletin, 2025)

Charge as a key physicochemical factor in adsorption of organic micropollutants from wastewater effluent by rice husk bio-silica - Alba Rodriguez-Otero; Selina Tisler; Lisa M. Reinhardt; Mathias B. Jørgensen; Brice Bouyssiere; Jan H. Christensen (Water Research, 2025)

Modeling MBR fouling: A critical review analysis towards establishing a framework for good modeling practices - V. Sandoval-García; M.V. Ruano; M. Alliet; C. Brepols; J. Comas; J. Harmand; M. Heran; G. Mannina; I. Rodriguez-Roda; I. Smets; A. Robles (Water Research, 2025)

Retraction status of “Glaciar Norte” of Pico de Orizaba, Mexico: Update to 2024 - Víctor Soto; Carlos M. Welsh-Rodriguez; Rafael Torres-Orozco; Francisco Cordoba-Montiel; Hugo Delgado-Granados (Journal of South American Earth Sciences, 2025)

The diurnal variation of dust and water ice aerosol optical depth at Jezero crater observed by MEDA/TIRS over a full Martian year - Michael D. Smith; Germán M. Martínez; Eduardo Sebastián; Mark T. Lemmon; Samuel A. Atwood; Daniel Toledo; Daniel Viúdez-Moreiras; Aurélien Stcherbinine; Jose Antonio Rodriguez-Manfredi; Manuel de la Torre Juárez (Icarus, 2025)

Photodegradation of acetaminophen on titania fibers prepared by electrospinning - M. García-Rollán; F.J. Garcia-Mateos; J.M. Rosas; J. Rodriguez-Mirasol; T. Cordero; C. Belver; J. Bedia (Chemical Engineering Journal, 2025)

Multiple mating enhances luteogenesis increasing corpus luteum perfusion area and progesterone production in ewes - J.P. Bottino; M.G.K. Rodriguez; M. Ratto; R. Ungerfeld (Animal Reproduction Science, 2025)

Between and within-city variations of PM2.5 oxidative potential in five cities in Colombia - Néstor Y. Rojas; Dayana M. Agudelo-Castañeda; Daniela Bustos; Krystal J. Godri Pollitt; Dong Gao; Laura A. Rodriguez-Villamizar (Air Quality, Atmosphere & Health, 2025)
Fine particulate matter (PM 2.5 ) has been shown to cause oxidative stress, which has negative health consequences. The oxidative potential (OP) of PM 2.5 , a promising health exposure metric, was assessed in five Colombian cities using the synthetic respiratory tract lining fluid assay that tracks the depletions of glutathione and ascorbate. For this, a set of 91 integrated 2-week ambient PM 2.5 samples were collected using Ultrasonic Personal Aerosol Samplers (UPAS) at background (5), traffic (37), industrial (12) and residential (37) sites. Across all site types, mean PM 2.5 mass concentration was 20.20 ± 9.36 µg m − 3 . The oxidative potential (OP AA for ascorbate and OP GSH for glutathione) varied widely across cities with an average of 2.67 ± 1.27 for AA and 2.93 ± 1.22 % depletion m − 3 for GSH. OP metrics among cities were not correlated with PM 2.5 mass concentrations. Overall, industrial sites showed higher PM 2.5 mass concentrations and OP AA . In contrast, OP GSH was not found to differ among industrial, traffic, or residential sites, but was lower for background sites. Our findings provide substantial evidence of variations in PM 2.5 OP between cities and within the cities. Further research is needed to assess the association between OP and adverse health effects, as well as to attribute the sources that cause such variations.

Capped honey segmentation in honey combs based on deep learning approach - Francisco J. Rodriguez-Lozano; Sergio R. Geninatti; José M. Flores; Francisco J. Quiles-Latorre; Manuel Ortiz-Lopez (Computers and Electronics in Agriculture, 2024)

Occurrence, characterization, and ecological risk analysis of petroleum hydrocarbons in water and sediments following large-scale field simulated oil spills at the experimental lakes area, Northwestern Ontario, Canada - Zeyu Yang; Keval Shah; Bruce Hollebone; Sonia Laforest; Madison MacGillivray; Diane Dey; Jose Luis Rodriguez; Benoit Lalonde; Chun Yang; Vanessa Beaulac; Jules M. Blais; Mark Hanson; et al. (Marine Pollution Bulletin, 2024)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Optimization of the stowage of fishing discards: Innovations in trawlers in the Gulf of Cadiz (SW Iberian Peninsula) - Daniel J. Coronil-Huertas; Carlos Rodriguez-García; Santiago Pavón-Quintana; Juan M. Vidal-Pérez; Jésica Sarmiento-Carbajal; Remedios Cabrera-Castro (Regional Studies in Marine Science, 2024)

Simultaneous degradation of cyanobacteria and cyanotoxins by catalytic wet peroxide oxidation: Impact of morphology and growth stage - David Ortiz; Alicia Martin-Montero; Cristian Rodriguez; Neus Lopez-Arago; Samuel Cirés; Andreas Ballot; Zahara M. de Pedro; Antonio Quesada; Jose A. Casas; Macarena Munoz (Journal of Environmental Chemical Engineering, 2024)

Sublethal effects of microplastic and oil co-exposure on biological rates and lipid profiles of keystone Arctic copepods - R. Almeda; R. Rodriguez-Torres; S. Rist; M. Winding; S. Jonasdottir; T. Gissel Nielsen (Environmental Pollution, 2024)

Competitive ability of three native grass species during establishment - M. C. Scarfó; D. A. Rodriguez; C. Milano; A. Loydi (Plant Ecology, 2024)

The role of traditional NSAIDs and selective COX-2 inhibitors on COVID-19 outcomes: a real-world data study - Narmeen Mallah; Irene Visos-Varela; Bahi Takkouche; Rosendo Bugarín-González; María Piñeiro-Lamas; Teresa Herdeiro; Maruxa Zapata-Cachafeiro; Almudena Rodríguez-Fernández; Angel Salgado-Barreira; Adolfo Figueiras; Eduardo Carracedo-Martínez; Rosa M. García-Álvarez; et al. (Inflammopharmacology, 2024)

Correction to: Validation of a novel western blot assay to monitor patterns and levels of alpha dystroglycan in skeletal muscle of patients with limb girdle muscular dystrophies - Thulashitha Rajasingham; Hector M. Rodriguez; Andreas Betz; Douglas M. Sproule; Uma Sinha (Journal of Muscle Research and Cell Motility, 2024)

Exploring the Nature of Arhopalus ferus (Coleoptera: Cerambycidae: Spondylidinae) Pheromone Attraction - Jessica L. Kerr; Cecilia M. Romo; Brooke O’Connor; Georgia Dickson; Max Novoselov; Samuel Aguilar-Arguello; Christine Todoroki; Adriana Najar-Rodriguez; Lee-Anne Manning; Andrew Twidle; Anne Barrington; Gaetan Leclair; et al. (Journal of Chemical Ecology, 2024)
Cerambycid species of the Spondylidinae subfamily are distributed worldwide and are known for being prolific invaders that infest conifers. In New Zealand, Arhopalus ferus (Mulsant), the burnt pine longhorn beetle, is well-established and requires monitoring at high-risk sites such as ports, airports, and sawmills as part of the requirements to meet pine log export standards set by the New Zealand Ministry of Primary Industries (MPI). Currently, its surveillance relies on traps baited with host volatiles (i.e., ethanol and α-pinene). We used volatile collections from adult beetles, electroantennograms, and field trapping bioassays to identify the pheromones emitted by the burnt pine longhorn beetle A. ferus and their effects on its behaviour. We show that A. ferus males emit mainly ( E )-fuscumol and geranylacetone, as well as the minor components, α -terpinene and p -mentha-1,3,8-triene, and that all four compounds elicit a dose-dependent response in antennae of both sexes. Traps baited with the binary combination of geranylacetone plus fuscumol captured significantly more female A. ferus than did unbaited traps in two of three field experiments. α-Terpinene did not affect A. ferus trap catches and effects of p -mentha-1,3,8-triene on trap catch were not determined. Our findings provide further evidence of the use of fuscumol and geranylacetone as aggregation-sex pheromones by longhorn beetles in the Spondylidinae subfamily, and suggest that their deployment in survey traps may improve the efficacy of A. ferus monitoring in New Zealand and elsewhere.

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Evidence of web collecting (Araneidae) by the hummingbird green-breasted mango (Anthracothorax Prevostii) - Alex M. Cubas-Rodriguez (Ornithology Research, 2024)

Electrochemical oxidation of a membrane-distillation concentrate for the treatment of real pharmaceutical wastewater - Orlando Garcia-Rodriguez; Chenyi Fang; Huan Jiang; Jinghui Deng; Joseph Imbrogno; Tim M. Swenson; Sui Zhang; Olivier Lefebvre (Chemosphere, 2024)

Options and considerations for validation of prokaryotic names under the SeqCode - Stephanus N. Venter; Luis M. Rodriguez-R; Maria Chuvochina; Marike Palmer; Philip Hugenholtz; Emma T. Steenkamp (Systematic and Applied Microbiology, 2024)

Demystifying the tropics: FTIR characterization of pantropical woods and their α-cellulose extracts for past atmospheric 14C reconstructions - June Nakachi Griffin; Guaciara M. Santos; Lucas Duy Nguyen; Daigard R.O. Rodriguez; Lucas G. Pereira; Nelson Jaén-Barrios; Gabriel Assis-Pereira; Nathan de Oliveira Barreto; Arno F.N. Brandes; Ana Carolina Barbosa; Peter Groenendijk (Science of The Total Environment, 2024)

Phthalates and fatty acid markers in free-ranging cetaceans from an insular oceanic region: Ecological niches as drivers of contamination - Annalisa Sambolino; Filipe Alves; Marta Rodriguez; Mieke Weyn; Rita Ferreira; Ana M. Correia; Massimiliano Rosso; Manfred Kaufmann; Nereida Cordeiro; Ana Dinis (Environmental Pollution, 2024)

Genotypic Variation and Potential Mechanisms of Resistance against Multiple Insect Herbivores in Cranberries - Paolo Salazar-Mendoza; Gonzalo Miyagusuku-Cruzado; M. Monica Giusti; Cesar Rodriguez-Saona (Journal of Chemical Ecology, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Exploring the restorative capacity of urban green spaces and their biodiversity through an adapted One Health approach: A scoping review - Natalia Rodriguez Castañeda; Melissa Pineda-Pinto; Natalie M. Gulsrud; Clair Cooper; Mairéad O’Donnell; Marcus Collier (Urban Forestry & Urban Greening, 2024)

Cardiac alterations induced by Heloderma horridum horridum venom in rats: An experimental study with ECG analysis using a linear regression algorithm - Karla Isabel Vazquez-Gonzalez; Alberto Ochoa-Brust; Alejandrina Rodriguez-Hernandez; Hugo Ventura-Cisneros; Gisela Jareth Lino-Lopez; Rafael Barbosa-Valdovinos; Armando Rodriguez-Vazquez; Oscar F. Vazquez-Vuelvas; Ramon A. Felix; Juana M. Jiménez-Vargas; Valery Melnikov; Laura Leticia Valdez-Velazquez (Toxicon, 2024)

Comparing levoglucosan and mannosan ratios in sediments and corresponding aerosols from recent Australian fires - Harrison Stevens; Leon A. Barmuta; Zanna Chase; Krystyna M. Saunders; Atun Zawadzki; Andrew R. Bowie; Morgane M.G. Perron; Estrella Sanz Rodriguez; Brett Paull; David P. Child; Michael A.C. Hotchkis; Bernadette C. Proemse (Science of The Total Environment, 2024)

Association of pesticide exposure with respiratory health outcomes and rhinitis in avocado farmworkers from Michoacán, Mexico - Cecilia S. Alcalá; Cynthia Armendáriz-Arnez; Ana M. Mora; Maria G. Rodriguez-Zamora; Asa Bradman; Samuel Fuhrimann; Christian Lindh; María José Rosa (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A case-cohort study of per- and polyfluoroalkyl substance concentrations and incident prostate cancer in the cancer prevention Study-II LifeLink cohort study - Alyssa N. Troeschel; Lauren R. Teras; James M. Hodge; Juan Rodriguez; Ying Wang; Johnni Daniel; W. Ryan Diver; Andrea Winquist (Environmental Research, 2024)

Integrating high-resolution remote sensing and empirical wildlife detection data for climate-resilient corridors across tropical elevational gradients - Ian M. McCullough; Christopher Beirne; Carolina Soto-Navarro; Amy Eppert; Eleanor Flatt; Yvonne J.M. Kemp; Péter K. Molnár; Michael S. Mooring; Yana Nikolova; Erik R. Olson; Carolina Pinto; Junior Porras; et al. (Biological Conservation, 2024)

The Impact of Microbial Interactions on Ecosystem Function Intensifies Under Stress - Brittni L. Bertolet; Luciana Chavez Rodriguez; José M. Murúa; Alonso Favela; Steven D. Allison (Ecology Letters, 2024)
A major challenge in ecology is to understand how different species interact to determine ecosystem function, particularly in communities with large numbers of co‐occurring species. We use a trait‐based model of microbial litter decomposition to quantify how different taxa impact ecosystem function. Furthermore, we build a novel framework that highlights the interplay between taxon traits and environmental conditions, focusing on their combined influence on community interactions and ecosystem function. Our results suggest that the ecosystem impact of a taxon is driven by its resource acquisition traits and the community functional capacity, but that physiological stress amplifies the impact of both positive and negative interactions. Furthermore, net positive impacts on ecosystem function can arise even as microbes have negative pairwise interactions with other taxa. As communities shift in response to global climate change, our findings reveal the potential to predict the biogeochemical functioning of communities from taxon traits and interactions.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

P16-01 Potential androgenic effects induced by pure cyanotoxins (microcystin-LR, cylindrospermopsin) in silico, in vitro and in vivo - A. Casas-Rodriguez; A. Cascajosa-Lira; N. Ayala-Soldado; M. Puerto; A.M. Cameán; A. Jos (Toxicology Letters, 2024)

P02-23 A high-throughput gut-on-chip platform to study the epithelial responses to enterotoxins - M. Morelli; M.C. Rodriguez; N. den Breems; K. Queiroz (Toxicology Letters, 2024)

P02-07 Using microfluidic hepatic spheroid cultures for assessing effects of T2 mycotoxin - M. Taroncher; J.-M. de Hoyos-Vega; A.-M. Gonzalez-Suarez; Y. Rodriguez-Carrasco; M.-J. Ruiz; A. Revzin (Toxicology Letters, 2024)

S13-04 Towards interoperable modelling tools for integrative risk assessment – the PARC model network approach - J. Kruisselbrink; W. de Boer; M. van Lenthe; T. van Voorthuijsen; P. Palmont; L. Rodriguez Martin; D. Devriendt; E. Govarts; M. Carsique; A. Crépet; J. van Klaveren; J. Engel (Toxicology Letters, 2024)

Vitrification of pig embryos dysregulates the microRNA transcriptome profile - Cristina Cuello; Alejandro González-Plaza; Josep M. Cambra; Manuela Garcia-Canovas; Inmaculada Parrilla; Heriberto Rodriguez-Martinez; Maria A. Gil; Emilio A. Martinez (Theriogenology, 2024)

Anti-oomycete activity and plant growth promoting properties of avocado fungal endophytes - Emma I. Nieves-Campos; Alejandro Méndez-Bravo; Yareli Pérez-Bautista; Jesús Llanderal-Mendoza; Edgar Guevara-Avendaño; Itzel A. Solís-García; Nayeli A. Diyarza-Sandoval; Silvia M. Contreras-Ramos; Jacobo Rodriguez-Campos; Alfonso Méndez-Bravo; Frédérique Reverchon (Rhizosphere, 2024)

Crustal mobility analysis in the proximal Andean broken foreland at 31°S: A geodetic and geophysical approach - Flavia Leiva; Francisco Ruiz; Aixa Rodriguez; Gemma Acosta; Marcelo Gonzalez; Franco Clavel; Guido M. Gianni; Virginia Mackern; Federico Lince Klinger; Héctor P.A. Garcia; Marianela Lupari; Marcos Sánchez; et al. (Journal of South American Earth Sciences, 2024)

Cadmium exposure induced light/dark- and time-dependent redox changes at subcellular level in Arabidopsis plants - Aurelio M. Collado-Arenal; Marino Exposito-Rodriguez; Philip M. Mullineaux; Adela Olmedilla; María C. Romero-Puertas; Luisa M. Sandalio (Journal of Hazardous Materials, 2024)

Exploring the nexus of urban form, transport, environment and health in large-scale urban studies: A state-of-the-art scoping review - Georgia M.C. Dyer; Sasha Khomenko; Deepti Adlakha; Susan Anenberg; Martin Behnisch; Geoff Boeing; Manuel Esperon-Rodriguez; Antonio Gasparrini; Haneen Khreis; Michelle C. Kondo; Pierre Masselot; Robert I. McDonald; et al. (Environmental Research, 2024)

Morphological changes in the fetal kidney induced by exposure to fluoride during pregnancy - Esaú Montañez-Rodriguez; Sabino Hazael Avila-Rojas; Ariana Guadalupe Jimenez-Dorantes; Juan Carlos León-Contreras; Rogelio Hernandez-Pando; José Manuel Arreola-Guerra; Casimiro Gerarduzzi; María Estela Meléndez-Camargo; Luz M. Del Razo; Olivier Christophe Barbier (Environmental Toxicology and Pharmacology, 2024)

A direct geolocation method for aerial imaging surveys of invasive plants - R. Rodriguez; D. M. Jenkins; J. Leary; R. Perroy (International Journal of Environmental Science and Technology, 2024)

Validation of a novel western blot assay to monitor patterns and levels of alpha dystroglycan in skeletal muscle of patients with limb girdle muscular dystrophies - Thulashitha Rajasingham; Hector M. Rodriguez; Andreas Betz; Douglas M. Sproule; Uma Sinha (Journal of Muscle Research and Cell Motility, 2024)
The cell membrane protein, dystroglycan, plays a crucial role in connecting the cytoskeleton of a variety of mammalian cells to the extracellular matrix. The α-subunit of dystroglycan (αDG) is characterized by a high level of glycosylation, including a unique O-mannosyl matriglycan. This specific glycosylation is essential for binding of αDG to extracellular matrix ligands effectively. A subset of muscular dystrophies, called dystroglycanopathies, are associated with aberrant, dysfunctional glycosylation of αDG. This defect prevents myocytes from attaching to the basal membrane, leading to contraction-induced injury. Here, we describe a novel Western blot (WB) assay for determining levels of αDG glycosylation in skeletal muscle tissue. The assay described involves extracting proteins from fine needle tibialis anterior (TA) biopsies and separation using SDS-PAGE followed by WB. Glycosylated and core αDG are then detected in a multiplexed format using fluorescent antibodies. A practical application of this assay is demonstrated with samples from normal donors and patients diagnosed with LGMD2I/R9. Quantitative analysis of the WB, which employed the use of a normal TA derived calibration curve, revealed significantly reduced levels of αDG in patient biopsies relative to unaffected TA. Importantly, the assay was able to distinguish between the L276I homozygous patients and a more severe form of clinical disease observed with other FKRP variants. Data demonstrating the accuracy and reliability of the assay are also presented, which further supports the potential utility of this novel assay to monitor changes in ⍺DG of TA muscle biopsies in the evaluation of potential therapeutics.

A multi-technique approach to unveil the composition and fabrication of a pre-Roman glass masterpiece: a double-faced human-head shape polychrome glass pendant (2nd -1st c. BC) - S. Barroso-Solares; E. Estalayo; J. Aramendia; E. Rodriguez-Gutierrez; C. Sanz-Minguez; A. C. Prieto; J. M. Madariaga; J. Pinto (Archaeological and Anthropological Sciences, 2024)
Pre-Roman glass craftsmanship reached its summit with the development of complex polychrome glass beads, being the Phoenician glass pendants the most exquisite and elaborate example. The uniqueness and complexity of such findings could reveal key information for the understanding of the production and trade of glass pieces at that age. However, these findings have practically never been studied from a physic-chemical perspective. In this work, a remarkable polychrome glass pendant (2nd -1st c. BC) found at the archaeological site of Pintia (Padilla de Duero, Valladolid, Spain) is studied by a multi-analytical non-destructive approach, employing X-ray tomography to understand its fabrication procedure, as well as X-ray fluorescence (XRF) and Raman spectroscopy, both employed in microscopic mode, to determine the composition of each glass employed in its fabrication. The outstanding preservation state and well-defined archaeological context of this glass pendant offered a unique opportunity to expand the understanding of pre-Roman glass pieces, while the combination of the experimental techniques employed provided the first complete and detailed study of a Phoenician glass pendant. The fabrication procedure of the pendant has been identified step-by-step, showing evidence of the use of pre-made pieces for the eyes, as well as hints of its fabrication in a secondary workshop. Moreover, the microchemical analysis of the vividly colored glasses by XRF and Raman spectroscopy revealed a composition compatible with the use of natron as fluxing agent, typical of Phoenician glass, the presence of surface alterations corresponding to carbonatation processes, as well as the nature of the employed chromophores or pigments: Mn, Cu, and Co for the blue, Fe-S for the black, CaSb 2 O 7 and CaSb 2 O 7 + TiO 2 for two diverse white glasses, and a pyrochloric triple oxide (Pb 2 Sb 2 − x Sn x O 7−x/2 ) and lead oxides for the yellow. Remarkably, the use of pyrochloric triple oxides as yellow pigments has scarcely been previously reported at that age. Finally, the identification by Raman spectroscopy of CaSb 2 O 7 and the β-phase of CaSiO 3 , as well as the Raman spectra features of the glass matrix corresponding to the blue glass, indicated maximum firing temperatures below 1100 °C.

Fabrication, characterization, and potential applications of re-assembled casein micelles - Muhammed Aslam Khan; Yacine Hemar; Jiecheng Li; Zhi Yang; Luis M. De Leon-Rodriguez (Critical Reviews in Food Science and Nutrition, 2024)

Role of peripheral inflammation in minimal hepatic encephalopathy - Marta Llansola; Paula Izquierdo-Altarejos; Carmina Montoliu; Gergana Mincheva; Andrea Palomares-Rodriguez; María A. Pedrosa; Yaiza M. Arenas; Vicente Felipo (Metabolic Brain Disease, 2024)

“Hg distribution and accumulation in soil and vegetation in areas impacted by artisanal gold mining in the Southern Amazonian region of Madre de Dios, Peru.” - Maria J. Rodriguez-Pascual; Claudia M. Vega; Natasha Andrade; Luis E. Fernández; Miles R. Silman; Alba Torrents (Chemosphere, 2024)

Sequential high-recovery nanofiltration and electrochemical degradation for the treatment of pharmaceutical wastewater - Chenyi Fang; Orlando Garcia-Rodriguez; Liming Yang; Yaochang Zhou; Joseph Imbrogno; Tim M. Swenson; Olivier Lefebvre; Sui Zhang (Water Research, 2024)

No Effect of Breakfast Consumption Observed for Afternoon Resistance Training Performance in Habitual Breakfast Consumers and Nonconsumers: A Randomized Crossover Trial - Matthew T. Stratton; Madelin R. Siedler; Christian Rodriguez; Patrick S. Harty; Jake R. Boykin; Dale S. Keith; Jacob J. Green; Sarah J. White; Ethan Tinoco; Brielle DeHaven; Trisha A. VanDusseldorp; Grant M. Tinsley (Journal of the Academy of Nutrition and Dietetics, 2024)

Connecting blue-green infrastructure elements to reduce combined sewer overflows - Giovan Battista Cavadini; Mayra Rodriguez; Lauren M. Cook (Journal of Environmental Management, 2024)

Crop nitrogen status and yield formation: A cross-species comparison for maize, rice, and wheat field crops - Ignacio M. Rodriguez; Josefina Lacasa; Gilles Lemaire; Ben Zhao; Syed Tahir Ata-Ul-Karim; Ignacio A. Ciampitti (Field Crops Research, 2024)

Spatio-temporal patterns in the biomass, species composition and nitrogen content of drift macroalgae in an urbanised coastal embayment - Juan Manuel Valero-Rodriguez; Tim Dempster; Wei Wen Wong; John A. Lewis; Perran L. M. Cook; Stephen E. Swearer (Journal of Applied Phycology, 2024)
Understanding spatio-temporal variability in the production of drift macroalgae is useful for monitoring and assessing the influence of local anthropogenic nutrient sources on coastal ecosystems. In this study we: (1) assessed how the drift macroalgal community composition and biomass have changed over a 22-year period in Port Phillip Bay (a large coastal embayment in Victoria, Australia); and (2) measured the amount of accumulated nitrogen in drift macroalgae and the contribution of anthropogenic nitrogen sources through isotopic analysis. The surveys revealed little overlap in species composition (<13%) and a significant decrease in standing stock biomass (from 631 to 49 g m -2 ) between surveys (1995/1996 and 2017/2018). This was associated with a high degree of turnover (β-diversity) at the genus level between surveys (mean – 0.53), resulting in distinct communities at all sites, particularly among red algal genera. In addition, the occurrence of ephemeral macroalgal blooms and a semi-perennial mat of the red macroalga Botryocladia sonderi at 10-15 m depth at locations close to nutrient sources indicate drift macroalgae are important nutrient accumulators in the bay. Isotopic analysis revealed a high contribution of anthropogenic-derived nitrogen (δ 15 N > 17‰ and ~ 3% N content) at depths and locations close to nutrient sources, particularly at times of the year when large wastewater discharges occur. Harvesting of drift macroalgae could be a cost-effective solution for offsetting nitrogen inputs from anthropogenic sources, but it will be important to first investigate whether harvesting results in negative impacts to associated fauna or nutrient cycling.

Outpatient glucocorticoid use and COVID-19 outcomes: a population-based study - Almudena Rodríguez-Fernández; Irene Visos-Varela; Maruxa Zapata-Cachafeiro; Samuel Pintos-Rodríguez; Rosa M. García-Álvarez; Teresa M. Herdeiro; María Piñeiro-Lamas; Adolfo Figueiras; Ángel Salgado-Barreira; Rosendo Bugarín-González; Eduardo Carracedo-Martínez; Rosa M García-Álvarez; et al. (Inflammopharmacology, 2024)
Introduction Owing to controversy information surrounds effect of glucocorticoids on the evolution of COVID-19, we evaluate the effects of outpatient glucocorticoid use on the severity and progression of COVID-19 and risk of infection and analyse the effect of window of exposure and dose. Methods We conducted a population-based case − control study, involving 4 substudies: (i) Hospitalisation; (ii) Mortality, using subjects hospitalised with a PCR + as cases and subjects without a PCR + as controls; (iii) Progression, including subjects with a PCR + (hospitalised versus non-hospitalised); and (iv) Susceptibility, with all subjects with a PCR + and subjects without a PCR + . Adjusted odds ratios (ORa) and their 95% confidence intervals (95% CI) were calculated. Results The outpatient glucocorticoid use was associated with an increased risk of hospitalisation (aOR 1.79; 95% CI 1.56–2.05), mortality (aOR 2.30; 95% CI 1.68–3.15), progression (aOR 1.69; 95% CI 1.43–2.00) and susceptibility (aOR 1.29, 95% CI 1.19–1.41). Furthermore, the effects was observed to be greater at higher doses and the closer that drug use approached the outcome date, with an almost fourfold increase in mortality among users in the previous month (aOR 3.85; 95% CI 2.63–5.62). Conclusions According to the results of this real-world data study, outpatient glucocorticoid use should be considered in making decisions about intrahospital treatment.

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Sediment analysis and water quality assessment in the Pixquiac basin: drinking water supply of Xalapa city (Veracruz, Mexico) - M. C. Dupont; E. Martinez-Tavera; P. F. Rodriguez-Espinosa; A. G. Hernandez-Ramirez; P. Guadarrama Guzmán (Environmental Monitoring and Assessment, 2024)

Environmental performance analysis of coated austenitic steels for their use in supercritical steam turbines - M. Baranda; C. Mayo; R. Diaz; R. Rodriguez; F. J. Pérez (Clean Technologies and Environmental Policy, 2024)

Screening mammography frequency following dense breast notification among a predominantly Hispanic/Latina screening cohort - Erica J. Lee Argov; Carmen B. Rodriguez; Mariangela Agovino; Karen M. Schmitt; Elise Desperito; Anita G. Karr; Ying Wei; Mary Beth Terry; Parisa Tehranifar (Cancer Causes & Control, 2024)

Lightning-induced fire regime in Portugal based on satellite-derived and in situ data - Lucas S. Menezes; Ana Russo; Renata Libonati; Ricardo M. Trigo; José M.C. Pereira; Akli Benali; Alexandre M. Ramos; Célia M. Gouveia; Carlos A. Morales Rodriguez; Ricardo Deus (Agricultural and Forest Meteorology, 2024)

Mn and Co decorated biomorphic ceria fiber catalysts for soot and benzene total oxidation. - M. Rodriguez; F. Hanon; F. Devred; E.M. Gaigneaux; E.E. Miró; V.G. Milt (Chemosphere, 2024)

Water temperature and microenvironmental factors predict the presence and detection of the snail host of Fasciola hepatica in Andean Patagonia - Ana C. Rodriguez Quinteros; Paula Soler; Marcela Larroza; Juan M. Morales; Juan M. Gurevitz (Veterinary Parasitology, 2024)

Nobiletin as a novel agent to enhance porcine in vitro embryo development and quality - Yulia N. Cajas; Karina Cañón-Beltrán; Rosane Mazzarella; Carolina Nuñez-Puente; Encina M. González; Heriberto Rodriguez-Martinez; Dimitrios Rizos; Cristina A. Martinez-Serrano (Theriogenology, 2024)

Sunflower yield gaps and their causes in Argentina - Ignacio M. Rodriguez; Antonio J. Hall; Juan P. Monzon; Jorge L. Mercau; Sofia Gayo; Monica Lopez Pereira; Anibal Cerrudo; Hernán A. Urcola; Carolina B. Troglia; Sebastián Zuil; María Paolini; Gustavo Martini; et al. (Field Crops Research, 2024)

Pioneering minimum liquid discharge desalination: A pilot study in Lampedusa Island - C. Morgante; F. Vassallo; C. Cassaro; G. Virruso; D. Diamantidou; N. Van Linden; A. Trezzi; C. Xenogianni; R. Ktori; M. Rodriguez; G. Scelfo; S. Randazzo; et al. (Desalination, 2024)

The imprint of coevolving semi-arid landscapes, soil, and vegetation on soil moisture and vegetation variability - Ankur Srivastava; Omer Yetemen; Jose F. Rodriguez; Nikul Kumari; Patricia M. Saco (CATENA, 2024)

Oligodeoxynucleotide IMT504: Effects on Central Nervous System Repair Following Demyelination - Patricia A. Mathieu; Yim Rodriguez Sampertegui; Fernanda Elias; Alexis Silva Silva; María de Luján Calcagno; Ricardo López; Ana M. Adamo (Molecular Neurobiology, 2024)

Global mercury concentrations in biota: their use as a basis for a global biomonitoring framework - David C. Evers; Joshua T. Ackerman; Staffan Åkerblom; Dominique Bally; Nil Basu; Kevin Bishop; Nathalie Bodin; Hans Fredrik Veiteberg Braaten; Mark E. H. Burton; Paco Bustamante; Celia Chen; John Chételat; et al. (Ecotoxicology, 2024)
An important provision of the Minamata Convention on Mercury is to monitor and evaluate the effectiveness of the adopted measures and its implementation. Here, we describe for the first time currently available biotic mercury (Hg) data on a global scale to improve the understanding of global efforts to reduce the impact of Hg pollution on people and the environment. Data from the peer-reviewed literature were compiled in the Global Biotic Mercury Synthesis (GBMS) database (>550,000 data points). These data provide a foundation for establishing a biomonitoring framework needed to track Hg concentrations in biota globally. We describe Hg exposure in the taxa identified by the Minamata Convention: fish, sea turtles, birds, and marine mammals. Based on the GBMS database, Hg concentrations are presented at relevant geographic scales for continents and oceanic basins. We identify some effective regional templates for monitoring methylmercury (MeHg) availability in the environment, but overall illustrate that there is a general lack of regional biomonitoring initiatives around the world, especially in Africa, Australia, Indo-Pacific, Middle East, and South Atlantic and Pacific Oceans. Temporal trend data for Hg in biota are generally limited. Ecologically sensitive sites (where biota have above average MeHg tissue concentrations) have been identified throughout the world. Efforts to model and quantify ecosystem sensitivity locally, regionally, and globally could help establish effective and efficient biomonitoring programs. We present a framework for a global Hg biomonitoring network that includes a three-step continental and oceanic approach to integrate existing biomonitoring efforts and prioritize filling regional data gaps linked with key Hg sources. We describe a standardized approach that builds on an evidence-based evaluation to assess the Minamata Convention’s progress to reduce the impact of global Hg pollution on people and the environment.

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

Microdiversity in marine pelagic ammonia‐oxidizing archaeal populations in a Mediterranean long‐read metagenome - Pablo Suárez‐Moo; Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera (Environmental Microbiology, 2024)
The knowledge of the different population‐level processes operating within a species, and the genetic variability of the individual prokaryotic genomes, is key to understanding the adaptability of microbial populations. Here, we characterized the flexible genome of ammonia‐oxidizing archaeal (AOA) populations using a metagenomic recruitment approach and long‐read (PacBio HiFi) metagenomic sequencing. In the lower photic zone of the western Mediterranean Sea (75 m deep), the genomes Nitrosopelagicus brevis CN25 and Nitrosopumilus catalinensis SPOT1 had the highest recruitment values among available complete AOA genomes. They were used to analyse the diversity of flexible genes (variable from strain to strain) by examining the long‐reads located within the flexible genomic islands (fGIs) identified by their under‐recruitment. Both AOA genomes had a large fGI involved in the glycosylation of exposed structures, highly variable, and rich in glycosyltransferases. N. brevis had two fGIs related to the transport of phosphorus and ammonium respectively. N. catalinensis had fGIs involved in phosphorus transportation and metal uptake. A fGI5 previously reported as ‘unassigned function’ in N. brevis could be associated with defense. These findings demonstrate that the microdiversity of marine microbe populations, including AOA, can be effectively characterized using an approach that incorporates third‐generation sequencing metagenomics.

Multinational evaluation of genetic diversity indicators for the Kunming‐Montreal Global Biodiversity Framework - Alicia Mastretta‐Yanes; Jessica M. da Silva; Catherine E. Grueber; Luis Castillo‐Reina; Viktoria Köppä; Brenna R. Forester; W. Chris Funk; Myriam Heuertz; Fumiko Ishihama; Rebecca Jordan; Joachim Mergeay; Ivan Paz‐Vinas; et al. (Ecology Letters, 2024)
Under the recently adopted Kunming‐Montreal Global Biodiversity Framework, 196 Parties committed to reporting the status of genetic diversity for all species. To facilitate reporting, three genetic diversity indicators were developed, two of which focus on processes contributing to genetic diversity conservation: maintaining genetically distinct populations and ensuring populations are large enough to maintain genetic diversity. The major advantage of these indicators is that they can be estimated with or without DNA‐based data. However, demonstrating their feasibility requires addressing the methodological challenges of using data gathered from diverse sources, across diverse taxonomic groups, and for countries of varying socio‐economic status and biodiversity levels. Here, we assess the genetic indicators for 919 taxa, representing 5271 populations across nine countries, including megadiverse countries and developing economies. Eighty‐three percent of the taxa assessed had data available to calculate at least one indicator. Our results show that although the majority of species maintain most populations, 58% of species have populations too small to maintain genetic diversity. Moreover, genetic indicator values suggest that IUCN Red List status and other initiatives fail to assess genetic status, highlighting the critical importance of genetic indicators.

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

Phthalates and substitute plasticizers: Main achievements from the European human biomonitoring initiative HBM4EU - Antje Gerofke; Rosa Lange; Nina Vogel; Phillipp Schmidt; Till Weber; Madlen David; Hanne Frederiksen; Kirsten Baken; Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Žanna Martinsone; et al. (International Journal of Hygiene and Environmental Health, 2024)

Predicting milk-derived hydrogel-forming peptides with TANGO - Muhammed Aslam Khan; Yacine Hemar; Ka-Wing Cheng; Florian J. Stadler; Luis M. De Leon-Rodriguez (International Dairy Journal, 2024)

Time course of acute hepatopancreatic necrosis disease (AHPND) in the Pacific white shrimp Penaeus vannamei by wet mount analysis - Rodolfo Lozano-Olvera; Selene M. Abad-Rosales; Sonia A. Soto-Rodriguez; Karla G. Aguilar-Rendón (Aquaculture International, 2024)

Like noodles in a soup: Anthropogenic microfibers are being ingested by juvenile fish in nursery grounds of the Southwestern Atlantic Ocean - Nadia M. Alves; Julieta Rodriguez; Rosana Di Mauro; Julieta S. Rodríguez; David Maldonado; Mara S. Braverman; Brenda Temperoni; Marina V. Diaz (Marine Pollution Bulletin, 2024)

Quis custodiet ipsos custodes? A call for community participation in the governance of the SeqCode - Iain C. Sutcliffe; Luis M. Rodriguez-R; Stephanus N. Venter; William B. Whitman (Systematic and Applied Microbiology, 2024)

Graphene-based Semiconductors for Photocatalytic Degradation of Organic Dye from Wastewater: A Comprehensive Review - Pierre G. Ramos; Harry Rivera; Luis A. Sánchez; María E. Quintana; Juan M. Rodriguez (Water, Air, & Soil Pollution, 2024)

Exploring genomic inbreeding and selection signatures in a commercial Brangus herd through functional annotation - Gabriel A. Zayas; Eduardo E. Rodriguez; Aakilah S. Hernandez; Fernanda M. Rezende; Raluca G. Mateescu (Journal of Applied Genetics, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Do baseline assumptions alter the efficacy of green stormwater infrastructure to reduce combined sewer overflows? - Mayra Rodriguez; Giovan Battista Cavadini; Lauren M. Cook (Water Research, 2024)

Water in Circular Economy and Resilience (WICER) Framework - A. Delgado; D.J. Rodriguez; C.A. Amadei; M. Makino (Utilities Policy, 2024)

Effect of storage and single layer centrifugation before cryopreservation on stallion sperm cryosurvival - M.M. Nunes; J.M. Morrell; F.C.C. Santos; M.H. Miragaya; M.F. Gallelli; M. Rodriguez; J.D. Guimarães (Journal of Equine Veterinary Science, 2024)

Evaluation of water diffusion, water vapor permeability coefficients, physicochemical and antimicrobial properties of thin films of nopal mucilage, orange essential oil, and orange pectin - Roberta M. Mora-Palma; Porfirio E. Martinez-Munoz; Margarita Contreras-Padilla; A. Feregrino-Perez; Mario E. Rodriguez-Garcia (Journal of Food Engineering, 2024)

MaPPeRTrac: A Massively Parallel, Portable, and Reproducible Tractography Pipeline - Lanya T. Cai; Joseph Moon; Paul B. Camacho; Aaron T. Anderson; Won Jong Chwa; Bradley P. Sutton; Amy J. Markowitz; Eva M. Palacios; Alexis Rodriguez; Geoffrey T. Manley; Shivsundaram Shankar; Peer-Timo Bremer; et al. (Neuroinformatics, 2024)

A new approach of simultaneous adsorption and regeneration of activated carbon to address the bottlenecks of pharmaceutical wastewater treatment - Weichen Qin; Yuling Dong; Huan Jiang; Wei Hao Loh; Joseph Imbrogno; Tim M. Swenson; Orlando Garcia-Rodriguez; Olivier Lefebvre (Water Research, 2024)

Considerations for the development of guidance on dose level selection for developmental and reproductive toxicity studies - R.W. Lewis; A.K. Andrus; J. Arroyo; S. Brescia; P.A. Botham; M. Corvaro; G.P. Daston; T. Hofmann; C. Rodriguez; F. Sewell; B. van Ravenzwaay; K. Wiench; et al. (Regulatory Toxicology and Pharmacology, 2024)

Possibly seismically triggered avalanches after the S1222a Marsquake and S1000a impact event - A. Lucas; I.J. Daubar; M. Le Teuff; C. Perrin; T. Kawamura; L. Posiolova; P. Lognonné; S. Rodriguez; D. Giardini; G. Sainton; A. Mangeney; A. McEwen (Icarus, 2024)

Revisiting the relationship between nitrogen nutrition index and yield across major species - Ignacio M. Rodriguez; Josefina Lacasa; Emmanuela van Versendaal; Gilles Lemaire; Gilles Belanger; Guillaume Jégo; Patricio G. Sandaña; Rogério P. Soratto; Ivica Djalovic; Syed Tahir Ata-Ul-Karim; Nahuel I. Reussi Calvo; Claudia M. Giletto; et al. (European Journal of Agronomy, 2024)

Assessment of gill microbiome of two strains of Atlantic salmon reared in flowthrough and recirculation hatcheries and following seawater transfer - Petra R. Quezada-Rodriguez; Jamie Downes; Fintan Egan; Richard S. Taylor; Samantha White; Aisling Brenan; Megan L. Rigby; Barbara F. Nowak; James W. Wynne; Neil M. Ruane (Aquaculture, 2024)

Lab-scale engineered hydrochar production and techno-economic scaling-up analysis - Kannan Nadarajah; Oscar M. Rodriguez-Narvaez; Jerome Ramirez; Erick R. Bandala; Ashantha Goonetilleke (Waste Management, 2024)

Practice Is Evolving—a Briefing of the Revised 2024 Scopes and Standards of Practice - Susan Adams; Patricia Davidson; Erica Howes; Kimi McAdam; Christopher M. Messenger; Christopher Mills; Egondu M. Onuoha; Anna Marie Rodriguez; Christina Rollins; Dana Buelsing Sowards; Karen Hui; Carol J. Gilmore; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Glandular trichomes as a source of antifungal metabolites in a karyologically characterized population of Argyrochosma flava: Morphology and histochemistry - Ana M. Rodriguez; Marcos G. Derita; Aldo R. Andrada; Valeria de los A. Páez; Mónica Ponce; Olga G. Martínez; Diego A. Neira; Marcela A. Hernández (Flora, 2024)

Non-Catalytic direct partial oxidation of methane to methanol in a Wall-Coated microreactor - Kelly Cohen; Justin Blanchard; Paul Rodriguez; Kevin Kelly; James A. Dorman; Kerry M. Dooley (Chemical Engineering Journal, 2024)

Synergistic effect of Pd single atoms and nanoparticles deposited on carbon supports by ALD boosts alkaline hydrogen evolution reaction - Bilal Bawab; Sitaramanjaneya M. Thalluri; Eva Kolíbalová; Raul Zazpe; Ludek Jelinek; Jhonatan Rodriguez-Pereira; Jan M. Macak (Chemical Engineering Journal, 2024)

Effect of biosolid compost amended on Pb availability in soils cultivated with lettuce - M. E. Gómez; G. V. Ferreyroa; M. J. Salazar; M. L. Pignata; J. H. Rodriguez (International Journal of Environmental Science and Technology, 2024)

Exploring the potential of microbial fuel cell-assisted biodegradation of nonylphenol - E. De la Peña; C. Castillo-Zacarías; R. G. Araújo; M. Rostro-Alanis; R. Parra-Saldivar; J. Rodriguez-Rodriguez (International Journal of Environmental Science and Technology, 2024)

Multi-omic characterization of mechanisms contributing to rapid phenotypic plasticity in the coral Acropora cervicornis under divergent environments - Javier A. Rodriguez-Casariego; Alex Mercado-Molina; Leila Soledade Lemos; Natalia Soares Quinete; Anthony Bellantuono; Mauricio Rodriguez-Lanetty; Alberto Sabat; Jose M. Eirin-Lopez (Coral Reefs, 2024)

Analysis of an optical imaging system prototype for autonomously monitoring zooplankton in an aquaculture facility - M.N. Bowman; R.A. McManamay; A. Rodriguez Perez; G. Hamerly; W. Arnold; E. Steimle; K. Kramer; B. Norris; D. Prangnell; M. Matthews (Aquacultural Engineering, 2024)

Andean soil-derived lignocellulolytic bacterial consortium as a source of novel taxa and putative plastic-active enzymes - Laura Díaz-García; Maria Chuvochina; Golo Feuerriegel; Boyke Bunk; Cathrin Spröer; Wolfgang R. Streit; Luis M. Rodriguez-R; Jörg Overmann; Diego Javier Jiménez (Systematic and Applied Microbiology, 2024)

Investigating the gastrointestinal physiology of mature horses with and without a history of cribbing behavior in response to feeding a digestive support supplement - Ana M. Arias-Esquivel; Ana C. Cerqueira de Melo Vasco; Jill Lance; Lori K Warren; Luis A Rodriguez-Campos; Megan C. Lee; Christina N. Rodriguez; Carissa L Wickens (Journal of Equine Veterinary Science, 2024)

A user's guide to the bioinformatic analysis of shotgun metagenomic sequence data for bacterial pathogen detection - Blake G. Lindner; Kenji Gerhardt; Dorian J. Feistel; Luis M. Rodriguez-R; Janet K. Hatt; Konstantinos T. Konstantinidis (International Journal of Food Microbiology, 2024)

Self-governance mediates small-scale fishing strategies, vulnerability and adaptive response - Timothy H. Frawley; Blanca González-Mon; Mateja Nenadovic; Fiona Gladstone; Keiko Nomura; José Alberto Zepeda-Domínguez; Salvador Rodriguez-Van Dyck; Erica M. Ferrer; Jorge Torre; Fiorenza Micheli; Heather M. Leslie; Xavier Basurto (Global Environmental Change, 2024)

Impact of Drought on Ecohydrology of Southern California Grassland and Shrubland - Luciana Chavez Rodriguez; Scot Parker; Nicole M. Fiore; Steven D. Allison; Michael L. Goulden (Ecosystems, 2024)
Through their rooting profiles and water demands, plants affect the distribution of water in the soil profile. Simultaneously, soil water content controls plant development and interactions within and between plant communities. These plant-soil water feedbacks might vary across plant communities with different rooting depths and species composition. In semiarid environments, understanding these differences will be essential to predict how ecosystems will respond to drought, which may become more frequent and severe with climate change. In this study, we tested how plant-soil water feedbacks responded to drought in two contrasting ecosystem types—grassland and shrubland—in the coastal foothills of southern California. During years 5–8 of an ongoing precipitation manipulation experiment, we measured changes in plant communities and soil moisture up to 2 m depth. We observed different water use patterns in grassland and shrubland communities with distinct plant functional types and water use strategies. Drought treatment did not affect perennial, deep-rooted shrubs because they could access deep soil water pools. However, mid-rooted shrubs were sensitive to drought and experienced decreased productivity and die-off. As a result, water content actually increased with drought at soil depths from 50–150 cm. In grassland, biomass production by annual species, including annual grasses and forbs, declined with drought, resulting in lower water uptake from the surface soil layer. An opportunistic “live fast, die young“ life strategy allowed these species to recover quickly once water availability increased. Our results show how drought interacts with plant community composition to affect the soil water balance of semiarid ecosystems, information that could be integrated into global scale models.

Intra-urban variability of long-term exposure to PM2.5 and NO2 in five cities in Colombia - Laura A. Rodriguez-Villamizar; Yurley Rojas; Sara Grisales; Sonia C. Mangones; Jhon J. Cáceres; Dayana M. Agudelo-Castañeda; Víctor Herrera; Diana Marín; Juan G. Piñeros Jiménez; Luis C. Belalcázar-Ceron; Oscar Alberto Rojas-Sánchez; Jonathan Ochoa Villegas; et al. (Environmental Science and Pollution Research, 2023)
Rapidly urbanizing cities in Latin America experience high levels of air pollution which are known risk factors for population health. However, the estimates of long-term exposure to air pollution are scarce in the region. We developed intraurban land use regression (LUR) models to map long-term exposure to fine particulate matter (PM 2.5 ) and nitrogen dioxide (NO 2 ) in the five largest cities in Colombia. We conducted air pollution measurement campaigns using gravimetric PM 2.5 and passive NO 2 sensors for 2 weeks during both the dry and rainy seasons in 2021 in the cities of Barranquilla, Bucaramanga, Bogotá, Cali, and Medellín, and combined these data with geospatial and meteorological variables. Annual models were developed using multivariable spatial regression models. The city annual PM 2.5 mean concentrations measured ranged between 12.32 and 15.99 µg/m 3 while NO 2 concentrations ranged between 24.92 and 49.15 µg/m 3 . The PM 2.5 annual models explained 82% of the variance ( R 2 ) in Medellín, 77% in Bucaramanga, 73% in Barranquilla, 70% in Cali, and 44% in Bogotá. The NO 2 models explained 65% of the variance in Bucaramanga, 57% in Medellín, 44% in Cali, 40% in Bogotá, and 30% in Barranquilla. Most of the predictor variables included in the models were a combination of specific land use characteristics and roadway variables. Cross-validation suggests that PM 2.5 outperformed NO 2 models. The developed models can be used as exposure estimate in epidemiological studies, as input in hybrid models to improve personal exposure assessment, and for policy evaluation.

Current deformation along the northern Caribbean plate boundary from GNSS measurements in Cuba - E. Calais; O.F. Gonzalez; E.D. Arango-Arias; B. Moreno; R. Palau; M. Cutie; E. Diez; C. Montenegro; E. Rodriguez Roche; J. Garcia; E. Castellanos; S. Symithe (Tectonophysics, 2023)

Women's participation in the mining industry: Tracing the business case across APEC countries - Cecilia Campero; Leila M. Harris; Alessia Rodriguez; Nadja C. Kunz (The Extractive Industries and Society, 2023)

Unraveling the in vivo fate of inhaled micro- and nanoplastics with PET imaging - Samantha Delaney; Cindy Rodriguez; Samantha M. Sarrett; Eric J. Dayts; Brian M. Zeglis; Outi Keinänen (Science of The Total Environment, 2023)

Native plant growth promoting rhizobacteria improve the growth of pepper seedlings and modify the phenolic compounds profile - M. Andrés Lobato-Ureche; Marí. Micaela Pérez-Rodriguez; E. Malovini; P.N. Piccoli; R.P. Monasterio; A. Carmen Cohen (Rhizosphere, 2023)

Engineered hydrochar production methodologies, key factors influencing agriculture wastewater treatment, and life cycle analysis: A critical review - Oscar M. Rodriguez-Narvaez; Kannan Nadarajah; V.A. Suarez-Toriello; Erick R. Bandala; Ashantha Goonetilleke (Journal of Water Process Engineering, 2023)

Trauma-Informed Care Training for Dietetic Interns Improves Attitudes Toward Women Who Have Experienced Trauma - Nancy Rodriguez; Diana M. Gonzales-Pacheco; Laura D. Byham-Gray; Pamela Rothpletz-Puglia (Journal of Nutrition Education and Behavior, 2023)

From lab to table: Expanding gastronomic possibilities with fermentation using the edible fungus Neurospora intermedia - Vayu Maini Rekdal; Nabila Rodriguez-Valeron; Mikel Olaizola Garcia; Diego Prado Vásquez; Pia M. Sörensen; Rasmus Munk; Jay D. Keasling (International Journal of Gastronomy and Food Science, 2023)

Incorporating environmental covariates to explore genotype × environment × management (G × E × M) interactions: A one-stage predictive model - Michael H. Mumford; Clayton R. Forknall; Daniel Rodriguez; Joseph X. Eyre; Alison M. Kelly (Field Crops Research, 2023)

Use of silicone wristbands to measure firefighters’ exposures to polycyclic aromatic hydrocarbons (PAHs) during live fire training - Jennifer L.A. Keir; William Papas; Adam Wawrzynczak; Rocio Aranda-Rodriguez; Jules M. Blais; Paul A. White (Environmental Research, 2023)

Plasma-grafting surface modifications to enhance membrane hydrophobicity for brine membrane distillation - Hugo Giraldo-Mejía; Yurieth M. Quintero; Francisca Mery; Fernando Rodriguez; Efrem Curcio; Humberto Estay; Andreina Garcia (Desalination, 2023)

Sustained Three-Year Declines in Forest Soil Respiration are Proportional to Disturbance Severity - Kayla C. Mathes; Stephanie Pennington; Carly Rodriguez; Ben Bond-Lamberty; Jeff W. Atkins; Christoph S. Vogel; Christopher M. Gough (Ecosystems, 2023)

Why are you hitting yourself? Whole-exome sequencing diagnosis of monogenic autoimmunity - Lina M. Castano-Jaramillo; Francisco Rivas Larrauri; Selma C. Scheffler-Mendoza; Alonso Gutierrez-Hernandez; Juan Carlos Bustamante Ogando; Paulina Colin; Margarita Ortega Cisneros; Sandra Rajme-López; Edgar Alejandro Medina-Torres; Laura Berron Ruiz; Ana Luisa Rodriguez-Lozano; Sara Elva Espinosa Padilla; et al. (Journal of Genetics, 2023)

Bokashi fermentation of brewery’s spent grains positively affects larval performance of the black soldier fly Hermetia illucens while reducing gaseous nitrogen losses - Marco Gebiola; Michael V. Rodriguez; Alexandro Garcia; Andrea Garnica; Jeffery K. Tomberlin; Francesca M. Hopkins; Kerry E. Mauck (Waste Management, 2023)

Geological context and human exposures to element mixtures in mining and agricultural settings in Colombia - Oscar Florez-Vargas; Eugenio Vilanova; Carolina Alcaide; José A. Henao; Carlos A. Villarreal-Jaimes; Olga M. Medina-Pérez; Laura A. Rodriguez-Villamizar; Alvaro J. Idrovo; Luz H. Sánchez-Rodríguez (Science of The Total Environment, 2023)

Assessment of plastic waste generated by the aquaculture industry: The case study of pearl farming in French Polynesia - M. Crusot; J.-C. Gaertner; T. Rodriguez; C. Lo; N. Gaertner-Mazouni (Journal of Cleaner Production, 2023)

Anti-obesity potential of a yogurt functionalized with a CLNA-rich pomegranate oil - Manuela Machado; Sérgio Sousa; Luís M. Rodriguez-Alcalá; Ana Maria Gomes; Manuela Pintado (Food Research International, 2023)

Marriage between variable selection and prediction methods to model plant disease risk - Franco Suarez; Cecilia Bruno; Franca Kurina Giannini; M. Paz Giménez Pecci; Patricia Rodriguez Pardina; Mónica Balzarini (European Journal of Agronomy, 2023)

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Financial and Operational Feasibility Pilot of a Medically Tailored Meal Program - W. Phillips; S. Geneva; M. Yepes-Rios; M. Alejandro-Rodriguez; J. Evans; R. Miles (Journal of the Academy of Nutrition and Dietetics, 2023)

Smoking, blood DNA methylation sites and lung cancer risk - Arce Domingo-Relloso; Roby Joehanes; Zulema Rodriguez-Hernandez; Lies Lahousse; Karin Haack; M. Daniele Fallin; Miguel Herreros-Martinez; Jason G. Umans; Lyle G. Best; Tianxiao Huan; Chunyu Liu; Jiantao Ma; et al. (Environmental Pollution, 2023)

Boron isotopes in Central American volcanics indicate a key role for the subducting oceanic crust - Stephen J. Turner; Mattison H. Barickman; Julian Rodriguez; David A. Fike; Clive M. Jones; Kun Wang; Ivan P. Savov; Samuele Agostini; Michael J. Krawczynski; Rita Parai (Earth and Planetary Science Letters, 2023)

Kinetics of Na- and K- uranyl arsenate dissolution - Isabel Meza; Noah Jemison; Jorge Gonzalez-Estrella; Peter C. Burns; Virginia Rodriguez; Ginger E. Sigmon; Jennifer E.S. Szymanowski; Abdul-Mehdi S. Ali; Kaelin Gagnon; José M. Cerrato; Peter Lichtner (Chemical Geology, 2023)

Cu(II)-acylhydrazone complex, a potent and selective antitumor agent against human osteosarcoma: Mechanism of action studies over in vitro and in vivo models - Lucia M. Balsa; Luisina M. Solernó; Maria R. Rodriguez; Beatriz S. Parajón-Costa; Ana C. Gonzalez-Baró; Daniel F. Alonso; Juan Garona; Ignacio E. León (Chemico-Biological Interactions, 2023)

Semen collection and ejaculation trigger changes in the blood flow of the reproductive system in rams - Mariana Garcia Kako Rodriguez; M. Isabel Vázquez; Julia Giriboni; Danilo Fila; Rodolfo Ungerfeld (Tropical Animal Health and Production, 2023)

Upper Limb Recovery in Cervical Spinal Cord Injury After a Brain-Computer Interface Controlled Functional Electrical Stimulation Intervention - Jessica Cantillo-Negrete; Ruben I. Carino-Escobar; Ismael Leyva-Martinez; Aida Barrera-Ortiz; Marlene A. Rodriguez-Barragan; Omar Mendoza-Montoya; Javier M. Antelis (Journal of Medical and Biological Engineering, 2023)

Genomic approaches to mitigating genetic diversity loss in declining populations - Christen M. Bossu; Marina Rodriguez; Christine Rayne; Debra A. Chromczak; Philip G. Higgins; Lynne A. Trulio; Kristen C. Ruegg (Molecular Ecology, 2023)
The accelerating pace of global biodiversity loss is exacerbated by habitat fragmentation and subsequent inbreeding in small populations. To address this problem, conservation practitioners often turn to assisted breeding programmes with the aim of enhancing genetic diversity in declining populations. Although genomic information is infrequently included in these efforts, it has the potential to significantly enhance the success of such programmes. In this study, we showcase the value of genomic approaches for increasing genetic diversity in assisted breeding efforts, specifically focusing on a highly inbred population of Western burrowing owls. To maximize genetic diversity in the resulting offspring, we begin by creating an optimal pairing decision tree based on sex, kinship and patterns of homozygosity across the genome. To evaluate the effectiveness of our strategy, we compare genetic diversity, brood size and nestling success rates between optimized and non‐optimized pairs. Additionally, we leverage recently discovered correlations between telomere length and fitness across species to investigate whether genomic optimization could have long‐term fitness benefits. Our results indicate that pairing individuals with contrasting patterns of homozygosity across the genome is an effective way to increase genetic diversity in offspring. Although short‐term field‐based metrics of success did not differ significantly between optimized and non‐optimized pairs, offspring from optimized pairs had significantly longer telomeres, suggesting that genetic optimization can help reduce the risk of inbreeding depression. These findings underscore the importance of genomic tools for informing efforts to preserve the adaptive potential of small, inbred populations at risk of further decline.

Linking climate change to urban planning through vulnerability assessment: The case of two cities at the Mexico-US border - Dalia M. Muñoz-Pizza; Roberto A. Sanchez-Rodriguez; Eduardo Gonzalez-Manzano (Urban Climate, 2023)

LP-51: Determining of a broad range of organic chemicals in seminal plasma through an innovative LC-HRMS-based methodology suitable for target and non-target analysis - E. Sánchez-Resino; M. Marquès; D. Gutiérrez-Martín; E. Restrepo-Montes; M. Á. Martínez-Rodriguez; A. Salas-Huetos; N. Babio; J. Salas-Salvadó; J.L. Domingo; R. Gil-Solsona; P. Gago-Ferrero (Toxicology Letters, 2023)

P21-14: Neurodevelopmental toxicity of T-2 mycotoxin in human-based primary and induced pluripotent stem cell-derived neural progenitor cells in 3D and 2D - M. Taroncher Ruiz; J. Kapr; K. Bartmann; J. Tigges; Y. Rodriguez-Carrasco; M.J. Ruiz; E. Fritsche (Toxicology Letters, 2023)

S17-02: The Long-term Impact of Perinatal Exposures on Susceptibility to Immune-mediated Diseases - K.A. Rychlik; E.J. Illingworth; S.E. Attreed; S.S. Sanchez; A. Grant-Alfieri; M.C. Rodriguez Steube; A. Mathur; I.F. Sanchez; C. Tang; M. Suresh; G. Lopez-Cecetaite; P. Sadhukhan; et al. (Toxicology Letters, 2023)

Wood decay fungi and their bacterial interaction partners in the built environment – A systematic review on fungal bacteria interactions in dead wood and timber - Julia Embacher; Susanne Zeilinger; Martin Kirchmair; Luis M. Rodriguez-R; Sigrid Neuhauser (Fungal Biology Reviews, 2023)

Fine-tuning the CROPGRO-Sunflower model and its application to the quantification of crop responses to environmental and management variables - Ignacio M. Rodriguez; Jorge L. Mercau; Pablo A. Cipriotti; Antonio J. Hall; Juan P. Monzon (Field Crops Research, 2023)

Effect of Supranutritional Dosage Selenium in Neonatal Goat Kids on Productive Performance, Physicochemical Profiles in Meat, Selenium Levels in Tissues, and Histopathological Findings - Oscar Ortiz-Morales; J. Efrén Ramírez-Bribiesca; Jorge Hernández-Bautista; David Hernández-Sánchez; José Ricardo Bárcena-Gama; Elein Hernández-Trujillo; Victor M. Díaz-Sánchez; German Garrido-Fariña; José C. López-Ojeda; Martha Hernández-Rodriguez (Biological Trace Element Research, 2023)

Pesticides exposure in pregnant Argentinian women: Potential relations with the residence areas and the anthropometric neonate parameters - Piuque M. Rodriguez; Paola M. Ondarza; Karina S.B. Miglioranza; Critina L. Ramirez; Berta Vera; Celeste Muntaner; Natalia L. Guiñazú (Chemosphere, 2023)

Biological processes modelling for MBR systems: A review of the state-of-the-art focusing on SMP and EPS - Giorgio Mannina; Bing-Jie Ni; Jacek Makinia; Jérôme Harmand; Marion Alliet; Christoph Brepols; M. Victoria Ruano; Angel Robles; Marc Heran; Hazal Gulhan; Ignasi Rodriguez-Roda; Joaquim Comas (Water Research, 2023)

Cryotop vitrification of large batches of pig embryos simultaneously provides excellent postwarming survival rates and minimal interference with gene expression - Alejandro Gonzalez-Plaza; Josep M. Cambra; Manuela Garcia-Canovas; Inmaculada Parrilla; Maria A. Gil; Emilio A. Martinez; Heriberto Rodriguez-Martinez; Cristina A. Martinez; Cristina Cuello (Theriogenology, 2023)

Coastal raptors and raiders: New bird tracks in the Pleistocene of SW iberian Peninsula - Carlos Neto de Carvalho; João Belo; Silvério Figueiredo; Pedro P. Cunha; Fernando Muñiz; Zain Belaústegui; Mário Cachão; Joaquín Rodriguez-Vidal; Luis M. Cáceres; Andrea Baucon; Andrew S. Murray; Jan-Pieter Buylaert; et al. (Quaternary Science Reviews, 2023)

Miocene tropical storms: Carbonate framework approaches and geochemistry proxies in a reservoir model - Orangel Aguilera; Olga M. Oliveira De Araújo; Ricardo Tadeu Lopes; Marcelo Cohen; Dayana Alvarado Sierra; Beatriz Teixeira Guimarães; Ana Paula Linhares; Félix Rodriguez; Manuel Moreira; Rut Díaz; Hamilton Santos Gama Filho; Marcelino Jose Dos Anjos; et al. (Marine and Petroleum Geology, 2023)

Eucalyptus bleached kraft pulp-ionic liquid inks for 3D printing of ionogels and hydrogels - Cynthia Hopson; Victoria Rigual; M. Virginia Alonso; Mercedes Oliet; Francisco Rodriguez (Carbohydrate Polymers, 2023)

Improving the design and conduct of aquatic toxicity studies with oils based on 20 years of CROSERF experience - WA Stubblefield; M Barron; G Bragin; ME DeLorenzo; B de Jourdan; B Echols; DP French-McCay; P Jackman; JR Loughery; TF Parkerton; DA Renegar; JL Rodriguez-Gil (Aquatic Toxicology, 2023)

The unremarkable alveolar epithelial glycocalyx: a thorium dioxide-based electron microscopic comparison after heparinase or pneumolysin treatment - Sara Timm; Marie Lettau; Jan Hegermann; Maria Linda Rocha; Sarah Weidenfeld; Diana Fatykhova; Birgitt Gutbier; Geraldine Nouailles; Elena Lopez-Rodriguez; Andreas Hocke; Stefan Hippenstiel; Martin Witzenrath; et al. (Histochemistry and Cell Biology, 2023)
Recent investigations analyzed in depth the biochemical and biophysical properties of the endothelial glycocalyx. In comparison, this complex cell-covering structure is largely understudied in alveolar epithelial cells. To better characterize the alveolar glycocalyx ultrastructure, unaffected versus injured human lung tissue explants and mouse lungs were analyzed by transmission electron microscopy. Lung tissue was treated with either heparinase (HEP), known to shed glycocalyx components, or pneumolysin (PLY), the exotoxin of Streptococcus pneumoniae not investigated for structural glycocalyx effects so far. Cationic colloidal thorium dioxide (cThO 2 ) particles were used for glycocalyx glycosaminoglycan visualization. The level of cThO 2 particles orthogonal to apical cell membranes (≙ stained glycosaminoglycan height) of alveolar epithelial type I (AEI) and type II (AEII) cells was stereologically measured. In addition, cThO 2 particle density was studied by dual-axis electron tomography (≙ stained glycosaminoglycan density in three dimensions). For untreated samples, the average cThO 2 particle level was ≈ 18 nm for human AEI, ≈ 17 nm for mouse AEI, ≈ 44 nm for human AEII and ≈ 35 nm for mouse AEII. Both treatments, HEP and PLY, resulted in a significant reduction of cThO 2 particle levels on human and mouse AEI and AEII. Moreover, a HEP- and PLY-associated reduction in cThO 2 particle density was observed. The present study provides quantitative data on the differential glycocalyx distribution on AEI and AEII based on cThO 2 and demonstrates alveolar glycocalyx shedding in response to HEP or PLY resulting in a structural reduction in both glycosaminoglycan height and density. Future studies should elucidate the underlying alveolar epithelial cell type-specific distribution of glycocalyx subcomponents for better functional understanding.

Evaluation of reference genes for qRT-PCR studies in the colchicine producing Gloriosa superba L. - Nekha Johnson; Diana Rodriguez Diaz; Sivakumar Ganapathy; John S. Bass; Toni M. Kutchan; Abdul L. Khan; Albert B. Flavier (Plant Biotechnology Reports, 2023)

A framework for the assessment of farm diversification options in broadacre agriculture - Lipy Adhikari; Adam M. Komarek; Peter de Voil; Daniel Rodriguez (Agricultural Systems, 2023)

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Sedimentary provenance in continental rifts: U–Pb detrital zircon, Nd and Sr isotopes and lithogeochemistry of the Eocene alluvial sandstones of the Resende Basin, SE–Brazil - Manuela de Oliveira Carvalho; Catherine M. Mottram; Claudio de Morisson Valeriano; Renato Rodriguez Cabral Ramos; Randall Parrish; Joseph Dunlop; Natália Cota; Gabriel Paravidini; Carla Cristine Aguiar Neto; Monica Heilbron; Craig Storey (Sedimentary Geology, 2023)

Insulin like growth factor I plasma concentration assessment during the luteal phase in pregnant and non pregnant llamas - M. Florencia Gallelli; Marcelo Miragaya; Enzo Zampini; Liliana Rossetto; Marcelo Aba; Marcelo Rodriguez; Carolina Bianchi (Small Ruminant Research, 2023)

Does the protein structure of β-lactoglobulin impact its complex coacervation with type A gelatin and the ability of the complexes to entrap lutein? - Martin Daniel Aya Rodriguez; Danilo C. Vidotto; Ana Augusta O. Xavier; Raphaela A. Mantovani; Guilherme M. Tavares (Food Hydrocolloids, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Influence of secretome obtained from preovulatory follicular fluid on energy metabolism and meiotic competence of equine cumulus–oocyte complexes - Jose M Ortiz-Rodriguez; Pablo Fernández-Hernández; Marcos Luis-Calero; Marcella Spinaci; Diego Bucci; Beatriz Macías-García; Lauro González-Fernández (Journal of Equine Veterinary Science, 2023)

Effect of transvaginal oocyte aspiration on progesterone concentrations and estrous cycle length in domestic jennies - Ana Flores Bragulat; Carolina Alonso; Catalina Castañeira; Ayelen Rodriguez; Jose M Zeledon; Luis Losinno; Andres Gambini (Journal of Equine Veterinary Science, 2023)

Efficiency of equine oocyte recovery from post mortem ovaries or by ovum pick up - Catalina Castañeira; Ana P Flores Bragulat; Carolina N Alonso; Ayelen M Rodriguez; Guido A Rocchi; Jose M Zeledon (Journal of Equine Veterinary Science, 2023)

Dry-spun carbon nanotube ultrafiltration membranes tailored by anti-viral metal oxide coatings for human coronavirus 229E capture in water - Ahmed O. Rashed; Chi Huynh; Andrea Merenda; Julio Rodriguez-Andres; Lingxue Kong; Takeshi Kondo; Joselito M. Razal; Ludovic F. Dumée (Journal of Environmental Chemical Engineering, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Recent growth increase in endemic Juglans boliviana from the tropical Andes - Rose C. Oelkers; Laia Andreu-Hayles; Rosanne D’Arrigo; Arturo Pacheco-Solana; Milagros Rodriguez-Caton; Alfredo Fuentes; Guaciara M. Santos; Ernesto Tejedor; M. Eugenia Ferrero; Carla Maldonado (Dendrochronologia, 2023)

Connected Conservation: Rethinking conservation for a telecoupled world - Rachel Carmenta; Jos Barlow; Mairon G. Bastos Lima; Erika Berenguer; Shofwan Choiruzzad; Natalia Estrada-Carmona; Filipe França; Giorgos Kallis; Evan Killick; Alexander Lees; Adrian Martin; Unai Pascual; et al. (Biological Conservation, 2023)

Contrasting reproductive strategies between stress-tolerant and competitive coral taxa - K. G. Bonilla; J. R. Guest; M. V. Baria-Rodriguez (Coral Reefs, 2023)

Single‐amplified genomes reveal most streamlined free‐living marine bacteria - Juan J. Roda‐Garcia; Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera; Salvador Almagro‐Moreno; Mario López‐Pérez (Environmental Microbiology, 2023)
Evolutionary adaptations of prokaryotes to the environment sometimes result in genome reduction. Our knowledge of this phenomenon among free‐living bacteria remains scarce. We address the dynamics and limits of genome reduction by examining one of the most abundant bacteria in the ocean, the SAR86 clade. Despite its abundance, comparative genomics has been limited by the absence of pure cultures and the poor representation in metagenome‐assembled genomes. We co‐assembled multiple previously available single‐amplified genomes to obtain the first complete genomes from members of the four families. All families showed a convergent evolutionary trajectory with characteristic features of streamlined genomes, most pronounced in the TMED112 family. This family has a genome size of ca. 1 Mb and only 1 bp as median intergenic distance, exceeding values found in other abundant microbes such as SAR11, OM43 and Prochlorococcus . This genomic simplification led to a reduction in the biosynthesis of essential molecules, DNA repair‐related genes, and the ability to sense and respond to environmental factors, which could suggest an evolutionary dependence on other co‐occurring microbes for survival (Black Queen hypothesis). Therefore, these reconstructed genomes within the SAR86 clade provide new insights into the limits of genome reduction in free‐living marine bacteria.

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

A case of feline osteochondromatosis - Á. Gómez; A. Rodriguez Largo; E. Pérez; P. Mendivil; S. Loomans; M. Pérez; K. Chiers; L. Luján (Journal of Comparative Pathology, 2023)

Toward thermal autarky for large-scale biogas plants: Dynamic energy modeling for energy efficiency in anaerobic digesters with enhanced multimembrane gasholders - M. Avila-Lopez; C. Robles-Rodriguez; L. Tiruta-Barna; A. Ahmadi (Fuel, 2023)

Protein recovery from brewery solid wastes - Luciana M. Rodriguez; Julia L. Camina; Virginia Borroni; Ethel E. Pérez (Food Chemistry, 2023)

Multi-level responses of oysters Crassostrea virginica for assessing organochlorine pesticides in a Ramsar coastal lagoon in southern Mexico - Mariana V. Capparelli; Guadalupe Ponce-Vélez; Ricardo Dzul-Caamal; Erick M. Rodriguez-Cab; Marcela Cabrera; Oscar Lucas-Solis; Gabriel M. Moulatlet (Chemosphere, 2023)

Comparison of the 7-day CO-Synch and 8-day estradiol-based protocols for estrus synchronization and timed artificial insemination in suckled Bos taurus cows - Alejandro M. Rodriguez; Sebastian Maresca; Sebastian López-Valiente; María G. Bilbao; Karen D. Moran; Julián A. Bartolome; Scott L. Pratt; Nathan M. Long (Theriogenology, 2023)

Age-dependent effect of the IFIH1/MDA5 gene variants on the risk of critical COVID-19 - María G. Muñiz-Banciella; Guillermo M. Albaiceta; Laura Amado-Rodríguez; Estefanía Salgado del Riego; Inés López Alonso; Cecilia López-Martínez; Paula Martín-Vicente; Marta García-Clemente; Tamara Hermida-Valverde; Ana I. Enríquez-Rodriguez; Cristina Hernández-González; Elías Cuesta-Llavona; et al. (Immunogenetics, 2023)

Genus and size-specific susceptibility of soft corals to 2020 bleaching event in the Philippines - Christine C. Baran; Rhea Mae A. Luciano; Christine S. Segumalian; Darryl Anthony M. Valino; Maria Vanessa Baria-Rodriguez (Marine Biology Research, 2023)

Elastomeric biodegradable starch/bentonite nanocomposites. Structure-thermo-mechanical correlation and degradation behavior - A. Romo-Uribe; A. Reyes-Mayer; M. Calixto-Rodriguez; E. Sarmiento-Bustos (Carbohydrate Polymers, 2023)

Holistic Assessment of Calcium Fertilization in Potato: Diagnostic, Productivity, and Tuber Quality - C. M. Giletto; M. Kloster Erreguerrena; P. Ceroli; W. Carciochi; S. E. Silva; S. Rodriguez; F. Salvagiotti; N. I. Reussi Calvo (Journal of Soil Science and Plant Nutrition, 2023)

PFAS levels and exposure determinants in sensitive population groups - L. Fábelová; A. Beneito; M. Casas; A. Colles; L. Dalsager; E. Den Hond; C. Dereumeaux; K. Ferguson; L. Gilles; E. Govarts; A. Irizar; M.J. Lopez Espinosa; et al. (Chemosphere, 2023)

Global assessment of chemical quality of drinking water: The case of trihalomethanes - Cristina M Villanueva; Iro Evlampidou; Fathelrahman Ibrahim; Carolina Donat-Vargas; Antonia Valentin; Anca-Maria Tugulea; Shinya Echigo; Dragana Jovanovic; Albert T Lebedev; Mildred Lemus-Pérez; Manuel Rodriguez-Susa; Arben Luzati; et al. (Water Research, 2023)

Hotspots of geogenic arsenic and manganese contamination in groundwater of the floodplains in lowland Amazonia (South America) - Caroline M.C. de Meyer; Ingo Wahnfried; Juan M. Rodriguez Rodriguez; Rolf Kipfer; Pilar A. García Avelino; Edward A. Carpio Deza; Michael Berg (Science of The Total Environment, 2023)

Water, environment, and socioeconomic justice in California: A multi-benefit cropland repurposing framework - Angel Santiago Fernandez-Bou; José M. Rodríguez-Flores; Alexander Guzman; J. Pablo Ortiz-Partida; Leticia M. Classen-Rodriguez; Pedro A. Sánchez-Pérez; Jorge Valero-Fandiño; Chantelise Pells; Humberto Flores-Landeros; Samuel Sandoval-Solís; Gregory W. Characklis; Thomas C. Harmon; et al. (Science of The Total Environment, 2023)

Adapting to climate change on desert rangelands: A multi-site comparison of grazing behavior plasticity of heritage and improved beef cattle - Andres F. Cibils; Rick E. Estell; Sheri Spiegal; Shelemia Nyamuryekung'e; Matthew M. McIntosh; Danielle M. Duni; Oscar A. Herrera Conegliano; Felipe A. Rodriguez Almeida; Octavio Roacho Estrada; Lisandro J. Blanco; Michael C. Duniway; Santiago A. Utsumi; et al. (Journal of Arid Environments, 2023)

Serotonin transporter availability in physically aggressive personality disordered patients: associations with trait and state aggression, and response to fluoxetine - Daniel R. Rosell; Mark Slifstein; Judy Thompson; Xiaoyan Xu; M. Mercedes Perez-Rodriguez; Margaret M. McClure; Erin A. Hazlett; Antonia S. New; Nabeel Nabulsi; Yiyun Huang; Richard E. Carson; Larry S. Siever; et al. (Psychopharmacology, 2023)

Modeling spatio-temporal activity dynamics of the small relict marsupial Dromiciops gliroides - M. Soledad Vazquez; Luca Schenone; Mariano A. Rodriguez-Cabal; Guillermo C. Amico (Mammalian Biology, 2023)

Potential distribution and conservation implications of key marsupials for the Patagonian temperate forest - M. Soledad Vazquez; Ramiro R. Ripa; Mariano A. Rodriguez-Cabal; Guillermo C. Amico (Mammalian Biology, 2023)

The Challenges of Characterizing the Zooplankton Community Response Following Simulated Spills of Diluted Bitumen into Boreal Lake Limnocorrals - T. A. Black; M. J. Paterson; L. Timlick; J. Cederwall; J. M. Blais; B. Hollebone; D. M. Orihel; V. P. Palace; J. L. Rodriguez-Gil; M. L. Hanson (Bulletin of Environmental Contamination and Toxicology, 2023)

Integrating phytoplankton pigment and DNA meta‐barcoding observations to determine phytoplankton composition in the coastal ocean - Dylan Catlett; David A. Siegel; Paul G. Matson; Emma K. Wear; Craig A. Carlson; Thomas S. Lankiewicz; M. Debora Iglesias‐Rodriguez (Limnology and Oceanography, 2023)
Quantifying phytoplankton composition is critical to predicting marine ecosystem structure and function. DNA meta‐barcoding and high‐performance liquid chromatography (HPLC) pigment analysis are two widely used methods for assessing phytoplankton composition; however, comparing their performance has been done only rarely. Here, we integrate DNA meta‐barcoding and HPLC pigment observations to determine eukaryotic phytoplankton composition in the Santa Barbara Channel, California. We find that both methods identify the same four dominant eukaryotic phytoplankton taxa (diatoms, dinoflagellates, chlorophytes, and prymnesiophytes), but inter‐ and intra‐lineage variability in biomarker pigmentation (associated with both a lack of taxonomic specificity of biomarker pigments and intrinsic differences in accessory pigmentation) drives substantial disagreement between the methods. Covariation network analysis circumvents this disagreement and reveals that diverse assemblages of phytoplankton and other protists covary with distinct suites of biomarker pigments. Our results highlight the strengths and weaknesses of each method in characterizing phytoplankton composition and reveal novel insights into phytoplankton physiology that could only be gained by integrating the two methods. Finally, we suggest a path to monitor eukaryotic plankton communities on unprecedented spatiotemporal scales based on the covariation of unique phytoplankton and protistan assemblages with remotely sensible phytoplankton pigment concentrations.

Characterization of the molecular mechanisms of silicon uptake in coccolithophores - Sarah Ratcliffe; Erin M. Meyer; Charlotte E. Walker; Michael Knight; Heather M. McNair; Paul G. Matson; Debora Iglesias‐Rodriguez; Mark Brzezinski; Gerald Langer; Aleksey Sadekov; Mervyn Greaves; Colin Brownlee; et al. (Environmental Microbiology, 2023)
Coccolithophores are an important group of calcifying marine phytoplankton. Although coccolithophores are not silicified, some species exhibit a requirement for Si in the calcification process. These species also possess a novel protein (SITL) that resembles the SIT family of Si transporters found in diatoms. However, the nature of Si transport in coccolithophores is not yet known, making it difficult to determine the wider role of Si in coccolithophore biology. Here, we show that coccolithophore SITLs act as Na + ‐coupled Si transporters when expressed in heterologous systems and exhibit similar characteristics to diatom SITs. We find that CbSITL from Coccolithus braarudii is transcriptionally regulated by Si availability and is expressed in environmental coccolithophore populations. However, the Si requirement of C. braarudii and other coccolithophores is very low, with transport rates of exogenous Si below the level of detection in sensitive assays of Si transport. As coccoliths contain only low levels of Si, we propose that Si acts to support the calcification process, rather than forming a structural component of the coccolith itself. Si is therefore acting as a micronutrient in coccolithophores and natural populations are only likely to experience Si limitation in circumstances where dissolved silicon (DSi) is depleted to extreme levels.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Bioprospection of naturalized soybean-nodulating Bradyrhizobium strains in Uruguayan soils: a genetic and symbiotic approach - N. E. Rodriguez Rodriguez; E. Beyhaut; M. Sicardi; A. Rodríguez-Blanco (Environmental Sustainability, 2023)

The 2022 Diadema antillarum die-off event: Comparisons with the 1983-1984 mass mortality - Alwin Hylkema; Kimani Kitson-Walters; Patricia R. Kramer; Joshua T. Patterson; Lynnette Roth; Moriah L. B. Sevier; Maria Vega-Rodriguez; Matthew M. Warham; Stacey M. Williams; Judith C. Lang (Frontiers in Marine Science, 2023)
The 1983-1984 die-off of the long-spined sea urchin Diadema antillarum stands out as a catastrophic marine event because of its detrimental effects on Caribbean coral reefs. Without the grazing activities of this key herbivore, turf and macroalgae became the dominant benthic group, inhibiting coral recruitment and compromising coral reef recovery from other disturbances. In the decades that followed, recovery of D. antillarum populations was slow to non-existent. In late January 2022, a new mass mortality of D. antillarum was first observed in the U.S. Virgin Islands. We documented the spread and extent of this new die-off using an online survey. Infected individuals were closely monitored in the lab to record signs of illness, while a large population on Saba, Dutch Caribbean, was surveyed weekly before and during mortality to determine the lethality of this event. Within four months the die-off was distributed over 1,300 km from north to south and 2,500 km east to west. Whereas the 1983-1984 die-off advanced mostly with the currents, the 2022 event has appeared far more quickly in geographically distant areas. First die-off observations in each jurisdiction were often close to harbor areas, which, together with their rapid appearance, suggests that anthropogenic factors may have contributed to the spread of the causative agent. The signs of illness in sick D. antillarum were very similar to those recorded during the 1983-1984 die-off: lack of tube feet control, slow spine reaction followed by their loss, and necrosis of the epidermis were observed in both lab and wild urchins. Affected populations succumbed fast; within a month of the first signs of illness, a closely monitored population at Saba, Dutch Caribbean, had decreased from 4.05 individuals per m 2 to 0.05 individuals per m 2 . Lethality can therefore be as high as 99%. The full extent of the 2022 D. antillarum die-off event is not currently known. The slower spread in the summer of 2022 might indicate that the die-off is coming to a (temporary) standstill. If this is the case, some populations will remain unaffected and potentially supply larvae to downstream areas and augment natural recovery processes. In addition, several D. antillarum rehabilitation approaches have been developed in the past decade and some are ready for large scale implementation. However, active conservation and restoration should not distract from the primary goal of identifying a cause and, if possible, implementing actions to decrease the likelihood of future D. antillarum die-off events.

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Different Roles of Beclin1 in the Interaction Between Glia and Neurons after Exposure to Morphine and the HIV- Trans-Activator of Transcription (Tat) Protein - Jessica Lapierre; Mohan K. M. Karuppan; Marissa Perry; Myosotys Rodriguez; Nazira El-Hage (Journal of Neuroimmune Pharmacology, 2022)

SbTT8, a New Sorghum bHLH Transcription Factor that Rescues Brown Seed Coat Phenotype in Arabidopsis tt8 Mutant Plants - M. Agustina Salez; Javier M. González; Joana C. Bernacchini; M. Victoria Rodriguez; M. Lorena Falcone Ferreyra; Paula Casati; Sebastián P. Rius (Journal of Plant Biology, 2022)

Elevated Winter Stream Temperatures below Wastewater Treatment Plants Shift Reproductive Development of Female Johnny Darter Etheostoma nigrum: A Field and Histologic Approach - Catherine M. Adams; Dana L. Winkelman; Paula A. Schaffer; Daniel L. Villeneuve; Jenna E. Cavallin; Michael Ellman; Kelvin Santana Rodriguez; Ryan M. Fitzpatrick (Fishes, 2022)
River water temperatures are increasing globally, particularly in urban systems. In winter, wastewater treatment plant (WWTP) effluent inputs are of particular concern because they increase water temperatures from near freezing to ~7–15 °C. Recent laboratory studies suggest that warm overwinter temperatures impact the reproductive timing of some fishes. To evaluate winter water temperature’s influence in the wild, we sampled Johnny Darter Etheostoma nigrum from three urban South Platte River tributaries in Colorado upstream and downstream of WWTP effluent discharge sites. Fish were collected weekly during the spring spawning season of 2021 and reproductive development was determined from histological analysis of the gonads. Winter water temperatures were approximately 5–10 °C greater ~300 m downstream of the WWTP effluent compared to upstream sites, and approximately 3 °C warmer at sampling sites ~5000 m downstream of the effluent discharge. Females collected downstream of WWTP effluent experienced accelerated reproductive development compared to upstream by 1–2 weeks. Water quality, including total estrogenicity, and spring water temperatures did not appear to explain varying reproductive development. It appears that small increases in winter water temperature influence the reproductive timing in E. nigrum. Further investigations into how shifts in reproductive timing influence other population dynamics are warranted.

Validity of a portable X-ray fluorescence device for analyzing field dust wipe samples for lead - A. B. Obeng; M. Del Rio; C. Costa; C. Chavarria; C. Rodriguez; M. B. Galkaduwa; C. Wekumbura; K. Gamage; G. M. Hettiarachchi; W. Hargrove; C. Sobin (International Journal of Environmental Science and Technology, 2022)

Prevalence of epitheliocystis in freshwater Atlantic salmon reared in flow‐through and recirculation aquaculture systems - Petra R. Quezada‐Rodriguez; Richard S. Taylor; Jamie Downes; Fintan Egan; Samantha White; Aisling Brenan; Megan Rigby; Barbara F. Nowak; Neil M. Ruane; James W. Wynne (Journal of Fish Diseases, 2022)
Epitheliocystis, an intracellular bacterial infection in the gills and skin epithelium, has been frequently reported in Atlantic salmon ( Salmo salar ) during freshwater production in a number of countries. This study describes the prevalence and intensity of a natural epitheliocystis infection present in the gills of two strains of Atlantic salmon reared in either a flow‐through (FT) or a recirculation aquaculture system (RAS) in Ireland. Repeated sampling of gills prior to and throughout seawater transfer, histology and quantitative real‐time PCR were used to determine infection prevalence and intensity. Despite no clinical gill disease, and minor histopathological changes, epitheliocystis lesions were identified in histology at all time points. Specific PCR confirmed the presence of Candidatus Clavichlamydia salmonicola in both strains and its number of copies was correlated with intensity of epitheliocystis lesions. A significant interaction between hatchery system and fish strain on the prevalence and intensity of gill epitheliocystis was found both using histological and molecular methods. Specifically, fish from FT had higher prevalence and intensity than RAS reared fish and within FT, the Irish cohort were more affected than Icelandic.

A novel equation that incorporates the linear and hyperbolic nature of the force–velocity relationship in lower and upper limb exercises - Julian Alcazar; Fernando Pareja-Blanco; Carlos Rodriguez-Lopez; Hector Gutierrez-Reguero; Juan Sanchez-Valdepeñas; Pedro J. Cornejo-Daza; Ignacio Ara; Luis M. Alegre (European Journal of Applied Physiology, 2022)

In vivo subchronic effects of ciguatoxin-related compounds, reevaluation of their toxicity - Sandra Raposo-García; Andrea Boente-Juncal; Mercedes Rodriguez-Vieytes; Mercedes Camiña; Celia Costas; Alejandro Cao; M. Carmen Louzao; Manuel Cifuentes; Carmen Vale; Luis M. Botana (Archives of Toxicology, 2022)
Ciguatoxins are marine compounds that share a ladder-shaped polyether structure produced by dinoflagellates of the genus Gambierdiscus and Fukuyoa , and include maitotoxins (MTX1 and MTX3), ciguatoxins (CTX3C) and analogues (gambierone), components of one of the most frequent human foodborne illness diseases known as ciguatera fish poisoning. This disease was previously found primarily in tropical and subtropical areas but nowadays, the dinoflagellates producers of ciguatoxins had spread to European coasts. One decade ago, the European Food Safety Authority has raised the need to complete the toxicological available data for the ciguatoxin group of compounds. Thus, in this work, the in vivo effects of ciguatoxin-related compounds have been investigated using internationally adopted guidelines for the testing of chemicals. Intraperitoneal acute toxicity was tested for maitotoxin 1 at doses between 200 and 3200 ng/kg and the acute oral toxicity of Pacific Ciguatoxin CTX3C at 330 and 1050 ng/kg and maitotoxin 1 at 800 ng/kg were also evaluated showing not effects on mice survival after a 96 h observation period. Therefore, for the following experiments the oral subchronic doses were between 172 and 1760 ng/kg for gambierone, 10 and 102 ng/kg for Pacific Ciguatoxin CTX3C, 550 and 1760 ng/kg for maitotoxin 3 and 800, 2560 and 5000 ng/kg for maitotoxin 1. The results presented here raise the need to reevaluate the in vivo activity of these agents. Although the intraperitoneal lethal dose of maitotoxin 1 is assumed to be 50 ng/kg, without chemical purity identifications and description of the bioassay procedures, in this work, an intraperitoneal lethal dose of 1107 ng/kg was obtained. Therefore, the data presented here highlight the need to use a common procedure and certified reference material to clearly establish the levels of these environmental contaminants in food.

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

The acute effects of action observation on muscle strength/weakness and corticospinal excitability in older adults - Kylie K. Harmon; Ryan M. Girts; Jason I. Pagan; Gabriela Rodriguez; Matt S. Stock (Experimental Brain Research, 2022)

Activation-Inhibition dynamics of the oscillatory bursts of the human EEG during resting state. The macroscopic temporal range of few seconds - Carlos M. Gómez; Brenda Y. Angulo-Ruíz; Vanesa Muñoz; Elena I. Rodriguez-Martínez (Cognitive Neurodynamics, 2022)
The ubiquitous brain oscillations occur in bursts of oscillatory activity. The present report tries to define the statistical characteristics of electroencephalographical (EEG) bursts of oscillatory activity during resting state in humans to define (i) the statistical properties of amplitude and duration of oscillatory bursts, (ii) its possible correlation, (iii) its frequency content, and (iv) the presence or not of a fixed threshold to trigger an oscillatory burst. The open eyes EEG recordings of five subjects with no artifacts were selected from a sample of 40 subjects. The recordings were filtered in frequency ranges of 2 Hz wide from 1 to 99 Hz. The analytic Hilbert transform was computed to obtain the amplitude envelopes of oscillatory bursts. The criteria of thresholding and a minimum of three cycles to define an oscillatory burst were imposed. Amplitude and duration parameters were extracted and they showed durations between hundreds of milliseconds and a few seconds, and peak amplitudes showed a unimodal distribution. Both parameters were positively correlated and the oscillatory burst durations were explained by a linear model with the terms peak amplitude and peak amplitude of amplitude envelope time derivative. The frequency content of the amplitude envelope was contained in the 0–2 Hz range. The results suggest the presence of amplitude modulated continuous oscillations in the human EEG during the resting conditions in a broad frequency range, with durations in the range of few seconds and modulated positively by amplitude and negatively by the time derivative of the amplitude envelope suggesting activation-inhibition dynamics. This macroscopic oscillatory network behavior is less pronounced in the low-frequency range (1–3 Hz).

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Anthropogenic Marsh Impoundments Alter Collective Tendency in Schooling Fish - Ivan I. Rodriguez-Pinto; Guillaume Rieucau; Nils Olav Handegard; Matthew E. Kimball; Kevin M. Boswell (Estuaries and Coasts, 2022)

Increasing Vascular Response to Injury Improves Tendon Early Healing Outcome in Aged Rats - Corinne N. Riggin; Stephanie N. Weiss; Ashley B. Rodriguez; Harina Raja; Mengcun Chen; Susan M. Schultz; Chandra M. Sehgal; Louis J. Soslowsky (Annals of Biomedical Engineering, 2022)

Recent Reports on Redox Stress-Induced Mitochondrial DNA Variations, Neuroglial Interactions, and NMDA Receptor System in Pathophysiology of Schizophrenia - Narasimha M. Beeraka; Marco F. Avila-Rodriguez; Gjumrakch Aliev (Molecular Neurobiology, 2022)

Two Fish in a Pod. Mislabelling on Board Threatens Sustainability in Mixed Fisheries - Carmen Blanco-Fernandez; Karim Erzini; Sara Rodriguez-Diego; Pablo Alba-Gonzalez; Ndiaga Thiam; Fambaye Ngom Sow; Mamadou Diallo; Jónas R. Viðarsson; Duarte Fernández-Vidal; Jorge M. S. Gonçalves; Mafalda Rangel; Kim Stobberup; et al. (Frontiers in Marine Science, 2022)
Accuracy in reporting captures is a key element to achieve fisheries sustainability. However, identification of the catches might be a challenge when two or more species are morphologically similar and caught jointly, like the mixed fisheries of black hakes in East Atlantic African waters. Black hakes ( Merluccius senegalensis and M. polli ) are tough to differentiate without previous training due to their high morphological resemblance. The two species are managed as a single stock, although the biological differences between them suggest the need of a separate management. In this study, a total of 806 black hakes were visually identified by fishers on deck of fishing vessels operating in Mauritania and Senegal waters, then assigned to a species by sequencing 450bp of the Mitochondrial Control Region. Comparing the results with visual identification we found 31.4% of the total catch were incorrectly labelled on board by the fishermen. The accuracy of the fishers’ identification depended on the depth of capture and on fish size, larger individuals caught from deeper waters being more correctly assigned to M. polli . Mislabelling biased to M. polli suggests that M . senegalensis , already catalogued as endangered, is being underreported, which could endanger the conservation of this species and threaten the sustainability of black hake fisheries. Our results highlight the need for separate evaluation of the stocks in mixed fisheries for morphologically similar fish. Thus, monitoring through DNA barcoding in the very first step of the seafood chain surveys would improve accurate species delimitation and reduce its impact on the correct assessment of the stocks.

Mesenchymal Stromal Cell‐derived Extracellular Vesicles in Preclinical Animal Models of Tumor Growth: Systematic Review and Meta‐analysis - Adrian J.M. Bailey; Alvin Tieu; Manika Gupta; Mitchell Slobodian; Risa Shorr; Tim Ramsay; Rosendo A. Rodriguez; Dean A. Fergusson; Manoj M. Lalu; David S. Allan (Stem Cell Reviews and Reports, 2022)

The ligand-to-metal charge transfer excited state of [Re(dmpe)3]2+ - Tayliz M. Rodriguez; Mawuli Deegbey; Elena Jakubikova; Jillian L. Dempsey (Photosynthesis Research, 2022)

Degradation of dibutyl phthalate by Paenarthrobacter sp. Shss isolated from Saravan landfill, Hyrcanian Forests, Iran - S. Shariati; C. Ebenau-Jehle; A. A. Pourbabaee; H. A. Alikhani; M. Rodriguez-Franco; M. Agne; M. Jacoby; R. Geiger; F. Shariati; M. Boll (Biodegradation, 2022)
Phthalic acid esters are predominantly used as plasticizers and are industrially produced on the million ton scale per year. They exhibit endocrine-disrupting, carcinogenic, teratogenic, and mutagenic effects on wildlife and humans. For this reason, biodegradation, the major process of phthalic acid ester elimination from the environment, is of global importance. Here, we studied bacterial phthalic acid ester degradation at Saravan landfill in Hyrcanian Forests, Iran, an active disposal site with 800 tons of solid waste input per day. A di- n -butyl phthalate degrading enrichment culture was established from which Paenarthrobacter sp. strain Shss was isolated. This strain efficiently degraded 1 g L –1 di- n -butyl phthalate within 15 h with a doubling time of 5 h. In addition, dimethyl phthalate, diethyl phthalate, mono butyl phthalate, and phthalic acid where degraded to CO 2 , whereas diethyl hexyl phthalate did not serve as a substrate. During the biodegradation of di- n -butyl phthalate, mono- n -butyl phthalate was identified in culture supernatants by ultra-performance liquid chromatography coupled to electrospray ionization quadrupole time-of-flight mass spectrometry. In vitro assays identified two cellular esterase activities that converted di- n -butyl phthalate to mono- n -butyl phthalate, and the latter to phthalic acid, respectively. Our findings identified Paenarthrobacter sp. Shss amongst the most efficient phthalic acid esters degrading bacteria known, that possibly plays an important role in di- n -butyl phthalate elimination at a highly phthalic acid esters contaminated landfill.

Spatial and Short-Term Temporal Patterns of Octocoral Assemblages in the West Philippine Sea - Jue Alef A. Lalas; Romina Therese S. Lim; Joey P. Cabasan; Christine S. Segumalian; Rhea Mae A. Luciano; Darryl Anthony M. Valino; Melchor R. Jacinto; Hazel O. Arceo; Maria Vanessa Baria-Rodriguez (Frontiers in Marine Science, 2022)
Octocorals are relatively understudied than other coral reef organisms despite their ecological and economic values. The Philippines is known to have high marine biodiversity, but information on octocorals is lacking. This study investigated spatial and temporal variations in the assemblage of octocorals in selected reef sites in the West Philippine Sea (WPS)- the Kalayaan Island Group (i.e., Pag-asa, Sabina, Lawak, and Northeast Investigator) and Ulugan in 2017 and 2019. Results showed high octocoral taxonomic richness (at least 10 families) in the study sites. Mean percent octocoral cover in WPS was 5.35% SE ± 0.55, with Sabina having the highest octocoral cover in both years. Significant differences in octocoral cover were observed among sites in both years, but among-station differences were only observed in 2017. Octocoral assemblage also differed among sites in both years (ANOSIM: R > 0.5, p < 0.05), wherein different octocoral taxa dominated in different sites. In particular, variations were driven by high cover of holaxonians, nephtheids, and coelogorgiids in Sabina, and clavulariids, tubiporiids, and xeniids in Northeast Investigator in 2017. In 2019, significant variations were driven by high cover of helioporiids in Pag-asa, while Sabina had higher abundance of holaxonians, nephtheids, alcyoniids, and xeniids. Short-term temporal variation on octocoral cover in monitoring stations in Pag-asa was not observed (Kruskal-Wallis, p > 0.05), although the overall mean octocoral cover increased from 1.23% ± SE 0.47 in 2017 to 2.09% SE ± 0.37 in 2019. Further, there was no significant change in the octocoral assemblage in Pag-asa between years (ANOSIM, R = 0.11, p = 0.07). This study highlights high octocoral taxonomic richness in the WPS relative to other sites in the Indo-Pacific Region and provides baseline information on the octocoral assemblages, which can be useful for future ecological studies and marine biodiversity conservation efforts.

Antidepressant activity of pharmacological and genetic deactivation of the small-conductance calcium-activated potassium channel subtype-3 - Mina G. Nashed; Shannon Waye; S. M. Nageeb Hasan; Diana Nguyen; Micaela Wiseman; Jing Zhang; Harry Lau; O. Chandani Dinesh; Roger Raymond; Iain R. Greig; Francis Rodriguez Bambico; José N. Nobrega (Psychopharmacology, 2022)

A Comprehensive, FAIR File Format for Neuroanatomical Structure Modeling - A. E. Sullivan; S. J. Tappan; P. J. Angstman; A. Rodriguez; G. C. Thomas; D. M. Hoppes; M. A. Abdul-Karim; M. L. Heal; Jack R. Glaser (Neuroinformatics, 2022)
With advances in microscopy and computer science, the technique of digitally reconstructing, modeling, and quantifying microscopic anatomies has become central to many fields of biological research. MBF Bioscience has chosen to openly document their digital reconstruction file format, the Neuromorphological File Specification, available at www.mbfbioscience.com/filespecification (Angstman et al., 2020). The format, created and maintained by MBF Bioscience, is broadly utilized by the neuroscience community. The data format’s structure and capabilities have evolved since its inception, with modifications made to keep pace with advancements in microscopy and the scientific questions raised by worldwide experts in the field. More recent modifications to the neuromorphological file format ensure it abides by the Findable, Accessible, Interoperable, and Reusable (FAIR) data principles promoted by the International Neuroinformatics Coordinating Facility (INCF; Wilkinson et al., Scientific Data, 3 , 160018,, 2016). The incorporated metadata make it easy to identify and repurpose these data types for downstream applications and investigation. This publication describes key elements of the file format and details their relevant structural advantages in an effort to encourage the reuse of these rich data files for alternative analysis or reproduction of derived conclusions.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Symbiont shuffling induces differential DNA methylation responses to thermal stress in the coral Montastraea cavernosa - Javier A. Rodriguez‐Casariego; Ross Cunning; Andrew C. Baker; Jose M. Eirin‐Lopez (Molecular Ecology, 2022)
Algal symbiont shuffling in favour of more thermotolerant species has been shown to enhance coral resistance to heat‐stress. Yet, the mechanistic underpinnings and long‐term implications of these changes are poorly understood. This work studied the modifications in coral DNA methylation, an epigenetic mechanism involved in coral acclimatization, in response to symbiont manipulation and subsequent heat stress exposure. Symbiont composition was manipulated in the great star coral Montastraea cavernosa through controlled thermal bleaching and recovery, producing paired ramets of three genets dominated by either their native symbionts (genus Cladocopium ) or the thermotolerant species ( Durusdinium trenchi ). Single‐base genome‐wide analyses showed significant modifications in DNA methylation concentrated in intergenic regions, introns and transposable elements. Remarkably, DNA methylation changes in response to heat stress were dependent on the dominant symbiont, with twice as many differentially methylated regions found in heat‐stressed corals hosting different symbionts ( Cladocopium vs. D . trenchii ) compared to all other comparisons. Interestingly, while differential gene body methylation was not correlated with gene expression, an enrichment in differentially methylated regions was evident in repetitive genome regions. Overall, these results suggest that changes in algal symbionts favouring heat tolerant associations are accompanied by changes in DNA methylation in the coral host. The implications of these results for coral adaptation, along with future avenues of research based on current knowledge gaps, are discussed in the present work.

Variable response of Red Sea coral communities to recent disturbance events along a latitudinal gradient - Nicholas M. Hammerman; Alberto Rodriguez-Ramirez; Timothy L. Staples; Thomas M. DeCarlo; Vincent Saderne; George Roff; Nicole Leonard; Jian-xin Zhao; Susann Rossbach; Michelle N. Havlik; Carlos M. Duarte; John M. Pandolfi (Marine Biology, 2021)

NGS and phenotypic ontology-based approaches increase the diagnostic yield in syndromic retinal diseases - I. Perea-Romero; F. Blanco-Kelly; I. Sanchez-Navarro; I. Lorda-Sanchez; S. Tahsin-Swafiri; A. Avila-Fernandez; I. Martin-Merida; M. J. Trujillo-Tiebas; R. Lopez-Rodriguez; M. Rodriguez de Alba; I. F. Iancu; R. Romero; et al. (Human Genetics, 2021)
Syndromic retinal diseases (SRDs) are a group of complex inherited systemic disorders, with challenging molecular underpinnings and clinical management. Our main goal is to improve clinical and molecular SRDs diagnosis, by applying a structured phenotypic ontology and next-generation sequencing (NGS)-based pipelines. A prospective and retrospective cohort study was performed on 100 probands with an a priori diagnosis of non-Usher SRDs, using available clinical data, including Human Phenotype Ontology annotation, and further classification into seven clinical categories (ciliopathies, specific syndromes and five others). Retrospective molecular diagnosis was assessed using different molecular and bioinformatic methods depending on availability. Subsequently, uncharacterized probands were prospectively screened using other NGS approaches to extend the number of analyzed genes. After phenotypic classification, ciliopathies were the most common SRD (35%). A global characterization rate of 52% was obtained, with six cases incompletely characterized for a gene that partially explained the phenotype. An improved characterization rate was achieved addressing prospective cases (83%) and well-recognizable syndrome (62%) subgroups. The 27% of the fully characterized cases were reclassified into a different clinical category after identification of the disease-causing gene. Clinical-exome sequencing is the most appropriate first-tier approach for prospective cases, whereas whole-exome sequencing and bioinformatic reanalysis increases the diagnosis of uncharacterized retrospective cases to 45%, mostly those with unspecific symptoms. Our study describes a comprehensive approach to SRDs in daily clinical practice and the importance of thorough clinical assessment and selection of the most appropriate molecular test to be used to solve these complex cases and elucidate novel associations.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Practical evaluation of single-frequency dGNSS for monitoring slow-moving landslides - Rodriguez J; Deane E; Hendry M. T; Macciotta R; Evans T; Gräpel C; Skirrow R (Landslides, 2021)

Spontaneously fermented traditional beverages as a source of bioactive compounds: an overview - R. B. Cuvas-Limon; Clarisse Nobre; Mario Cruz; Rosa M. Rodriguez-Jasso; Héctor A. Ruíz; Araceli Loredo-Treviño; J. A. Texeira; Ruth Belmares (Critical Reviews in Food Science and Nutrition, 2021)

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Chemical composition of Schinus areira essential oil and antimicrobial action against Staphylococcus aureus - Andrea C. Cutro; M. Victoria Castelli; Silvia N. López; Manuel A. Rosales; Axel Hollmann; Sergio A. Rodriguez (Natural Product Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Evidence of A tlantic bluefin tuna spawning in the B ay of B iscay, north‐eastern A tlantic - Jose M. Rodriguez; Carolina Johnstone; Diego Lozano‐Peral (Journal of Fish Biology, 2021)
The spawning grounds of the Atlantic bluefin tuna ( Thunnus thynnus ) are traditionally considered to be the Gulf of Mexico (Gulf of Mexico) and the Mediterranean Sea (Mediterranean Sea). However, for the western Atlantic, unequivocal evidence of bluefin spawning outside the Gulf of Mexico has been shown. In this study we present the first records of genetically confirmed bluefin larvae in the southern Bay of Biscay (eastern Atlantic). These findings provide evidence of bluefin spawning activity outside the Mediterranean Sea, in the north‐eastern Atlantic. However, our results suggest that the bluefin spawning in the Bay of Biscay is a sporadic phenomenon.

An Economic Perspective on Policies to Save the Vaquita: Conservation Actions, Wildlife Trafficking, and the Structure of Incentives - Enrique Sanjurjo-Rivera; Sarah L. Mesnick; Sara Ávila-Forcada; Oriana Poindexter; Rebecca Lent; Vanda Felbab-Brown; Andrés M. Cisneros-Montemayor; Dale Squires; U. Rashid Sumaila; Gordon Munro; Rafael Ortiz-Rodriguez; Ramses Rodriguez; et al. (Frontiers in Marine Science, 2021)
The Upper Gulf of California is a diverse and highly productive ecosystem supporting some of the most important fisheries in Mexico, yet a history of weak fisheries management and illegal fishing threaten the area’s biodiversity and undermine human well-being in the communities along its shores. The vaquita ( Phocoena sinus) is endemic to these waters and is on the brink of extinction due to incidental entanglement in gillnets used by small-scale fishers. The resurgence of an illegal gillnet fishery for totoaba ( Totoaba macdonaldi ), whose swim bladders are highly prized in Hong Kong and continental China, has accelerated the steep decline of the vaquita population. Vaquita is one of a growing number of cases linking illegal wildlife trade, organized crime, and biodiversity decline. This paper provides a summary of key reflections of a panel of fisheries economists gathered at the ninth forum of the North American Association of Fisheries Economists (NAAFE) to evaluate the policies implemented in the Upper Gulf through an economic lens and updated to reflect more recent developments. The panel recognized that poor fisheries management, lack of effective enforcement, distant demand for an illegal product, corruption, and few viable economic alternatives confound efforts to address vaquita bycatch. The complexity of these problems requires a holistic, multidisciplinary approach, combining top-down, direct regulation and bottom-up, participatory and incentive-based instruments. Addressing chronic deficiencies in enforcement, particularly in the very small area where the remaining vaquitas are found, is crucial to prevent imminent extinction. Equally crucial are sustained actions to support legal fishers able to make a good living – with a direct stake in healthy marine ecosystems – as key components of policies to address bycatch and reduce wildlife trafficking. The situation in the Upper Gulf of California is dire, yet similar threats to other marine mammals and wildlife trafficked species may benefit from the experience of the vaquita.

Nutritional and ecotoxicological aspects of the acidotolerant alga Keratococcus rhaphidioides (Chlorophyta): a potential candidate for algal mediated bioremediation of extremely acidic waters - J. M. Cabrera; S. S. Schultz; G. D. Baffico; M. C. Rodriguez; F. L. Pedrozo; M. M. Diaz (Journal of Applied Phycology, 2021)

Fine-scale time series surveys reveal new insights into spatio-temporal trends in coral cover (2002–2018), of a coral reef on the Southern Great Barrier Reef - Chris Roelfsema; Eva M. Kovacs; Julie Vercelloni; Kathryn Markey; Alberto Rodriguez-Ramirez; Sebastian Lopez-Marcano; Manuel Gonzalez-Rivero; Ove Hoegh-Guldberg; Stuart R. Phinn (Coral Reefs, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

An intrapopulational study of organic compounds and biomechanical properties of the shell of the Antarctic bivalve Laternula elliptica (P. P. King, 1832) at King George Island - M. Roberto García-Huidobro; María Josefina Poupin; Cristóbal Urrutia; Alejandro B. Rodriguez-Navarro; Christian Grenier; Juan F. Vivanco; Laura Ramajo; Isabel Benjumeda; Nelson A. Lagos; Marco A. Lardies (Polar Biology, 2021)

Cyclodextrins: a tool in plant cell and organ culture bioprocesses for the production of secondary metabolites - A. B. Cardillo; M. Perassolo; A. M. Giulietti; Julian Rodriguez Talou (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Gene Expression Response to Stony Coral Tissue Loss Disease Transmission in M. cavernosa and O. faveolata From Florida - Nikki Traylor-Knowles; Michael T. Connelly; Benjamin D. Young; Katherine Eaton; Erinn M. Muller; Valerie J. Paul; Blake Ushijima; Allyson DeMerlis; Melissa K. Drown; Ashley Goncalves; Nicholas Kron; Grace A. Snyder; et al. (Frontiers in Marine Science, 2021)
Since 2014, corals within Florida’s Coral Reef have been dying at an unprecedented rate due to stony coral tissue loss disease (SCTLD). Here we describe the transcriptomic outcomes of three different SCTLD transmission experiments performed at the Smithsonian Marine Station and Mote Marine Laboratory between 2019 and 2020 on the corals Orbicella faveolata and Montastraea cavernosa. Overall, diseased O. faveolata had 2194 differentially expressed genes (DEGs) compared with healthy colonies, whereas diseased M. cavernosa had 582 DEGs compared with healthy colonies. Many significant DEGs were implicated in immunity, extracellular matrix rearrangement, and apoptosis. These included, but not limited to, peroxidases, collagens, Bax-like, fibrinogen-like, protein tyrosine kinase, and transforming growth factor beta. A gene module was identified that was significantly correlated to disease transmission. This module possessed many apoptosis and immune genes with high module membership indicating that a complex apoptosis and immune response is occurring in corals during SCTLD transmission. Overall, we found that O. faveolata and M. cavernosa exhibit an immune, apoptosis, and tissue rearrangement response to SCTLD. We propose that future studies should focus on examining early time points of infection, before the presence of lesions, to understand the activating mechanisms involved in SCTLD.

Comparison of real and simulated lava flows in the Holocene volcanism of Gran Canaria (Canary Islands, Spain) with Q-LavHA: contribution to volcanic hazard management - A. Rodriguez-Gonzalez; M. Aulinas; S. Mossoux; F. J. Perez-Torrado; J. L. Fernandez-Turiel; M. Cabrera; C. Prieto-Torrell (Natural Hazards, 2021)

Correction to: Impact of acute high‑intensity interval exercise on plasma pentraxin 3 and endothelial function in obese individuals—a pilot study - Aaron L. Slusher; Brandon G. Fico; Katelyn M. Dodge; Ryan S. Garten; Peter J. Ferrandi; Alexandra A. Rodriguez; Gabriel Pena; Chun-Jung Huang (European Journal of Applied Physiology, 2021)

Impact of acute high-intensity interval exercise on plasma pentraxin 3 and endothelial function in obese individuals—a pilot study - Aaron L. Slusher; Brandon G. Fico; Katelyn M. Dodge; Ryan S. Garten; Peter J. Ferrandi; Alexandra A. Rodriguez; Gabriel Pena; Chun-Jung Huang (European Journal of Applied Physiology, 2021)

Managing groundwater supplies subject to drought: perspectives on current status and future priorities from England (UK) - M. J. Ascott; J. P. Bloomfield; I. Karapanos; C. R. Jackson; R. S. Ward; A. B. McBride; B. Dobson; N. Kieboom; I. P. Holman; A. F. Van Loon; E. J. Crane; B. Brauns; et al. (Hydrogeology Journal, 2021)
Effective management of groundwater resources during drought is essential. How is groundwater currently managed during droughts, and in the face of environmental change, what should be the future priorities? Four themes are explored, from the perspective of groundwater management in England (UK): (1) integration of drought definitions; (2) enhanced fundamental monitoring; (3) integrated modelling of groundwater in the water cycle; and (4) better information sharing. Whilst these themes are considered in the context of England, globally, they are relevant wherever groundwater is affected by drought.

Agroecological practices to support tropical livestock farming systems: a Caribbean and Latin American perspective - Gisele Alexandre; Lylian Rodriguez; Javier Arece; José Delgadillo; Gary Wayne Garcia; Kurt Habermeier; André M. Almeida; Audrey Fanchone; Jean-Luc Gourdine; Harry Archimède (Tropical Animal Health and Production, 2021)

The current situation and future perspectives of Quercus ilex and Pinus halepensis afforestation on agricultural land in Spain under climate change scenarios - L. Quinto; Rafael M. Navarro-Cerrillo; Guillermo Palacios-Rodriguez; F. Ruiz-Gómez; J. Duque-Lazo (New Forests, 2021)

Using a biophysical model to investigate connectivity between spawning grounds and nursery areas of King George whiting ( Sillaginodes punctatus : Perciformes) in South Australia’s gulfs - Troy A. Rogers; Ana Redondo Rodriguez; Anthony J. Fowler; Mark J. Doubell; Michael J. Drew; Michael A. Steer; Damian Matthews; Charles James; Bronwyn M. Gillanders (Fisheries Oceanography, 2021)
Many demersal marine fish species depend on a dispersive larval stage that connects geographically discrete sub‐populations. Understanding connectivity between these sub‐populations is necessary to determine stock structure, which identifies the appropriate spatial scale for fishery management. Such connectivity is poorly understood for King George whiting ( Sillaginodes punctatus ; Perciformes) in South Australia's gulf system, even though spawning grounds and nursery areas are adequately defined. In response to declines in commercial catches and estimated biomass, this study aimed to determine the most important spawning grounds and nursery areas to recruitment, and the connectivity between them. A biophysical model was seeded with particles according to the distribution and density of eggs throughout the spawning area in 2017 and 2018. Despite inter‐annual differences in the origins of particles, dispersal pathways and predicted settlement areas remained consistent between years. Predicted settlement was generally highest to nursery areas only short distances from regional spawning grounds, consistent with previous hydrodynamic models. However, the model also predicted that spawning in one region could contribute to recruitment in an adjacent region later in the spawning season, which aligned with the breakdown of thermohaline fronts at the entrance of each gulf. The connectivity between spawning grounds and nursery areas predicted by the model is supported by spatio‐temporal patterns in the otolith chemistry of pre‐flexion larvae and settled juveniles. Consequently, the most parsimonious explanation is that the populations of King George whiting in South Australia's gulf system constitute a single, panmictic stock, which has implications for fishery management.

Cross-ecosystem impacts of non-native ungulates on wetland communities - Luciana Motta; M. Noelia Barrios-Garcia; Sebastián A. Ballari; Mariano A. Rodriguez-Cabal (Biological Invasions, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Dynamics of volatilomes emitted during cross-talking of plant-growth-promoting bacteria and the phytopathogen, Fusarium solani - A. Gutiérrez-Santa Ana; H. A. Carrillo-Cerda; J. Rodriguez-Campos; J. B. Velázquez-Fernández; O. A. Patrón-Soberano; S. M. Contreras-Ramos (World Journal of Microbiology and Biotechnology, 2020)

Correction to: Reef-associated fishes have more maneuverable body shapes at a macroevolutionary scale - Olivier Larouche; Bailey Benton; Katherine A. Corn; Sarah T. Friedman; Dominique Gross; Mikayla Iwan; Brian Kessler; Christopher M. Martinez; Sierra Rodriguez; Hannah Whelpley; Peter C. Wainwright; Samantha A. Price (Coral Reefs, 2020)

Reef-associated fishes have more maneuverable body shapes at a macroevolutionary scale - Olivier Larouche; Bailey Benton; Katherine A. Corn; Sarah T. Friedman; Dominique Gross; Mikayla Iwan; Brian Kessler; Christopher M. Martinez; Sierra Rodriguez; Hannah Whelpley; Peter C. Wainwright; Samantha A. Price (Coral Reefs, 2020)

Tacit working models of human behavioural change II: Farmers’ folk theories of conservation programme design - M. Root-Bernstein; A. Bondoux; M. Guerrero-Gatica; F. Zorondo-Rodriguez (Ambio, 2020)

Amphetamine-induced striatal dopamine release in schizotypal personality disorder - Judy L. Thompson; Daniel R. Rosell; Mark Slifstein; Xiaoyan Xu; Ethan G. Rothstein; Yosefa A. Modiano; Lawrence S. Kegeles; Harold W. Koenigsberg; Antonia S. New; Erin A. Hazlett; Margaret M. McClure; M. Mercedes Perez-Rodriguez; et al. (Psychopharmacology, 2020)

UAVs for monitoring, investigation, and mitigation design of a rock slope with multiple failure mechanisms—a case study - J. Rodriguez; R. Macciotta; M. T. Hendry; M. Roustaei; C. Gräpel; R. Skirrow (Landslides, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Phytoplasma Infection of Cranberry Affects Development and Oviposition, but Not Host-Plant Selection, of the Insect Vector Limotettix vaccinii - Nakorn Pradit; Mark C. Mescher; Consuelo M. De Moraes; Cesar Rodriguez-Saona (Journal of Chemical Ecology, 2020)

Iterative subtractive binning of freshwater chronoseries metagenomes identifies over 400 novel species and their ecologic preferences - Luis M. Rodriguez‐R; Despina Tsementzi; Chengwei Luo; Konstantinos T. Konstantinidis (Environmental Microbiology, 2020)
Summary Recent advances in sequencing technology and bioinformatic pipelines have allowed unprecedented access to the genomes of yet‐uncultivated microorganisms from diverse environments. However, the catalogue of freshwater genomes remains limited, and most genome recovery attempts in freshwater ecosystems have only targeted specific taxa. Here, we present a genome recovery pipeline incorporating iterative subtractive binning, and apply it to a time series of 100 metagenomic datasets from seven connected lakes and estuaries along the Chattahoochee River (Southeastern USA). Our set of metagenome‐assembled genomes (MAGs) represents >400 yet‐unnamed genomospecies, substantially increasing the number of high‐quality MAGs from freshwater lakes. We propose names for two novel species: ‘ Candidatus Elulimicrobium humile’ (‘ Ca . Elulimicrobiota’, ‘Patescibacteria’) and ‘ Candidatus Aquidulcis frankliniae’ (‘Chloroflexi’). Collectively, our MAGs represented about half of the total microbial community at any sampling point. To evaluate the prevalence of these genomospecies in the chronoseries, we introduce methodologies to estimate relative abundance and habitat preference that control for uneven genome quality and sample representation. We demonstrate high degrees of habitat‐specialization and endemicity for most genomospecies in the Chattahoochee lakes. Wider ecological ranges characterized smaller genomes with higher coding densities, indicating an overall advantage of smaller, more compact genomes for cosmopolitan distributions.

The Effect of Short-Term Physical Activity on the Oxidative Stress in Rats with Different Stress Resistance Profiles in Cerebral Hypoperfusion - Vladimir V. Chrishtop; Irina K. Tomilova; Tatiana A. Rumyantseva; Elizaveta V. Mikhaylenko; Marco F. Avila-Rodriguez; Liudmila M. Mikhaleva; Vladimir N. Nikolenko; Siva G. Somasundaram; Cecil E. Kirkland; Sergey O. Bachurin; Gjumrakch Aliev (Molecular Neurobiology, 2020)

An NMR Protocol for In Vitro Paclitaxel Release from an Albumin-Bound Nanoparticle Formulation - Min Sung Suh; Sharadrao M. Patil; Darby Kozak; Eric Pang; Stephanie Choi; Xiaohui Jiang; Jason D. Rodriguez; David A. Keire; Kang Chen (AAPS PharmSciTech, 2020)

Hydrodynamics of Biomimetic Marine Propulsion and Trends in Computational Simulations - M. I. Lamas; C. G. Rodriguez (Journal of Marine Science and Engineering, 2020)
The aim of the present paper is to provide the state of the works in the field of hydrodynamics and computational simulations to analyze biomimetic marine propulsors. Over the last years, many researchers postulated that some fish movements are more efficient and maneuverable than traditional rotary propellers, and the most relevant marine propulsors which mimic fishes are shown in the present work. Taking into account the complexity and cost of some experimental setups, numerical models offer an efficient, cheap, and fast alternative tool to analyze biomimetic marine propulsors. Besides, numerical models provide information that cannot be obtained using experimental techniques. Since the literature about trends in computational simulations is still scarce, this paper also recalls the hydrodynamics of the swimming modes occurring in fish and summarizes the more relevant lines of investigation of computational models.

Three-dimensional regional bi-ventricular shape remodeling is associated with exercise capacity in endurance athletes - G. Bernardino; M. Sanz de la Garza; B. Domenech-Ximenos; S. Prat-Gonzàlez; R. J. Perea; I. Blanco; F. Burgos; A. Sepulveda-Martinez; M. Rodriguez-Lopez; F. Crispi; C. Butakoff; M. A. González Ballester; et al. (European Journal of Applied Physiology, 2020)

A Metabolic Intravascular Platform to Study FDG Uptake in Vascular Injury - F. Franchi; M. Olthoff; J. Krier; C. Noble; M. Al-Hijji; V. Ramaswamy; T. Witt; M. Burke; M. Benscoter; A. Lerman; G. S. Sandhu; M. Rodriguez-Porcel (Cardiovascular Engineering and Technology, 2020)

Genome repository of oil systems: An interactive and searchable database that expands the catalogued diversity of crude oil‐associated microbes - Smruthi Karthikeyan; Luis M. Rodriguez‐R; Patrick Heritier‐Robbins; Janet K. Hatt; Markus Huettel; Joel E. Kostka; Konstantinos T. Konstantinidis (Environmental Microbiology, 2020)
Summary Microbial communities ultimately control the fate of petroleum hydrocarbons (PHCs) that enter the natural environment, but the interactions of microbes with PHCs and the environment are highly complex and poorly understood. Genome‐resolved metagenomics can help unravel these complex interactions. However, the lack of a comprehensive database that integrates existing genomic/metagenomic data from oil environments with physicochemical parameters known to regulate the fate of PHCs currently limits data analysis and interpretations. Here, we curated a comprehensive, searchable database that documents microbial populations in natural oil ecosystems and oil spills, along with available underlying physicochemical data, geocoded via geographic information system to reveal their geographic distribution patterns. Analysis of the ~2000 metagenome‐assembled genomes (MAGs) available in the database revealed strong ecological niche specialization within habitats. Over 95% of the recovered MAGs represented novel taxa underscoring the limited representation of cultured organisms from oil‐contaminated and oil reservoir ecosystems. The majority of MAGs linked to oil‐contaminated ecosystems were detectable in non‐oiled samples from the Gulf of Mexico but not in comparable samples from elsewhere, indicating that the Gulf is primed for oil biodegradation. The repository should facilitate future work toward a predictive understanding of the microbial taxa and their activities that control the fate of oil spills.

Ecogenomics of the SAR11 clade - Jose M. Haro‐Moreno; Francisco Rodriguez‐Valera; Riccardo Rosselli; Francisco Martinez‐Hernandez; Juan J. Roda‐Garcia; Monica Lluesma Gomez; Oscar Fornas; Manuel Martinez‐Garcia; Mario López‐Pérez (Environmental Microbiology, 2020)
Summary Members of the SAR11 clade, despite their high abundance, are often poorly represented by metagenome‐assembled genomes. This fact has hampered our knowledge about their ecology and genetic diversity. Here we examined 175 SAR11 genomes, including 47 new single‐amplified genomes. The presence of the first genomes associated with subclade IV suggests that, in the same way as subclade V, they might be outside the proposed Pelagibacterales order. An expanded phylogenomic classification together with patterns of metagenomic recruitment at a global scale have allowed us to define new ecogenomic units of classification (genomospecies), appearing at different, and sometimes restricted, metagenomic data sets. We detected greater microdiversity across the water column at a single location than in samples collected from similar depth across the global ocean, suggesting little influence of biogeography. In addition, pangenome analysis revealed that the flexible genome was essential to shape genomospecies distribution. In one genomospecies preferentially found within the Mediterranean, a set of genes involved in phosphonate utilization was detected. While another, with a more cosmopolitan distribution, was unique in having an aerobic purine degradation pathway. Together, these results provide a glimpse of the enormous genomic diversity within this clade at a finer resolution than the currently defined clades.

Effects of the Invasion of Honey Locust (Gleditsia triacanthos L.) on Macrophytes and Algae of Pampean Streams (Argentina) - C. Vilches; A. M. Torremorell; M. C. Rodriguez Castro; A. Giorgi (Wetlands, 2020)

Tryptophan supplementation helps totoaba (Totoaba macdonaldi) juveniles to regain homeostasis in high-density culture conditions - Miguel Cabanillas-Gámez; Ulises Bardullas; Mario A Galaviz; Sergio Rodriguez; Verónica M Rodriguez; Lus M López (Fish Physiology and Biochemistry, 2020)

Sexual recombination within the “Kranich” race of the yellow rust fungus Puccinia striiformis f.sp. tritici on Berberis vulgaris - J. Rodriguez-Algaba; M. S. Hovmøller; A. F. Justesen (European Journal of Plant Pathology, 2020)

Metabolomic analysis of Lavandula dentata L. and Lavandula stoechas L. extracts by LC-QTOF/MS experiments and multivariate analysis techniques as a chemotaxonomical tool - José Pérez-del Palacio; Caridad Díaz-Navarro; Ariadna Martín-Blázquez; Carmen González-Olmedo; Noemí Vergara-Segura; Francesca Algieri; Alba Rodriguez-Nogales; M. Reyes González-Tejero; Manuel Casares-Porcel; Joaquín Molero-Mesa; M. Elena Rodríguez-Cabezas; Olga Genilloud; et al. (Plant Biosystems, 2020)

Low-density open-cell flexible polyolefin foams as efficient materials for oil absorption: influence of tortuosity on oil absorption - E. Lopez-Gonzalez; C. Saiz-Arroyo; M. A. Rodriguez-Perez (International Journal of Environmental Science and Technology, 2020)

Dense Mytilus Beds Along Freshwater-Influenced Greenland Shores: Resistance to Corrosive Waters Under High Food Supply - Carlos M. Duarte; Alejandro B. Rodriguez-Navarro; Antonio Delgado-Huertas; Dorte Krause-Jensen (Estuaries and Coasts, 2020)

Environmental plasticity and colonisation history in the Atlantic salmon microbiome: A translocation experiment - Tamsyn M. Uren Webster; Deiene Rodriguez‐Barreto; Giovanni Castaldo; Peter Gough; Sofia Consuegra; Carlos Garcia de Leaniz (Molecular Ecology, 2020)
Microbial communities associated with the gut and the skin are strongly influenced by environmental factors, and can rapidly adapt to change. Historical processes may also affect the microbiome. In particular, variation in microbial colonisation in early life has the potential to induce lasting effects on microbial assemblages. However, little is known about the relative extent of microbiome plasticity or the importance of historical colonisation effects following environmental change, especially for nonmammalian species. To investigate this we performed a reciprocal translocation of Atlantic salmon between artificial and semi‐natural conditions. Wild and hatchery‐reared fry were transferred to three common garden experimental environments for 6 weeks: standard hatchery conditions, hatchery conditions with an enriched diet, and simulated wild conditions. We characterized the faecal and skin microbiome of individual fish before and after the environmental translocation, using a BACI (before‐after‐control‐impact) design. We found evidence of extensive microbiome plasticity for both the gut and skin, with the greatest changes in alpha and beta diversity associated with the largest changes in environment and diet. Microbiome richness and diversity were entirely determined by environment, with no detectable effects of fish origin, and there was also a near‐complete turnover in microbiome structure. However, we also identified, for the first time in fish, evidence of historical colonisation effects reflecting early‐life experience, including ASVs characteristic of captive rearing. These results have important implications for host adaptation to local selective pressures, and highlight how conditions experienced during early life can have a long‐term influence on the microbiome and, potentially, host health.

Evaluating the performance of freshwater macroalgae in the bioremediation of nutrient-enriched water in temperate environments - J. M. Valero-Rodriguez; S. E. Swearer; T. Dempster; R. de Nys; A. J. Cole (Journal of Applied Phycology, 2020)

SPEXOR passive spinal exoskeleton decreases metabolic cost during symmetric repetitive lifting - S. J. Baltrusch; J. H. van Dieën; A. S. Koopman; M. B. Näf; C. Rodriguez-Guerrero; J. Babič; H. Houdijk (European Journal of Applied Physiology, 2020)

Adsorption of Diclofenac from Aqueous Solution onto Carbon Xerogels: Effect of Synthesis Conditions and Presence of Bacteria - A. I. Moral-Rodriguez; R. Leyva-Ramos; F. Carrasco-Marín; M. I. Bautista-Toledo; A. F. Pérez-Cadenas (Water, Air, & Soil Pollution, 2020)

Target of rapamycin signaling is tightly and differently regulated in the plant response under distinct abiotic stresses - Cintia M. Pereyra; Néstor R. Aznar; Marianela S. Rodriguez; Graciela L. Salerno; Giselle M. A. Martínez-Noël (Planta, 2020)

Phylogenetic placement of Leptosphaeria polylepidis, a pathogen of Andean endemic Polylepis tarapacana, and its newly discovered mycoparasite Sajamaea mycophila gen. et sp. nov. - Marcin Piątek; Pamela Rodriguez-Flakus; Alejandra Domic; Arely N. Palabral-Aguilera; M. Isabel Gómez; Adam Flakus (Mycological Progress, 2020)
Polylepis tarapacana forms one of the highest-altitude woodlands worldwide. Its populations are experiencing a decline due to unsustainable land-use practices, climate change, and fungal infection. In Sajama National Park in Bolivia, Polylepis tarapacana is affected by a disease caused by the pleosporalean fungus Leptosphaeria polylepidis , recently described in 2005. In this study, the integrative morphological and molecular analyses using sequences from multiple DNA loci showed that it belongs to the genus Paraleptosphaeria (Leptosphaeriaceae, Pleosporales). Accordingly, the appropriate new combination, Paraleptosphaeria polylepidis , is made. Pseudothecia of Pa. polylepidis were found to be overgrown by enigmatic conidiomata that were not reported in the original description of this fungus. Morphological and molecular analyses using sequences from two DNA loci revealed that they belong to an undescribed genus and species in the family Dictyosporiaceae (Pleosporales). The new generic and specific names, Sajamaea and S. mycophila , are introduced for this unusual fungus.

Health and lifestyle behaviors in colorectal cancer survivors with and without Lynch syndrome - Kirsten M. Donato; Katelyn Moore; Wendy M. Parker; Susan K. Peterson; Ellen R. Gritz; Christopher I. Amos; Karen H. Lu; Patrick M. Lynch; Miguel A. Rodriguez-Bigas; Y. Nancy You; Allison M. Burton-Chase (Journal of Community Genetics, 2020)

Development of a Co2+/PMS process involving target contaminant degradation and PMS decomposition - O. M. Rodriguez-Narvaez; M. O. A. Pacheco-Alvarez; K. Wróbel; J. Páramo-Vargas; E. R. Bandala; E. Brillas; J. M. Peralta-Hernandez (International Journal of Environmental Science and Technology, 2020)

A comparison of regional brain volumes and white matter connectivity in subjects with stimulant induced psychosis versus schizophrenia - Peter D. Alexander; Kristina M. Gicas; Alex Cheng; Donna J. Lang; Ric M. Procyshyn; Alexandra T. Vertinsky; William J. Panenka; Allen E. Thornton; Alexander Rauscher; Jamie Y. X. Wong; Tasha Chan; Andrea A. Jones; et al. (Psychopharmacology, 2019)

Improving Research Literacy in Diverse Minority Populations with a Novel Communication Tool - Melissa A. Simon; Rodney Haring; Elisa M. Rodriguez; Evelyn González; Judith S. Kaur; Marcie Kirschner; Laura Tom; Catherine A. O’Brian; Mira L. Katz (Journal of Cancer Education, 2019)

Metabolomic profile of cacao cell suspensions growing in blue light/dark conditions with potential in food biotechnology - Adriana M. Gallego; Luisa F. Rojas; Héctor A. Rodriguez; Conrado Mora; Lucía Atehortúa; Aura I. Urrea; Mark J. Guiltinan; Siela N. Maximova; Emmanuel Gaquerel; Martha Zuluaga; Natalia Pabón-Mora (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Availability of lead in agricultural soils amended with compost of biosolid with wood shavings and yard trimmings - Gisele V. Ferreyroa; Carolina Vergara Cid; Romina A. Verdenelli; María F. Dominchin; José M. Meriles; María L. Pignata; Judith H. Rodriguez (Environmental Science and Pollution Research, 2019)

Energy balance related lifestyle factors and risk of endometrial and colorectal cancer among individuals with lynch syndrome: a systematic review - Adriana M. Coletta; Susan K. Peterson; Leticia A. Gatus; Kate J. Krause; Susan M. Schembre; Susan C. Gilchrist; Mala Pande; Eduardo Vilar; Y. Nancy You; Miguel A. Rodriguez-Bigas; Larkin L. Strong; Patrick M. Lynch; et al. (Familial Cancer, 2019)

Non-native ungulates indirectly impact foliar arthropods but not soil function - Mariano A. Rodriguez-Cabal; M. Noelia Barrios-Garcia; Christopher J. Greyson-Gaito; Heather L. Slinn; M. Paz Tapella; Agustín Vitali; Gregory M. Crutsinger (Biological Invasions, 2019)

Defining the indigenous ranges of species to account for geographic and taxonomic variation in the history of human impacts: reply to Sanderson 2019 - P. J. Stephenson; Molly K. Grace; H. Resit Akçakaya; Ana S. L. Rodrigues; Barney Long; David P. Mallon; Erik Meijaard; Jon Paul Rodriguez; Richard P. Young; Thomas M. Brooks; Craig Hilton‐Taylor (Conservation Biology, 2019)

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Remotely Sensed Winds and Wind Stresses for Marine Forecasting and Ocean Modeling - Mark A. Bourassa; Thomas Meissner; Ivana Cerovecki; Paul S. Chang; Xiaolong Dong; Giovanna De Chiara; Craig Donlon; Dmitry S. Dukhovskoy; Jocelyn Elya; Alexander Fore; Melanie R. Fewings; Ralph C. Foster; et al. (Frontiers in Marine Science, 2019)

Phylogenomics of Enterococcus faecalis from wild birds: new insights into host‐associated differences in core and accessory genomes of the species - Ricardo León‐Sampedro; Rosa del Campo; Mercedes Rodriguez‐Baños; Val F. Lanza; María José Pozuelo; Carlos Francés‐Cuesta; Ana P. Tedim; Ana R. Freitas; Carla Novais; Luísa Peixe; Rob J. L. Willems; Jukka Corander; et al. (Environmental Microbiology, 2019)
Summary Wild birds have been suggested to be reservoirs of antimicrobial resistant and/or pathogenic Enterococcus faecalis ( Efs ) strains, but the scarcity of studies and available sequences limit our understanding of the population structure of the species in these hosts. Here, we analysed the clonal and plasmid diversity of 97 Efs isolates from wild migratory birds. We found a high diversity, with most sequence types (STs) being firstly described here, while others were found in other hosts including some predominant in poultry. We found that pheromone‐responsive plasmids predominate in wild bird Efs while 35% of the isolates entirely lack plasmids. Then, to better understand the ecology of the species, the whole genome of fivestrains with known STs (ST82, ST170, ST16 and ST55) were sequenced and compared with all the Efs genomes available in public databases. Using several methods to analyse core and accessory genomes (AccNET, PLACNET, hierBAPS and PANINI), we detected differences in the accessory genome of some lineages (e.g. ST82) demonstrating specific associations with birds. Conversely, the genomes of other Efs lineages exhibited divergence in core and accessory genomes, reflecting different adaptive trajectories in various hosts. This pangenome divergence, horizontal gene transfer events and occasional epidemic peaks could explain the population structure of the species.

The Possibility of an Infectious Etiology of Alzheimer Disease - Ghulam M. Ashraf; Vadim V. Tarasov; Alfiya Makhmutovа; Vladimir N. Chubarev; Marco Avila-Rodriguez; Sergey O. Bachurin; Gjumrakch Aliev (Molecular Neurobiology, 2019)

Cross-Cultural Medical Care Training and Education: a National Survey of Pediatric Hematology/Oncology Fellows-in-Training and Fellowship Program Directors - Amulya A. Nageswara Rao; Deepti M. Warad; Amy L. Weaver; Cathy D. Schleck; Vilmarie Rodriguez (Journal of Cancer Education, 2019)

Novel Caudovirales associated with Marine Group I Thaumarchaeota assembled from metagenomes - Mario López‐Pérez; Jose M. Haro‐Moreno; José R. de la Torre; Francisco Rodriguez‐Valera (Environmental Microbiology, 2019)
Summary Marine Group I (MGI) Thaumarchaeota are some of the most abundant microorganisms in the deep ocean and responsible for much of the ammonia oxidation occurring in this environment. In this work, we present 35 sequences assembled from metagenomic samples of the first uncultivated Caudovirales viruses associated with Thaumarchaeota, which we designated marthavirus. Most of the sequences were obtained from cellular metagenomes confirming that they represent an important tool to study environmental viral communities due to cells retrieved while undergoing viral lysis. Metagenomic recruitment showed that this viral population is formed by very divergent entities with high intrapopulation homogeneity. However, metatranscriptomic analyses revealed the same differential expression profile with the capsid as major transcript, indicative of viruses during the lytic cycle. The cobalamine biosynthesis gene cob S, an auxiliary metabolic gene, was also highly expressed during the infection. These analyses expand our understanding of the global diversity of archaeal viruses.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Telmisartan Protects a Microglia Cell Line from LPS Injury Beyond AT1 Receptor Blockade or PPARγ Activation - Abdel G. Elkahloun; Yara Rodriguez; Seham Alaiyed; Erin Wenzel; Juan M. Saavedra (Molecular Neurobiology, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Bottom boundary layer cooling and wind‐driven upwelling enhance the catchability of spanner crab ( Ranina ranina ) in South‐East Queensland, Australia - David M. Spencer; Ian W. Brown; Mark J. Doubell; Christopher J. Brown; Ana Redondo Rodriguez; Shing Yip Lee; Hong Zhang; Charles J. Lemckert (Fisheries Oceanography, 2019)
Species catchability is an important parameter used to help optimise stock assessment modelling and the economic efficiency of commercial fishing operations. Previous studies have shown several physical oceanographic parameters, including ambient temperature, waves and currents, affect the catchability of spanner crabs ( Ranina ranina ) throughout the Indo‐Pacific. Most notably in the Australian fishery, where oceanographic processes vary over space and time, a positive relationship between bottom boundary layer temperature ( BBLT ) and catch rates was observed. Here, we aimed to better understand how localised oceanographic processes affected this relationship in the southernmost South‐East Queensland ( SEQ ) sector of the Australian fishery at seasonal and short temporal scales. Our results show cooler BBLT , upwelling‐favourable alongshore wind stress and increased catch rates occurred during mating season in austral spring. At the end of austral summer, BBLT began warming, downwelling‐favourable winds were dominant, and catch rates declined around the post‐moult period. Outputs from the generalised linear models ( GLM s) that separated these effects in each season show that, at shorter temporal scales, daily catch rates also increased with episodic BBLT cooling and upwelling‐favourable alongshore wind stress, but only during austral autumn and winter. These new findings suggest that region‐specific, short‐term and seasonal variability of oceanographic processes responsible for changes in BBLT play an important role in influencing the catchability of spanner crabs. We suggest that the effects of region‐specific physical oceanographic processes must be considered in future work when investigating the catchability of commercially important fisheries species fished over large spatial domains.

Doubting dung: eDNA reveals high rates of misidentification in diverse European ungulate communities - Robert Spitzer; Marcin Churski; Annika Felton; Marco Heurich; Dries P. J. Kuijper; Marietjie Landman; Esther Rodriguez; Navinder J. Singh; Pierre Taberlet; Suzanne T. S. van Beeck Calkoen; Fredrik Widemo; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2019)

The Nutritional Contribution of Potato Varietal Diversity in Andean Food Systems: a Case Study - Stef de Haan; Gabriela Burgos; Reyna Liria; Flor Rodriguez; Hilary M. Creed-Kanashiro; Merideth Bonierbale (American Journal of Potato Research, 2019)

pH Variability Exacerbates Effects of Ocean Acidification on a Caribbean Crustose Coralline Alga - Maggie D. Johnson; Lucia M. Rodriguez Bravo; Shevonne E. O’Connor; Nicholas F. Varley; Andrew H. Altieri (Frontiers in Marine Science, 2019)

Vulnerability of smallholder farmers to climate change in Central America and Mexico: current knowledge and research gaps - Camila I. Donatti; Celia A. Harvey; M. Ruth Martinez-Rodriguez; Raffaele Vignola; Carlos Manuel Rodriguez (Climate and Development, 2019)

Lipotoxic Effects of Palmitic Acid on Astrocytes Are Associated with Autophagy Impairment - Ana Ortiz-Rodriguez; Estefania Acaz-Fonseca; Patricia Boya; Maria Angeles Arevalo; Luis M. Garcia-Segura (Molecular Neurobiology, 2019)

Differential Susceptibility of Wild and Cultivated Blueberries to an Invasive Frugivorous Pest - Cesar Rodriguez-Saona; Kevin R. Cloonan; Fernando Sanchez-Pedraza; Yucheng Zhou; M. Monica Giusti; Betty Benrey (Journal of Chemical Ecology, 2019)

Potential value of tedera (B. bituminosa) as high protein resource for poultry feed - M. Barbera; M.C. Muñoz; E. Rodriguez-Ponce; M.R. Ventura (Tropical Animal Health and Production, 2019)

Trophic ecology of European hake (Merlucius merlucius) larvae by stable isotopes analysis influenced by seasonal variability of oceanographic conditions off NW Galician waters. - Raul Carrion; Agueda Rodriguez; Jos M. Ervas; Alma De Rojas; Jose Maria Lopez; Piñeiro Carmen; Alberto Garcia (Frontiers in Marine Science, 2019)

Lichen species assemblage gradient in South Shetlands Islands, Antarctica: relationship to deglaciation and microsite conditions - J. M. Rodriguez; A. Passo; J. O. Chiapella (Polar Biology, 2018)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

PTRF acts as an adipokine contributing to adipocyte dysfunctionality and ectopic lipid deposition - Sergio Perez-Diaz; Maria P. Garcia-Sobreviela; Yolanda Gonzalez-Irazabal; Beatriz Garcia-Rodriguez; Silvia Espina; Izaskun Arenaz; Jose M. Arbones-Mainar (Journal of Physiology and Biochemistry, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Intra-organismal variation in the structure of plant vascular transport tissues in poplar trees - Anna L. Jacobsen; Jessica Valdovinos-Ayala; F. Daniela Rodriguez-Zaccaro; M. Angela Hill-Crim; Marta I. Percolla; Martin D. Venturas (Trees, 2018)

Invasive Rhinosinusitis Caused by Lasiodiplodia theobromae in an Allogeneic Hematopoietic Cell Transplant Recipient Case Report and Review of Literature - Anamaria Rodriguez; Shweta Anjan; Octavio V. Martinez; Lazaros J. Lekakis; Amer Beitinjaneh; Jose F. Camargo; Connie F. C. Gibas; Carmita J. Sanders; Nathan P. Wiederhold; Lilian M. Abbo (Mycopathologia, 2018)

Comparing the impact of a grazing regime with European bison versus one with free-ranging cattle on coastal dune vegetation in the Netherlands - E. Valdés-Correcher; Esther Rodriguez; Yvonne J. M. Kemp; Martin J. Wassen; Joris P. G. M. Cromsigt (Mammal Research, 2018)

Quantifying species recovery and conservation success to develop an IUCN Green List of Species - H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Molly K. Grace; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; David A. Keith; Barney Long; David P. Mallon; Erik Meijaard; et al. (Conservation Biology, 2018)
Stopping declines in biodiversity is critically important, but it is only a first step toward achieving more ambitious conservation goals. The absence of an objective and practical definition of species recovery that is applicable across taxonomic groups leads to inconsistent targets in recovery plans and frustrates reporting and maximization of conservation impact. We devised a framework for comprehensively assessing species recovery and conservation success. We propose a definition of a fully recovered species that emphasizes viability, ecological functionality, and representation; and use counterfactual approaches to quantify degree of recovery. This allowed us to calculate a set of 4 conservation metrics that demonstrate impacts of conservation efforts to date (conservation legacy); identify dependence of a species on conservation actions (conservation dependence); quantify expected gains resulting from conservation action in the medium term (conservation gain); and specify requirements to achieve maximum plausible recovery over the long term (recovery potential). These metrics can incentivize the establishment and achievement of ambitious conservation targets. We illustrate their use by applying the framework to a vertebrate, an invertebrate, and a woody and an herbaceous plant. Our approach is a preliminary framework for an International Union for Conservation of Nature (IUCN) Green List of Species, which was mandated by a resolution of IUCN members in 2012. Although there are several challenges in applying our proposed framework to a wide range of species, we believe its further development, implementation, and integration with the IUCN Red List of Threatened Species will help catalyze a positive and ambitious vision for conservation that will drive sustained conservation action.

Inflammatory and Anti-inflammatory Responses Co-exist Inside Lung Granuloma of Fatal Cases of Coccidioidomycosis: A Pilot Report - Heidi G. Rodriguez-Ramirez; Adolfo Soto-Dominguez; Gloria M. González; Oralia Barboza-Quintana; Mario C. Salinas-Carmona; Luis A. Ceceñas-Falcon; Roberto Montes-de-Oca-Luna; Alma Y. Arce-Mendoza; Adrian G. Rosas-Taraco (Mycopathologia, 2018)

Impact of dietary Arthrospira (Spirulina) biomass consumption on human health: main health targets and systematic review - A. de la Jara; C. Ruano-Rodriguez; M. Polifrone; P. Assunçao; Y. Brito-Casillas; A. M. Wägner; L. Serra-Majem (Journal of Applied Phycology, 2018)

Testing the ‘plant domestication-reduced defense’ hypothesis in blueberries: the role of herbivore identity - Johnattan Hernandez-Cumplido; M. Monica Giusti; Yucheng Zhou; Vera Kyryczenko-Roth; Yolanda H. Chen; Cesar Rodriguez-Saona (Arthropod-Plant Interactions, 2018)

Invasive pulmonary aspergillosis is associated with adverse clinical outcomes in critically ill patients receiving veno-venous extracorporeal membrane oxygenation - I. Rodriguez-Goncer; S. Thomas; P. Foden; M. D. Richardson; A. Ashworth; J. Barker; C. G. Geraghty; E. G. Muldoon; T. W. Felton (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Correction to: Top-down, Bottom-up and Sideways: the Multilayered Complexities of Multi-level Actors Shaping Forest Governance and REDD+ Arrangements in Madre de Dios, Peru - Dawn Rodriguez-Ward; Anne M. Larson; Harold Gordillo Ruesta (Environmental Management, 2018)

Top-down, Bottom-up and Sideways: The Multilayered Complexities of Multi-level Actors Shaping Forest Governance and REDD+ Arrangements in Madre de Dios, Peru - Dawn Rodriguez-Ward; Anne M. Larson; Harold Gordillo Ruesta (Environmental Management, 2018)

The impact of depuration on mussel hepatopancreas bacteriome composition and predicted metagenome - J. A. Rubiolo; A. Lozano-Leon; R. Rodriguez-Souto; N. Fol Rodríguez; M. R. Vieytes; L. M. Botana (Antonie van Leeuwenhoek, 2018)

Metal contaminations impact archaeal community composition, abundance and function in remote alpine lakes - Sergi Compte‐Port; Carles M. Borrego; Hélène Moussard; Mathilde Jeanbille; Claudia Ximena Restrepo‐Ortiz; Alberto de Diego; Azibar Rodriguez‐Iruretagoiena; Ainara Gredilla; Silvia Fdez‐Ortiz de Vallejuelo; Pierre E. Galand; Dimitri Kalenitchenko; Jean‐Luc Rols; et al. (Environmental Microbiology, 2018)
Summary Using the 16S rRNA and mcrA genes, we investigated the composition, abundance and activity of sediment archaeal communities within 18 high‐mountain lakes under contrasted metal levels from different origins (bedrock erosion, past‐mining activities and atmospheric depositions). Bathyarchaeota, Euryarchaeota and Woesearchaeota were the major phyla found at the meta‐community scale, representing 48%, 18.3% and 15.2% of the archaeal community respectively. Metals were equally important as physicochemical variables in explaining the assemblage of archaeal communities and their abundance. Methanogenesis appeared as a process of central importance in the carbon cycle within sediments of alpine lakes as indicated by the absolute abundance of methanogen 16S rRNA and mcrA gene transcripts (10 5 to 10 9 copies g −1 ). We showed that methanogen abundance and activity were significantly reduced with increasing concentrations of Pb and Cd, two indicators of airborne metal contaminations. Considering the ecological importance of methanogenesis in sediment habitats, these metal contaminations may have system wide implications even in remote area such as alpine lakes. Overall, this work was pioneer in integrating the effect of long‐range atmospheric depositions on archaeal communities and indicated that metal contamination might significantly compromise the contribution of Archaea to the carbon cycling of the mountain lake sediments.

Computational Investigation of a Self-Powered Fontan Circulation - Marcus W. Ni; Ray O. Prather; Giovanna Rodriguez; Rachel Quinn; Eduardo Divo; Mark Fogel; Alain J. Kassab; William M. DeCampli (Cardiovascular Engineering and Technology, 2018)

Role of Plant Volatiles in Host Plant Recognition by Listronotus maculicollis (Coleoptera: Curculionidae) - Olga S. Kostromytska; Cesar Rodriguez-Saona; Hans T. Alborn; Albrecht M. Koppenhöfer (Journal of Chemical Ecology, 2018)

Clinician and Parent Perspectives on Educational Needs for Increasing Adolescent HPV Vaccination - Christy A. Widman; Elisa M. Rodriguez; Frances Saad-Harfouche; Annamaria Masucci Twarozek; Deborah O. Erwin; Martin C. Mahoney (Journal of Cancer Education, 2018)

How can leadership processes in European bison be used to improve the management of free-roaming herds - Amandine Ramos; Lola Manizan; Esther Rodriguez; Yvonne J. M. Kemp; Cédric Sueur (European Journal of Wildlife Research, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Dynamic response behind an accident occurred in a main WSS - Mariana Simão; Jesus Mora-Rodriguez; Helena M. Ramos (European Journal of Environmental and Civil Engineering, 2018)

Specific Energy Requirements in Electrokinetic Remediation - Maria Villen-Guzman; Cesar Gomez-Lahoz; Francisco Garcia-Herruzo; Carlos Vereda-Alonso; Juan M. Paz-Garcia; Jose M. Rodriguez-Maroto (Transport in Porous Media, 2018)

Views on clinical trial recruitment, biospecimen collection, and cancer research: population science from landscapes of the Haudenosaunee (People of the Longhouse) - Rodney C. Haring; Whitney Ann Henry; Maui Hudson; Elisa M. Rodriguez; Maile Taualii (Journal of Cancer Education, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Impact of rapid diagnosis of Staphylococcus aureus bacteremia from positive blood cultures on patient management - M. P. Romero-Gómez; E. Cendejas-Bueno; J. García Rodriguez; J. Mingorance (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

An intravaginal ring that releases three antiviral agents and a contraceptive blocks SHIV-RT infection, reduces HSV-2 shedding, and suppresses hormonal cycling in rhesus macaques - Nina Derby; Meropi Aravantinou; Jessica Kenney; Shweta R. Ugaonkar; Asa Wesenberg; Jolanta Wilk; Larisa Kizima; Aixa Rodriguez; Shimin Zhang; Olga Mizenina; Keith Levendosky; Michael L. Cooney; et al. (Drug Delivery and Translational Research, 2017)

Ocular flutter following Zika virus infection - Emely Karam; Jose Giraldo; Flor Rodriguez; Carlos E. Hernandez-Pereira; Alfonso J. Rodriguez-Morales; Gabriela M. Blohm; Alberto E. Paniz-Mondolfi (Journal of NeuroVirology, 2017)

Impaired Mitochondrial Function and Dynamics in the Pathogenesis of FXTAS - M. I. Alvarez-Mora; L. Rodriguez-Revenga; I. Madrigal; M. Guitart-Mampel; G. Garrabou; M. Milà (Molecular Neurobiology, 2017)

Autonomous Coral Reef Survey in Support of Remote Sensing - Steven G. Ackleson; Joseph P. Smith; Luis M. Rodriguez; Wesley J. Moses; Brandon J. Russell (Frontiers in Marine Science, 2017)

Aerobic interval training reduces vascular resistances during submaximal exercise in obese metabolic syndrome individuals - Ricardo Mora-Rodriguez; V. E. Fernandez-Elias; F. Morales-Palomo; J. G. Pallares; M. Ramirez-Jimenez; J. F. Ortega (European Journal of Applied Physiology, 2017)

Imaging Markers of Post-Stroke Depression and Apathy: a Systematic Review and Meta-Analysis - Elles Douven; Sebastian Köhler; Maria M. F. Rodriguez; Julie Staals; Frans R. J. Verhey; Pauline Aalten (Neuropsychology Review, 2017)

Ventilator-associated pneumonia by methicillin-susceptible Staphylococcus aureus: do minimum inhibitory concentrations to vancomycin and daptomycin matter? - J. Ruiz-Ramos; P. Vidal-Cortés; A. Díaz-Lamas; R. Reig-Valero; F. Roche-Campo; M. Del Valle-Ortiz; X. Nuvials-Casals; M. Ortiz-Piquer; D. Andaluz-Ojeda; L. Tamayo-Lomas; M. A. Blasco-Navalpotro; M. Rodriguez-Aguirregabiria; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Advantage of multispectral imaging with sub-centimeter resolution in precision agriculture: generalization of training for supervised classification - F. Rodriguez-Moreno; J. Kren; F. Zemek; J. Novak; V. Lukas; M. Pikl (Precision Agriculture, 2017)

Satellite Remote Sensing for Coastal Management: A Review of Successful Applications - Matthew J. McCarthy; Kaitlyn E. Colna; Mahmoud M. El-Mezayen; Abdiel E. Laureano-Rosario; Pablo Méndez-Lázaro; Daniel B. Otis; Gerardo Toro-Farmer; Maria Vega-Rodriguez; Frank E. Muller-Karger (Environmental Management, 2017)

Progressive Neuronal Pathology and Synaptic Loss Induced by Prediabetes and Type 2 Diabetes in a Mouse Model of Alzheimer’s Disease - Juan Jose Ramos-Rodriguez; Tara Spires-Jones; Amy M. Pooler; Alfonso Maria Lechuga-Sancho; Brian J. Bacskai; Monica Garcia-Alloza (Molecular Neurobiology, 2017)

Ambulatory blood pressure response to a bout of HIIT in metabolic syndrome patients - M. Ramirez-Jimenez; F. Morales-Palomo; J. G. Pallares; Ricardo Mora-Rodriguez; J. F. Ortega (European Journal of Applied Physiology, 2017)

Evaluation of antimicrobial persistent activity of alcohol-based hand antiseptics against bacterial contamination - R. M. López-Gigosos; E. Mariscal-López; M. Gutierrez-Bedmar; A. García-Rodriguez; A. Mariscal (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Identification of MSH2 inversion of exons 1–7 in clinical evaluation of families with suspected Lynch syndrome - Maureen E. Mork; Andrea Rodriguez; Melissa W. Taggart; Miguel A. Rodriguez-Bigas; Patrick M. Lynch; Sarah A. Bannon; Y. Nancy You; Eduardo Vilar (Familial Cancer, 2017)

Semi‐quantitative reconstruction of early to late Holocene spring and summer sea ice conditions in the northern Barents Sea - Sarah M. P. Berben; Katrine Husum; Alba Navarro‐Rodriguez; Simon T. Belt; Steffen Aagaard‐Sørensen (Journal of Quaternary Science, 2017)
Semi‐quantitative estimates of early to late Holocene spring sea ice concentration (SpSIC) and occurrence of summer sea ice for the northern Barents Sea have been obtained by analysing the biomarkers IP 25 , brassicasterol and a tri‐unsaturated highly branched isoprenoid lipid in a Holocene marine sediment core. Sub‐surface water mass variations were derived from planktic foraminiferal assemblages and stable isotopes (δ 18 O, δ 13 C). The record indicates paleoceanographic changes over three intervals. During Period I (ca. 9500–5900 cal a BP), the study location experienced the lowest recorded SpSIC (ca. 25%) with short spring seasons and long productive summers, resulting partly from increased Atlantic Water inflow that caused a stronger ocean–atmosphere heat exchange. Throughout Period II (ca. 5900–2700 cal a BP), the winter sea ice margin migrated southwards and an overall cooling trend resulted in higher SpSIC (ca. 60%) and increased delivery of cold Arctic Water. During Period III (ca. 2700 cal a BP to present), SpSIC increased further (ca. 75%) and some sea ice remained during summer months. A sub‐surface warming probably indicates a decoupling of heat exchange between the ocean and the atmosphere. Longer springs and shorter summers were accompanied by the most southerly location of the winter sea ice margin.

Behaviour of two typical stents towards a new stent evolution - M. Simão; J. M. Ferreira; J. Mora-Rodriguez; J. Fragata; H. M. Ramos (Medical & Biological Engineering & Computing, 2017)

A comparison of psychotic symptoms in subjects with methamphetamine versus cocaine dependence - Peter D Alexander; Kristina M Gicas; Taylor S Willi; Clara N Kim; Veronika Boyeva; Ric M Procyshyn; Geoff N. Smith; Allen E Thornton; William J Panenka; Andrea A. Jones; Fidel Vila-Rodriguez; Donna J. Lang; et al. (Psychopharmacology, 2017)

Matrix metalloproteinase-14 triggers an anti-inflammatory proteolytic cascade in endotoxemia - Alina Aguirre; Jorge Blázquez-Prieto; Laura Amado-Rodriguez; Inés López-Alonso; Estefanía Batalla-Solís; Adrián González-López; Moisés Sánchez-Pérez; Carlos Mayoral-Garcia; Ana Gutiérrez-Fernández; Guillermo M Albaiceta (Journal of Molecular Medicine, 2017)

Does education influence wildlife friendly landscaping preferences? - Shari L. Rodriguez; M. Nils Peterson; Christopher J. Moorman (Urban Ecosystems, 2017)

Occurrence of Photobacterium damselae Subsp. Piscicida in Sea-Cage Farmed Meagre (Argyrosomus regius) in Tenerife, Canary Islands, Spain - J. Z. Costa; Ú. McCarthy; O. Perez; E. Ramos; M. Rodriguez; O. Monterroso; R. Riera (Thalassas: An International Journal of Marine Sciences, 2017)

Epidemiology and reporting of candidaemia in Belgium: a multi-centre study - C. Trouvé; S. Blot; M.-P. Hayette; S. Jonckheere; S. Patteet; H. Rodriguez-Villalobos; F. Symoens; E. Van Wijngaerden; K. Lagrou (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Electro-Magnetic Nano-Particle Bound Beclin1 siRNA Crosses the Blood–Brain Barrier to Attenuate the Inflammatory Effects of HIV-1 Infection in Vitro - Myosotys Rodriguez; Ajeet Kaushik; Jessica Lapierre; Seth M. Dever; Nazira El-Hage; Madhavan Nair (Journal of Neuroimmune Pharmacology, 2017)

What information do policy makers need to develop climate adaptation plans for smallholder farmers? The case of Central America and Mexico - Camila I. Donatti; Celia A. Harvey; M. Ruth Martinez-Rodriguez; Raffaele Vignola; Carlos Manuel Rodriguez (Climatic Change, 2017)

The effect of future climate change on the conservation of Chloraea disoides Lindl. (Orchidaceae) in Chile - C. Atala; L. Muñoz-Tapia; G. Pereira; C. Romero; R. Vargas; I. S. Acuña-Rodriguez; M. A. Molina-Montenegro; E. Brito (Brazilian Journal of Botany, 2017)

Genetic variation in resistance to leaf fungus indirectly affects spider density - Heather L. Slinn; Matthew A. Barbour; Kerri M. Crawford; Mariano A. Rodriguez‐Cabal; Gregory M. Crutsinger (Ecology, 2017)
Many host‐plants exhibit genetic variation in resistance to pathogens; however, little is known about the extent to which genetic variation in pathogen resistance influences other members of the host‐plant community, especially arthropods at higher trophic levels. We addressed this knowledge gap by using a common garden experiment to examine whether genotypes of Populus trichocarpa varied in resistance to a leaf‐blistering pathogen, Taphrina sp., and in the density of web‐building spiders, the dominant group of predatory arthropods. In addition, we examined whether variation in spider density was explained by variation in the density and size of leaf blisters caused by Taphrina . We found that P. trichocarpa genotypes exhibited strong differences in their resistance to Taphrina and that P. trichocarpa genotypes that were more susceptible to Taphrina supported more web‐building spiders, the dominant group of predatory arthropods. We suspect that this result is caused by blisters increasing the availability of suitable habitat for predators, and not due to variation in herbivores because including herbivore density as a covariate did not affect our models. Our study highlights a novel pathway by which genetic variation in pathogen resistance may affect higher trophic levels in arthropod communities.

Consensus Paper: Towards a Systems-Level View of Cerebellar Function: the Interplay Between Cerebellum, Basal Ganglia, and Cortex - Daniele Caligiore; Giovanni Pezzulo; Gianluca Baldassarre; Andreea C. Bostan; Peter L. Strick; Kenji Doya; Rick C. Helmich; Michiel Dirkx; James Houk; Henrik Jörntell; Angel Lago-Rodriguez; Joseph M. Galea; et al. (The Cerebellum, 2017)

South American PSP toxin-producing Cylindrospermopsis raciborskii (Cyanobacteria) decreases clearance rates of cladocerans more than copepods - Amelia Fabre; Gissell Lacerot; Rafael Rodriguez de Paiva; M. Carolina S. Soares; Valéria Freitas de Magalhães; Sylvia Bonilla (Hydrobiologia, 2017)

Sources of trace metals in PM10 from a petrochemical industrial complex in Northern Mexico - P. F. Rodriguez-Espinosa; R. M. Flores-Rangel; V. Mugica-Alvarez; S. S. Morales-Garcia (Air Quality, Atmosphere & Health, 2017)

Could the obligation to land undersized individuals increase the black market for juveniles: evidence from the Mediterranean? - Jose M Bellido; Mariano García‐Rodriguez; Teresa García‐Jiménez; María González‐Aguilar; Ana Carbonell‐Quetglas (Fish and Fisheries, 2017)
The latest Green Paper on the EU Common Fisheries Policy ( CFP ) identified the high level of discards in Europe as one of the structural weaknesses of the current CFP . The new CFP introduces a discard ban in European waters, with an obligation to land all regulated species. The fishing management system in the Mediterranean is based on effort control and technical measures, and this is raising some particular concerns about the effective implementation of the discard ban. With the exception of bluefin tuna ( Thunnus thynnus, Scombridae), there are no quotas in the Mediterranean and this regulation affects all regulated species with the minimum landing size. Under these circumstances, the discard ban may lead to an increase in the amount of juvenile fish caught, because such catches are not counted against a given quota, as is the case in the Atlantic fisheries, and thus, there is no incentive to avoid catching them. On the contrary, the obligation to land the juveniles that are now discarded and their subsequent fishmeal processing might even become commercially interesting. One possible consequence of the new regulation may be an increase in the illegal marketing of fish below the minimum size. The landing, storage and transportation of juveniles will all be legal, and this may simplify their commercialization via the black market. The discard ban and landing obligation should be accompanied by other measures to ensure their successful implementation, including the agreement of the fishing sector to comply with the rules and regulations.

Degradation of Hexachlorocyclohexanes (HCHs) by Stable Zero Valent Iron (ZVI) Microparticles - Carmen M. Dominguez; Sergio Rodriguez; David Lorenzo; Arturo Romero; Aurora Santos (Water, Air, & Soil Pollution, 2016)

Detection of comammox bacteria in full-scale wastewater treatment bioreactors using tag-454-pyrosequencing - Alejandro Gonzalez-Martinez; Alejandro Rodriguez-Sanchez; M. C. M van Loosdrecht; Jesus Gonzalez-Lopez; Riku Vahala (Environmental Science and Pollution Research, 2016)

β-Adrenergic receptor gene expression in HIV-associated neurocognitive impairment and encephalitis: implications for MOR-1K subcellular localization - Seth M. Dever; Myosotys Rodriguez; Nazira El-Hage (Journal of NeuroVirology, 2016)

Differential Response of a Local Population of Entomopathogenic Nematodes to Non-Native Herbivore Induced Plant Volatiles (HIPV) in the Laboratory and Field - Monique J. Rivera; Cesar Rodriguez-Saona; Hans T. Alborn; Albrecht M. Koppenhöfer (Journal of Chemical Ecology, 2016)

IFITM3 and severe influenza virus infection. No evidence of genetic association - M. López-Rodríguez; E. Herrera-Ramos; J. Solé-Violán; J. J. Ruíz-Hernández; L. Borderías; J. P. Horcajada; E. Lerma-Chippirraz; O. Rajas; M. Briones; M. C. Pérez-González; M. A. García-Bello; E. López-Granados; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Identification of DVT diseases using numerical simulations - M. Simão; J. M. Ferreira; J. Mora-Rodriguez; H. M. Ramos (Medical & Biological Engineering & Computing, 2016)

Engaging diverse populations in biospecimen donation: results from the Hoy y Mañana study - Elisa M. Rodriguez; Frances G. Saad-Harfouche; Austin Miller; Martin C. Mahoney; Christine B. Ambrosone; Carl D. Morrison; Willie Underwood; Deborah O. Erwin (Journal of Community Genetics, 2016)

Experimental and DFT characterization, antioxidant and anticancer activities of a Cu(II)–irbesartan complex: structure–antihypertensive activity relationships in Cu(II)–sartan complexes - María S. Islas; Alicia Luengo; Carlos A. Franca; Mercedes Griera Merino; Laura Calleros; Manuel Rodriguez-Puyol; Luis Lezama; Evelina G. Ferrer; Patricia A. M. Williams (JBIC Journal of Biological Inorganic Chemistry, 2016)

Identification of a novel PMS2 alteration c.505C>G (R169G) in trans with a PMS2 pathogenic mutation in a patient with constitutional mismatch repair deficiency - Maureen E. Mork; Ester Borras; Melissa W. Taggart; Amanda Cuddy; Sarah A. Bannon; Y. Nancy You; Patrick M. Lynch; Pedro T. Ramirez; Miguel A. Rodriguez-Bigas; Eduardo Vilar (Familial Cancer, 2016)

Genotype Number and Allelic Diversity Overview in the National Collection of Chilean Potatoes - M. Muñoz; C. Folch; F. Rodriguez; J. Kalazich; S. Orena; J. Santos; R. Vargas; A. Fahrenkrog; A. Puga (Potato Research, 2016)

Neisseria gonorrhoeae antimicrobial susceptibility in Barcelona: penA, ponA, mtrR, and porB mutations and NG-MAST sequence types associated with decreased susceptibility to cephalosporins - J. Serra-Pladevall; M. J. Barberá; S. Rodriguez; R. Bartolomé-Comas; G. Roig; R. Juvé; A. Andreu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Identification of a Novel Moth Sex Pheromone Component from Chilecomadia valdiviana - Heidy Herrera; Wilson Barros-Parada; M. Fernanda Flores; Wittko Francke; Eduardo Fuentes-Contreras; Marcela Rodriguez; Francisca Santis; Paulo H. G. Zarbin; Jan Bergmann (Journal of Chemical Ecology, 2016)

Soil mercury levels in the area surrounding the Cerro Prieto geothermal complex, MEXICO - M. A. Pastrana-Corral; F. T. Wakida; E. García-Flores; D. D. Rodriguez-Mendivil; A. Quiñonez-Plaza; T. D. J. Piñon-Colin (Environmental Monitoring and Assessment, 2016)

Recurrence of progressive multifocal leukoencephalopathy despite immune recovery in two HIV seropositive individuals - Kate M. Crossley; Shruti Agnihotri; Joga Chaganti; Michael L. Rodriguez; Leon Patrick McNally; Nagagopal Venna; Sarah E. Turbett; Matthew Gutman; Adrienne Morey; Igor J. Koralnik; Bruce J. Brew (Journal of NeuroVirology, 2016)

Amphibian‐killing chytrid in B razil comprises both locally endemic and globally expanding populations - T. S. Jenkinson; C. M. Betancourt Román; C. Lambertini; A. Valencia‐Aguilar; D. Rodriguez; C. H. L. Nunes‐de‐Almeida; J. Ruggeri; A. M. Belasen; D. da Silva Leite; K. R. Zamudio; J. E. Longcore; L. F. Toledo; et al. (Molecular Ecology, 2016)
Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ), is the emerging infectious disease implicated in recent population declines and extinctions of amphibian species worldwide. Bd strains from regions of disease‐associated amphibian decline to date have all belonged to a single, hypervirulent clonal genotype ( Bd ‐ GPL ). However, earlier studies in the Atlantic Forest of southeastern Brazil detected a novel, putatively enzootic lineage ( Bd ‐Brazil), and indicated hybridization between Bd ‐ GPL and Bd ‐Brazil. Here, we characterize the spatial distribution and population history of these sympatric lineages in the Brazilian Atlantic Forest. To investigate the genetic structure of Bd in this region, we collected and genotyped Bd strains along a 2400‐km transect of the Atlantic Forest. Bd ‐Brazil genotypes were restricted to a narrow geographic range in the southern Atlantic Forest, while Bd ‐ GPL strains were widespread and largely geographically unstructured. Bd population genetics in this region support the hypothesis that the recently discovered Brazilian lineage is enzootic in the Atlantic Forest of Brazil and that Bd ‐ GPL is a more recently expanded invasive. We collected additional hybrid isolates that demonstrate the recurrence of hybridization between panzootic and enzootic lineages, thereby confirming the existence of a hybrid zone in the Serra da Graciosa mountain range of Paraná State. Our field observations suggest that Bd ‐ GPL may be more infective towards native Brazilian amphibians, and potentially more effective at dispersing across a fragmented landscape. We also provide further evidence of pathogen translocations mediated by the Brazilian ranaculture industry with implications for regulations and policies on global amphibian trade.

Hydrological cycle effects on the aquatic community in a Neotropical stream of the Andean piedmont during the 2007–2010 ENSO events - M. I. Ríos‐Pulgarín; M. Barletta; N. J. Mancera‐Rodriguez (Journal of Fish Biology, 2016)
The seasonal and interannual changes in the fish, macroinvertebrates and phycoperiphyton assemblages of the Guarinó River were examined in relation to the physical and chemical environmental changes associated with the hydrological cycle and the El Niño‐Niña/Southern Oscillation (ENSO) between 2007 and 2010. Four samplings (in dry and rainy seasons) were performed per year. Environmental variables (temperature, pH, conductivity, turbidity, oxygen, total nitrogen, orthophosphate, depth and flow rate) were measured. The temporal patterns of the taxonomic compositions for the three assemblages and the functional composition of fish and macroinvertebrate assemblages with respect to environmental variables were examined through canonical discriminant analysis, multidimensional scaling and multiple correlations. The presence and abundance of fishes, macroinvertebrates and algae species were regulated by environmental variables associated with extreme hydrological events, which derived from the natural torrential regimen of the basin and larger‐scale phenomena, such as El Niño and La Niña. Fish abundance and richness were significantly correlated with algal density and pH, the macroinvertebrate density was negatively related to the flow rate and the richness was positively correlated with algal density. The algae richness was positively correlated with pH and negatively correlated with the flow rate and nitrogen. The algal density was positively correlated with pH and temperature and negatively correlated with river flow. The phycoperiphyton assemblage exhibited more direct responses in its density and richness to the hydrological changes ( r 2 = 0·743 and 0·800, respectively). In functional terms, the El Niño phenomenon was defined by a greater abundance of omnivorous and insectivorous fishes, as well as filter feeders, scrapers and macroinvertebrate predators. During La Niña, a greater abundance of benthic fishes (both detritivorous and insectivorous) and shredder and collector‐gatherer macroinvertebrates was observed. Differentiated responses recorded in the community were based on adaptive strategies for the local hydrological regime that enable fast recovery under conditions such as ENSO phenomena. Composition changes according to adaptations to different hydrological scenarios and the predominance of generalists' trophic guilds and species with plasticity in their habits and their ranges of environmental tolerance were found, supporting the habitat templet model.

Integrated Decision Support System for Prognostic and Diagnostic Analyses of Water Distribution System Failures - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Mina Hoorfar (Water Resources Management, 2016)

Impact of Raw Water Quality and Climate Factors on the Variability of Drinking Water Quality in Small Systems - A. Scheili; I. Delpla; R. Sadiq; M. J. Rodriguez (Water Resources Management, 2016)

From chemosynthesis-based communities to cold-water corals: Vulnerable deep-sea habitats of the Gulf of Cádiz - José L. Rueda; Emilio González-García; Cinja Krutzky; Francisco J. López-Rodriguez; Gerardo Bruque; Nieves López-González; Desiree Palomino; Ricardo F. Sánchez; Juan Tomás Vázquez; Luis M. Fernández-Salas; Victor Díaz-del-Río (Marine Biodiversity, 2016)

Sulfide-oxidizing bacteria establishment in an innovative microaerobic reactor with an internal silicone membrane for sulfur recovery from wastewater - F. Valdés; P. R. Camiloti; R. P. Rodriguez; T. P. Delforno; J. Carrillo-Reyes; M. Zaiat; D. Jeison (Biodegradation, 2016)

Biomineralization changes with food supply confer juvenile scallops ( Argopecten purpuratus ) resistance to ocean acidification - Laura Ramajo; Núria Marbà; Luis Prado; Sophie Peron; Marco A. Lardies; Alejandro B. Rodriguez‐Navarro; Cristian A. Vargas; Nelson A. Lagos; Carlos M. Duarte (Global Change Biology, 2016)
Future ocean acidification ( OA ) will affect physiological traits of marine species, with calcifying species being particularly vulnerable. As OA entails high energy demands, particularly during the rapid juvenile growth phase, food supply may play a key role in the response of marine organisms to OA . We experimentally evaluated the role of food supply in modulating physiological responses and biomineralization processes in juveniles of the Chilean scallop, Argopecten purpuratus, that were exposed to control ( pH ~ 8.0) and low pH ( pH ~ 7.6) conditions using three food supply treatments (high, intermediate, and low). We found that pH and food levels had additive effects on the physiological response of the juvenile scallops. Metabolic rates, shell growth, net calcification, and ingestion rates increased significantly at low pH conditions, independent of food. These physiological responses increased significantly in organisms exposed to intermediate and high levels of food supply. Hence, food supply seems to play a major role modulating organismal response by providing the energetic means to bolster the physiological response of OA stress. On the contrary, the relative expression of chitin synthase, a functional molecule for biomineralization, increased significantly in scallops exposed to low food supply and low pH , which resulted in a thicker periostracum enriched with chitin polysaccharides. Under reduced food and low pH conditions, the adaptive organismal response was to trade‐off growth for the expression of biomineralization molecules and altering of the organic composition of shell periostracum, suggesting that the future performance of these calcifiers will depend on the trajectories of both OA and food supply. Thus, incorporating a suite of traits and multiple stressors in future studies of the adaptive organismal response may provide key insights on OA impacts on marine calcifiers.

Loss and gains in ant–plant interactions mediated by extrafloral nectar: fidelity, cheats, and lies - K. Del-Claro; V. Rico-Gray; H. M. Torezan-Silingardi; E. Alves-Silva; R. Fagundes; D. Lange; W. Dáttilo; A. A. Vilela; A. Aguirre; D. Rodriguez-Morales (Insectes Sociaux, 2016)

Storm water retention and actual evapotranspiration performances of experimental green roofs in French oceanic climate - D. Yilmaz; M. Sabre; L. Lassabatère; M. Dal; F. Rodriguez (European Journal of Environmental and Civil Engineering, 2016)

IEOOS: the Spanish Institute of Oceanography Observing System - Elena Tel; Rosa Balbin; Jose-Manuel Cabanas; Maria-Jesus Garcia; M. Carmen Garcia-Martinez; Cesar Gonzalez-Pola; Alicia Lavin; Jose-Luis Lopez-Jurado; Carmen Rodriguez; Manuel Ruiz-Villarreal; Ricardo F. Sánchez-Leal; Manuel Vargas-Yáñez; et al. (Ocean Science, 2016)
Since its foundation, 100 years ago, the Spanish Institute of Oceanography (IEO) has been observing and measuring the ocean characteristics. Here is a summary of the initiatives of the IEO in the field of the operational oceanography. Some systems like the tide gauges network has been working for more than 70 years. The standard sections began at different moments depending on the local projects, and nowadays there are more than 180 coastal stations and deep-sea ones that are systematically sampled, obtaining physical and biochemical measurements. At this moment, the Observing System includes six permanent moorings equipped with current meters, an open-sea ocean-meteorological buoy offshore Santander and a sea-surface temperature satellite image station. It also supports the Spanish contribution to the Argo international programme with 47 deployed profilers, and continuous monitoring thermosalinometers, meteorological stations and vessel-mounted acoustic Doppler current profilers on the research vessel fleet. The system is completed with the contribution to the Northwest Iberian peninsula and Gibraltar observatories, and the development of regional prediction models. All these systematic measurements allow the IEO to give responses to ocean research activities, official agencies requirements and industrial and main society demands such as navigation, resource management, risks management, recreation, as well as for management development pollution-related economic activities or marine ecosystems. All these networks are linked to international initiatives, framed largely in supranational programmes of Earth observation sponsored by the United Nations or the European Union. The synchronic observation system permits a spatio-temporal description of some events, such as new deep water formation in the Mediterranean Sea and the injection of heat to intermediate waters in the Bay of Biscay after some colder northern storms in winter 2005.

Nitric oxide, prostaglandins and angiotensin II in the regulation of renal medullary blood flow during volume expansion - Carol Moreno; María T. Llinás; Francisca Rodriguez; Juan M. Moreno; F. Javier Salazar (Journal of Physiology and Biochemistry, 2016)

First recurrence of Clostridium difficile infection: clinical relevance, risk factors, and prognosis - T. Larrainzar-Coghen; D. Rodriguez-Pardo; M. Puig-Asensio; V. Rodríguez; C. Ferrer; R. Bartolomé; C. Pigrau; N. Fernández-Hidalgo; T. Pumarola; B. Almirante (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Cryopreserved amniotic membrane as transplant allograft: viability and post-transplant outcome - Natasha M. J. Perepelkin; Kirsten Hayward; Tumelo Mokoena; Michael J. Bentley; Lisa U. Ross-Rodriguez; Leah Marquez-Curtis; Locksley E. McGann; Jelena L. Holovati; Janet A. W. Elliott (Cell and Tissue Banking, 2016)

Effect of Microwave-Assisted Pretreatment Conditions on Hemicellulose Conversion and Enzymatic Hydrolysis of Norway Spruce - S. Kuittinen; Y. Puentes Rodriguez; M. Yang; M. Keinänen; O. Pastinen; M. Siika-aho; O. Turunen; A. Pappinen (BioEnergy Research, 2016)

Assessing stakeholder impacts and adaptation to low water-levels: the Trent-Severn waterway - J. M. A. Coleman; F. S. Sosa-Rodriguez; L. D. Mortsch; P. J. Deadman (Climatic Change, 2016)

Analysis of In Vitro Aptamer Selection Parameters - Maureen McKeague; Erin M. McConnell; Jose Cruz-Toledo; Elyse D. Bernard; Amanda Pach; Emily Mastronardi; Xueru Zhang; Michael Beking; Tariq Francis; Amanda Giamberardino; Ashley Cabecinha; Annamaria Ruscito; et al. (Journal of Molecular Evolution, 2015)

Metal enrichment of soils following the April 2012–2013 eruptive activity of the Popocatépetl volcano, Puebla, Mexico - P. F. Rodriguez-Espinosa; M. P. Jonathan; S. S. Morales-García; Lorena Elizabeth Campos Villegas; E. Martínez-Tavera; N. P. Muñoz-Sevilla; Miguel Alvarado Cardona (Environmental Monitoring and Assessment, 2015)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Nutrient enrichment intensifies hurricane impact in scrub mangrove ecosystems in the Indian River Lagoon, Florida, USA - Ilka C. Feller; Emily M. Dangremond; Donna J. Devlin; Catherine E. Lovelock; C. Edward Proffitt; Wilfrid Rodriguez (Ecology, 2015)
Mangroves are an ecological assemblage of trees and shrubs adapted to grow in intertidal environments along tropical, subtropical, and warm temperate coasts. Despite repeated demonstrations of their ecologic and economic value, multiple stressors including nutrient over‐enrichment threaten these and other coastal wetlands globally. These ecosystems will be further stressed if tropical storm intensity and frequency increase in response to global climate changes. These stressors will likely interact, but the outcome of that interaction is uncertain. Here, we examined potential interaction between nutrient over‐enrichment and the September 2004 hurricanes. Hurricanes Frances and Jeanne made landfall along Florida's Indian River Lagoon and caused extensive damage to a long‐term fertilization experiment in a mangrove forest, which previously revealed that productivity was nitrogen (N) limited across the forest and, in particular, that N enrichment dramatically increased growth rates and aboveground biomass of stunted Avicennia germinans trees in the interior scrub zone. During the hurricanes, these trees experienced significant defoliation with three to four times greater reduction in leaf area index (LAI) than control trees. Over the long term, the +N scrub trees took four years to recover compared to two years for controls. In the adjacent fringe and transition zones, LAI was reduced by >70%, but with no differences based on zone or fertilization treatment. Despite continued delayed mortality for at least five years after the storms, LAI in the fringe and transition returned to pre‐hurricane conditions in two years. Thus, nutrient over‐enrichment of the coastal zone will increase the productivity of scrub mangroves, which dominate much of the mangrove landscape in Florida and the Caribbean; however, that benefit is offset by a decrease in their resistance and resilience to hurricane damage that has the potential to destabilize the system.

Microsphere-Based Rapamycin Delivery, Systemic Versus Local Administration in a Rat Model of Renal Ischemia/Reperfusion Injury - Jurjen Zandstra; Marike M. van Beuge; Johan Zuidema; Arjen H. Petersen; Mark Staal; Luisa F. Duque; Sergio Rodriguez; Audrey A. R. Lathuile; Gert J. Veldhuis; Rob Steendam; Ruud A. Bank; Eliane R. Popa (Pharmaceutical Research, 2015)

Common polygenic variation contributes to risk of migraine in the Norfolk Island population - A. J. Rodriguez-Acevedo; M. A. Ferreira; Miles C. Benton; Melanie A. Carless; Harald H. Goring; Joanne E. Curran; John Blangero; R. A. Lea; L. R. Griffiths (Human Genetics, 2015)

Removal of BrO3 − from drinking water samples using newly developed agricultural waste-based activated carbon and its determination by ultra-performance liquid chromatography-mass spectrometry - Mu. Naushad; Mohammad R. Khan; Zeid A. ALOthman; Ibrahim AlSohaimi; Francisco Rodriguez-Reinoso; Turki M. Turki; Rahmat Ali (Environmental Science and Pollution Research, 2015)

HIV-infected microglia mediate cathepsin B-induced neurotoxicity - Frances Zenón; Yisel Cantres-Rosario; Radhika Adiga; Mariangeline Gonzalez; Eillen Rodriguez-Franco; Dianne Langford; Loyda M. Melendez (Journal of NeuroVirology, 2015)

Engaging Immigrant and Refugee Women in Breast Health Education - Matthew Gondek; May Shogan; Frances G. Saad-Harfouche; Elisa M. Rodriguez; Deborah O. Erwin; Kim Griswold; Martin C. Mahoney (Journal of Cancer Education, 2015)

Calliandra bifoliolata (Leguminosae, Mimosoideae), a new species from Chiapas, Mexico, with notes on C. brenesii, C. grandifolia, and C. laevis - Andrés Ernesto Ortiz-Rodriguez; Héctor M. Hernández; Miguel Angel Perez-Farrera (Brittonia, 2015)

Linking coastal aquaculture of meagre Argyrosomus regius and Western Mediterranean coastal fisheries through escapes incidents - P. Arechavala‐Lopez; J. M. Valero‐Rodriguez; J. Peñalver‐García; D. Izquierdo‐Gomez; P. Sanchez‐Jerez (Fisheries Management and Ecology, 2015)
Escape incidents in coastal aquaculture lead to economic losses for farmers and may have indirect socio‐economic effects on local fisheries. In this study, the relationship of meagre, Argyrosomus regius (Asso), production in open‐sea cages and coastal small‐scale fisheries was analysed through captures of escapes, which are easily detected because this species is considered locally absent in native communities in Western Mediterranean regions. Scale reading showed that 100% of captured meagre were escapees. The existence of a direct relationship, in terms of biomass, between the development of meagre coastal aquaculture and the increase of captures of this species by local fisheries was demonstrated. The spatial distribution of meagre captures suggested that there is a local environmental and economic interaction between meagre aquaculture and fisheries through escapees. Monitoring the presence of locally absent species such as meagre within landings might help to assess the magnitude of escapes, the potential economic effects on local aquaculture and fishery industries, and the potential adverse ecological impacts on local ecosystems.

Oxidized and reduced [2Fe–2S] clusters from an iron(I) synthon - Megan E. Reesbeck; Meghan M. Rodriguez; William W. Brennessel; Brandon Q. Mercado; David Vinyard; Patrick L. Holland (JBIC Journal of Biological Inorganic Chemistry, 2015)

Antagomirs targeting microRNA-134 increase hippocampal pyramidal neuron spine volume in vivo and protect against pilocarpine-induced status epilepticus - Eva M. Jimenez-Mateos; Tobias Engel; Paula Merino-Serrais; Isabel Fernaud-Espinosa; Natalia Rodriguez-Alvarez; James Reynolds; Cristina R. Reschke; Ronan M. Conroy; Ross C. McKiernan; Javier deFelipe; David C. Henshall (Brain Structure and Function, 2015)

Neighbouring populations, opposite dynamics: influence of body size and environmental variation on the demography of stream-resident brown trout (Salmo trutta) - Albert Fernández-Chacón; Meritxell Genovart; David Álvarez; José M. Cano; Alfredo F. Ojanguren; Rolando Rodriguez-Muñoz; Alfredo G. Nicieza (Oecologia, 2015)

Overexpression of 14-3-3ζ Increases Brain Levels of C/EBP Homologous Protein CHOP - Gary P. Brennan; Eva M. Jimenez-Mateos; Amaya Sanz-Rodriguez; Claire M. Mooney; Guri Tzivion; David C. Henshall; Tobias Engel (Journal of Molecular Neuroscience, 2015)

Maintaining Antioxidant Potential of Fresh Fruits and Vegetables After Harvest - Jose A. Villa-Rodriguez; H. Palafox-Carlos; Elhadi M. Yahia; J. Fernando Ayala-Zavala; Gustavo A. Gonzalez-Aguilar (Critical Reviews in Food Science and Nutrition, 2015)

Vertical distribution and migration of fish larvae in the NW Iberian upwelling system during the winter mixing period: implications for cross‐shelf distribution - J.M. Rodriguez; A. Cabrero; J. Gago; C. Guevara‐Fletcher; M. Herrero; A. Hernandez de Rojas; A. Garcia; R. Laiz‐Carrion; A.R. Vergara; P. Alvarez; C. Piñeiro; F. Saborido‐Rey (Fisheries Oceanography, 2015)
The vertical distribution and vertical migrations of fish larvae and implications for their cross‐shelf distribution were investigated in the northern limit of the NE Atlantic upwelling region during the late winter mixing period of 2012. The average positive values of the upwelling index for February and March of this year were far from normal, although the average hydrographic conditions during the period of study were of downwelling and the water column was completely mixed. Fish larvae, most in the preflexion stage, were concentrated in the upper layers of the water column and their distribution was depth stratified, both day and night. However, the larval fish community was not structured in the vertical plane and fish larvae did not show significant diel vertical migration ( DVM ), although five species showed ontogenetic vertical migration. In regions of coastal upwelling and in the absence of DVM , the location of fish larvae in the water column is crucial for their cross‐shelf distribution. Thus, the cross‐shelf distribution of the six most abundant species collected in this study can be explained by the surface onshore flow associated with coastal downwelling, retaining larvae of the coastal spawning species with a relatively shallow distribution in the shelf region and transporting larvae of slope spawning species onto the shelf. The wide vertical distribution shown by larvae of the offshore spawning species could be an adaptation of these species to ensure that some larvae reach the inshore nursery areas.

A hydrologic tracer study in a small, natural wetland in the humid tropics of Costa Rica - D. Kaplan; M. Bachelin; C. Yu; R. Muñoz-Carpena; Thomas L. Potter; W. Rodriguez-Chacón (Wetlands Ecology and Management, 2015)

Is Streptococcus bovis a urinary pathogen? - M. Matesanz; D. Rubal; I. Iñiguez; R. Rabuñal; F. García-Garrote; A. Coira; M. J. García-País; J. Pita; A. Rodriguez-Macias; M. J. López-Álvarez; M. P. Alonso; J. Corredoira (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Higher sensitivity to the conditioned rewarding effects of cocaine and MDMA in High-Novelty-Seekers mice exposed to a cocaine binge during adolescence - A. Mateos-García; C. Roger-Sánchez; M. Rodriguez-Arias; J. Miñarro; M. A. Aguilar; C. Manzanedo; M. C. Arenas (Psychopharmacology, 2015)

Testing a ‘genes‐to‐ecosystems’ approach to understanding aquatic–terrestrial linkages - Gregory M. Crutsinger; Seth M. Rudman; Mariano A. Rodriguez‐Cabal; Athena D. McKown; Takuya Sato; Andrew M. MacDonald; Julian Heavyside; Armando Geraldes; Edmund M. Hart; Carri J. LeRoy; Rana W. El‐Sabaawi (Molecular Ecology, 2014)
A ‘genes‐to‐ecosystems’ approach has been proposed as a novel avenue for integrating the consequences of intraspecific genetic variation with the underlying genetic architecture of a species to shed light on the relationships among hierarchies of ecological organization (genes → individuals → communities → ecosystems). However, attempts to identify genes with major effect on the structure of communities and/or ecosystem processes have been limited and a comprehensive test of this approach has yet to emerge. Here, we present an interdisciplinary field study that integrated a common garden containing different genotypes of a dominant, riparian tree, Populus trichocarpa , and aquatic mesocosms to determine how intraspecific variation in leaf litter alters both terrestrial and aquatic communities and ecosystem functioning. Moreover, we incorporate data from extensive trait screening and genome‐wide association studies estimating the heritability and genes associated with litter characteristics. We found that tree genotypes varied considerably in the quality and production of leaf litter, which contributed to variation in phytoplankton abundances, as well as nutrient dynamics and light availability in aquatic mesocosms. These ‘after‐life’ effects of litter from different genotypes were comparable to the responses of terrestrial communities associated with the living foliage. We found that multiple litter traits corresponding with aquatic community and ecosystem responses differed in their heritability. Moreover, the underlying genetic architecture of these traits was complex, and many genes contributed only a small proportion to phenotypic variation. Our results provide further evidence that genetic variation is a key component of aquatic–terrestrial linkages, but challenge the ability to predict community or ecosystem responses based on the actions of one or a few genes.

Effects of isometric training on the knee extensor moment–angle relationship and vastus lateralis muscle architecture - Luis M. Alegre; Asunción Ferri-Morales; Raúl Rodriguez-Casares; Xavier Aguado (European Journal of Applied Physiology, 2014)

Regional status assessment of stony corals in the US Virgin Islands - William S. Fisher; Leska S. Fore; Leah M. Oliver; Charles Lobue; Robert Quarles; Jed Campbell; Peggy Harris; Becky Hemmer; Sherry Vickery; Mel Parsons; Aaron Hutchins; Kent Bernier; et al. (Environmental Monitoring and Assessment, 2014)

Treatment of cosmetic wastewater by a full-scale membrane bioreactor (MBR) - Victor M. Monsalvo; Jesus Lopez; Angel F. Mohedano; Juan J. Rodriguez (Environmental Science and Pollution Research, 2014)

Establishment and characterization of a new cell line ( SSP ‐9) derived from Atlantic salmon Salmo salar that expresses type I if n - S. Rodriguez Saint‐Jean; C. González; M. Monrás; A. Romero; N. Ballesteros; R. Enríquez; S. Perez‐Prieto (Journal of Fish Biology, 2014)
In the present work, the establishment and biological characterization of a new cell line, SSP ‐9, derived from the pronephros of the Atlantic salmon Salmo salar , are reported. These cells grew well in Leibovitz's ( L15 ) medium supplemented with 10% foetal calf serum at temperatures from 15 to 25 ° C , and they have been sub‐cultured over 100 passages to produce a continuous cell line with an epithelial‐like morphology. The SSP ‐9 cells attached and spread efficiently at different plating densities, retaining 80% of cell viability after storage in liquid nitrogen. When karyotyped, the cells had 40–52 chromosomes, with a modal number of 48. Viral susceptibility tests showed that SSP ‐9 cells were susceptible to infectious pancreatic necrosis virus and infectious haematopoietic necrosis virus, producing infectious virus and regular cytopathic effects. Moreover, these cells could be stimulated by poly I:C, showing significant up‐regulation in the expression of the genes that regulate immune responses, such as ifn and mx‐1 . SSP ‐9 cells constitutively express genes characteristic of macrophages, such as major histocompatibility complex ( mhc‐ II ) and interleukin 12b ( il‐12b ), and flow cytometry assays confirmed that SSP ‐9 cells can be permanently transfected with plasmids expressing a reporter gene. Accordingly, this new cell line is apparently suitable for transgenic manipulation, and to study host cell–virus interactions and immune processes.

Geomechanical modelling to assess fault integrity at the CO2CRC Otway Project, Australia - C. M. Aruffo; A. Rodriguez-herrera; E. Tenthorey; F. Krzikalla; J. Minton; A. Henk (Australian Journal of Earth Sciences, 2014)

Engaging diverse populations about biospecimen donation for cancer research - Julie H. T. Dang; Elisa M. Rodriguez; John S. Luque; Deborah O. Erwin; Cathy D. Meade; Moon S. Chen (Journal of Community Genetics, 2014)

Fear extinction and acute stress reactivity reveal a role of LPA1 receptor in regulating emotional-like behaviors - C. Pedraza; J. Sánchez-López; E. Castilla-Ortega; C. Rosell-Valle; E. Zambrana-Infantes; M. García-Fernández; F. Rodriguez de Fonseca; J. Chun; L. J. Santín; G. Estivill-Torrús (Brain Structure and Function, 2014)

Understanding the Role of the Biological Pump in the Global Carbon Cycle: An Imperative for Ocean Science - Susumu Honjo; Timothy Eglinton; Craig Taylor; Kevin Ulmer; Stefan Sievert; Astrid Bracher; Christopher German; Virginia Edgcomb; Roger Francois; M. Debora Iglesias-Rodriguez; Benjamin Van Mooy; Daniel Rapeta (Oceanography, 2014)

Toxicity assessment through multiple endpoint bioassays in soils posing environmental risk according to regulatory screening values - A. Rodriguez-Ruiz; V. Asensio; B. Zaldibar; M. Soto; I. Marigómez (Environmental Science and Pollution Research, 2014)

Strategies to evaluate biodegradability: application to chlorinated herbicides - S. Sanchis; A. M. Polo; M. Tobajas; J. J. Rodriguez; A. F. Mohedano (Environmental Science and Pollution Research, 2014)

Escherichia coli viability determination using dynamic light scattering: a comparison with standard methods - Achim M. Loske; Elba M. Tello; Susana Vargas; Rogelio Rodriguez (Archives of Microbiology, 2014)

Quetiapine extended-release (Seroquel-XR) versus amitriptyline monotherapy for treating patients with fibromyalgia: a 16-week, randomized, flexible-dose, open-label trial - Elena P. Calandre; Fernando Rico-Villademoros; Jaime Galán; Rocio Molina-Barea; Juan S. Vilchez; Carmen M. Rodriguez-Lopez; Javier Hidalgo-Tallon; Piedad Morillas-Arques (Psychopharmacology, 2014)

Hybridization rate and climate change: are endangered species at risk? - R. A. Sánchez-Guillén; J. Muñoz; J. Hafernik; M. Tierney; G. Rodriguez-Tapia; A. Córdoba-Aguilar (Journal of Insect Conservation, 2014)

Reducing the draconitic errors in GNSS geodetic products - C. J. Rodriguez-Solano; U. Hugentobler; P. Steigenberger; M. Bloßfeld; M. Fritsche (Journal of Geodesy, 2014)

Promoting Colorectal Cancer Screening through Group Education in Community-Based Settings - Danielle M. Crookes; Ogo Njoku; Maria Carina Rodriguez; Elsa Iris Mendez; Lina Jandorf (Journal of Cancer Education, 2014)

New subgroup 16SrIII-Y phytoplasmas associated with false-blossom diseased cranberry (Vaccinium macrocarpon) plants and with known and potential insect vectors in New Jersey - I.-M. Lee; J. Polashock; K. D. Bottner-Parker; P. G. Bagadia; C. Rodriguez-Saona; Y. Zhao; R. E. Davis (European Journal of Plant Pathology, 2014)

Social network analysis resolves temporal dynamics of male dominance relationships - David Bierbach; Sophie Oster; Jonas Jourdan; Lenin Arias-Rodriguez; Jens Krause; Alexander D. M. Wilson; Martin Plath (Behavioral Ecology and Sociobiology, 2014)

Direct ageing of Thunnus thynnus from the eastern Atlantic Ocean and western Mediterranean Sea using dorsal fin spines - P. L. Luque; E. Rodriguez‐Marin; J. Landa; M. Ruiz; P. Quelle; D. Macias; J. M. Ortiz De Urbina (Journal of Fish Biology, 2014)
This study deals with important methodology issues that affect age estimates of eastern Atlantic bluefin tuna Thunnus thynnus using dorsal fin spines. Nearly 3800 spine sections were used from fish caught in the north‐east Atlantic Ocean and western Mediterranean Sea over a 21 year period. Edge type and marginal increment analyses indicated a yearly periodicity of annulus formation with the translucent bands (50% of occurrence) appearing from October to May. Nucleus vascularization seriously affected specimens older than 6 years, with the disappearance of 40–50% of the presumed annuli by that age. An alternate sectioning location was a clear improvement and this finding is an important contribution to the methodology of using this structure for ageing the full‐length range of eastern T. thynnus . Finally, there were no significant differences between the coefficients of von Bertalanffy growth model estimated from mean length at age data ( L ∞ = 327·4; k = 0·097; t 0 = −0·838) and those estimated from the growth curves accepted for the eastern and western T. thynnus management units.

Occurrence and Removal of Selected Pharmaceuticals and Personal Care Products in Three Wastewater-Treatment Plants - Jeong-Wook Kwon; Jose M. Rodriguez (Archives of Environmental Contamination and Toxicology, 2014)

Patient-reported hereditary breast and ovarian cancer in a primary care practice - John M. Quillin; Alexander H. Krist; Maria Gyure; Rosalie Corona; Vivian Rodriguez; Joseph Borzelleca; Joann N. Bodurtha (Journal of Community Genetics, 2014)

Growth responses to temperature, salinity and nutrient variations, and biomass variation and phenology of Ahnfeltia plicata (Rhodophyta, Ahnfeltiales): a commercially interesting agarophyte from the Magellanic Region, Chile - Andres Mansilla; Juan Pablo Rodriguez; Jonatas M. C. Souza; Sebastián Rosenfeld; Jaime Ojeda; Nair S. Yokoya (Journal of Applied Phycology, 2014)

Differential expression and ligand binding indicate alternative functions for zebrafish polymeric immunoglobulin receptor (pIgR) and a family of pIgR-like (PIGRL) proteins - Amanda N. Kortum; Ivan Rodriguez-Nunez; Jibing Yang; Juyoung Shim; Donna Runft; Marci L. O’Driscoll; Robert N. Haire; John P. Cannon; Poem M. Turner; Ronda T. Litman; Carol H. Kim; Melody N. Neely; et al. (Immunogenetics, 2014)

Comparative study of fuzzy evidential reasoning and fuzzy rule-based approaches: an illustration for water quality assessment in distribution networks - E. Aghaarabi; F. Aminravan; R. Sadiq; M. Hoorfar; M. J. Rodriguez; H. Najjaran (Stochastic Environmental Research and Risk Assessment, 2014)

Water distribution system failure: a framework for forensic analysis - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Alex Francisque; Mina Hoorfar (Environment Systems and Decisions, 2014)

High-quality conforming hexahedral meshes of patient-specific abdominal aortic aneurysms including their intraluminal thrombi - J. Tarjuelo-Gutierrez; B. Rodriguez-Vila; D. M. Pierce; T. E. Fastl; P. Verbrugghe; I. Fourneau; G. Maleux; P. Herijgers; G. A. Holzapfel; E. J. Gomez (Medical & Biological Engineering & Computing, 2014)

Genetic variation within a dominant shrub structures green and brown community assemblages - Gregory M. Crutsinger; Mariano A. Rodriguez-Cabal; Adam B. Roddy; Kabir G. Peay; Justin L. Bastow; Allison G. Kidder; Todd E. Dawson; Paul V. A. Fine; Jennifer A. Rudgers (Ecology, 2014)
Two rising challenges in ecology are understanding the linkages between above‐ and belowground components of terrestrial ecosystems and connecting genes to their ecological consequences. Here, we blend these emerging perspectives using a long‐term common‐garden experiment in a coastal dune ecosystem, whose dominant shrub species, Baccharis pilularis , exists as erect or prostrate architectural morphotypes. We explored variation in green (foliage‐based) and brown (detritus‐based) community assemblages, local ecosystem processes, and understory microclimate between the two morphs. Prostrate morphs supported more individuals, species, and different compositions of foliage arthropods, litter microarthropods, and soil bacteria than erect morphs. The magnitude of community compositional differences was maintained from crown to litter to soil. Despite showing strikingly similar responses, green and brown assemblages were associated with different underlying mechanisms. Differences in estimated shrub biomass best explained variation in the green assemblage, while understory abiotic conditions accounted for variation in the brown assemblage. Prostrate morphs produced more biomass and litter, which corresponded with their strong lateral growth in a windy environment. Compared to erect morphs, the denser canopy and thicker litter layer of prostrate morphs helped create more humid understory conditions. As a result, decomposition rates were higher under prostrate shrubs, despite prostrate litter being of poorer quality. Together, our results support the hypothesis that intraspecific genetic variation in primary producers is a key mediator of above‐ and belowground linkages, and that integrating the two perspectives can lead to new insights into how terrestrial communities are linked with ecosystem pools and processes.

Total arsenic in rice milk - Ron Shannon; Jose M. Rodriguez (Food Additives & Contaminants Part B-Surveillance, 2014)

Impacts of landscape fragmentation on simulated precipitation fields in the Amazonian sub-basin of Ji-Paraná using the Eta model - Daniel Andres Rodriguez; Sin Chan Chou; Javier Tomasella; Eleonora M. C. Demaria (Theoretical and Applied Climatology, 2014)

Multiple spine boutons are formed after long-lasting LTP in the awake rat - N. I. Medvedev; G. Dallérac; V. I. Popov; J. J. Rodriguez Arellano; H. A. Davies; I. V. Kraev; V. Doyère; M. G. Stewart (Brain Structure and Function, 2014)

A regulated deficit irrigation strategy for hedgerow olive orchards with high plant density - José E. Fernández; Alfonso Perez-Martin; José M. Torres-Ruiz; María V. Cuevas; Celia M. Rodriguez-Dominguez; Sheren Elsayed-Farag; Ana Morales-Sillero; José M. García; Virginia Hernandez-Santana; Antonio Diaz-Espejo (Plant and Soil, 2013)

Diffusional conductances to CO2 as a target for increasing photosynthesis and photosynthetic water-use efficiency - Jaume Flexas; Ülo Niinemets; Alexander Gallé; Margaret M. Barbour; Mauro Centritto; Antonio Diaz-Espejo; Cyril Douthe; Jeroni Galmés; Miquel Ribas-Carbo; Pedro L. Rodriguez; Francesc Rosselló; Raju Soolanayakanahally; et al. (Photosynthesis Research, 2013)

Optimization of a Trap for Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) and Trials to Determine the Effectiveness of Mass Trapping - E Lobos; M Occhionero; D Werenitzky; J Fernandez; L M Gonzalez; C Rodriguez; C Calvo; G Lopez; A C Oehlschlager (Neotropical Entomology, 2013)

The Immune System in Stroke: Clinical Challenges and Their Translation to Experimental Research - Craig J. Smith; Catherine B. Lawrence; Beatriz Rodriguez-Grande; Krisztina J. Kovacs; Jesus M. Pradillo; Adam Denes (Journal of Neuroimmune Pharmacology, 2013)

Erratum to: Evaluating Lynch syndrome in very early onset colorectal cancer probands without apparent polyposis - Kory W. Jasperson; Thuy M. Vu; Angela L. Schwab; Deborah W. Neklason; Miguel A. Rodriguez-Bigas; Randall W. Burt; Jeffrey N. Weitzel (Familial Cancer, 2013)

Gastrointestinal Histoplasmosis in a Hepatitis C-Infected Individual - Paul M. Rodriguez-Waitkus; Vafa Bayat; Elias George; Norbert Sule (Mycopathologia, 2013)

A Novel Human Glycoprotein ACA is an Upstream Regulator of Human Hematopoiesis - Z. A. Becker-Kojić; J. R. Ureña-Peralta; R. Saffrich; F. J. Rodriguez-Jiménez; M. P. Rubio; P. Rios; A. Romero; A. D. Ho; M. Stojković (Bulletin of Experimental Biology and Medicine, 2013)

Activation by ACA Induces Pluripotency in Human Blood Progenitor Cells - Z. A. Becker-Kojić; J. R. Ureña-Peralta; I. Zipančić; F. J. Rodriguez-Jiménez; M. P. Rubio; P. Stojković; M. G. Roselló; M. Stojković (Bulletin of Experimental Biology and Medicine, 2013)

Quantifying fine-scale resource selection by introduced European hedgehogs (Erinaceus europaeus) in ecologically sensitive areas - Mariano Rodriguez Recio; Renaud Mathieu; M. Cecilia Latham; A. David M. Latham; Philip J. Seddon (Biological Invasions, 2013)

Geographic variation in allele frequency of the gamete recognition protein M7 lysin throughout a mosaic blue mussel hybrid zone - Matthew R. Gilg; M. Camila Restrepo; Ronald Walton; Pamela M. Brannock; Thomas J. Hilbish; Emmanuel Rodriguez (Marine Biology, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

Assessing water stress in a hedgerow olive orchard from sap flow and trunk diameter measurements - M. V. Cuevas; M. J. Martín-Palomo; A. Diaz-Espejo; J. M. Torres-Ruiz; C. M. Rodriguez-Dominguez; A. Perez-Martin; R. Pino-Mejías; J. E. Fernández (Irrigation Science, 2013)

Hevea brasiliensis and Urtica dioica impact the in vitro mycorrhization of neighbouring Medicago truncatula seedlings - Tiffany Sosa-Rodriguez; Stéphane Declerck; Francoise Granet; Sylvie Gaurel; Els J. M. Van Damme; Hervé Dupré de Boulois (Symbiosis, 2013)

Population dynamics of Sonoran Desert saguaro cactus ( Carnegiea gigantea ) at the Desert Laboratory (Tucson, Arizona) - Susana Rodriguez-Buritica; Helen Raichle; Trevor Birt; Robert H. Webb; Raymond M. Turner; Elizabeth A. Pierson; D. Lawrence Venable (Ecology, 2013)
The saguaro cactus ( Carnegiea gigantea ) is one of the most iconic perennials in the Sonoran Desert. The ecological importance of this species has motivated studies that explored its physiological adaptations to deserts, factors controlling its recruitment and distribution, and changes in its population density and extent over time. The population of saguaros on Tumamoc Hill (Tucson, Arizona) is one of the best studied. Saguaros on and nearby Tumamoc Hill were mapped in 1908, and in 1964 R. M. Turner and J. R. Hastings established four 250‐m wide plots within the original census area. Plots were established on the north‐, south‐, east‐, and west‐facing slopes of Tumamoc Hill, and each plot extends from the top to the base of the hill. Plots were resurveyed in 1970, 1987, 1993, and between 2010 and 2012. In this Data Paper, we present all information associated with this monitoring program, which includes digital versions of Spalding's original 1908 saguaro map as well as information regarding individual saguaros located in each of the four plots. Collected data include plant height, number of branches, and plant condition, as well as plant location. Starting in 1993, we also noted the identity and condition of plant species growing in close proximity to each saguaro. The archived data set described here contains information pertaining to >5800 saguaros. Past analyses of these data include reconstructions of regeneration patterns from observed age structures and the determination of the average height‐specific growth rates for plants on each slope. The findings from these studies have broadened our understanding of the relationship between saguaro regeneration patterns and climate. These data have also provided pivotal information regarding regional trends of saguaro populations throughout the Sonoran Desert. As a group, the Tumamoc Hill censuses constitute one of the longest spatially explicit monitoring efforts for a single species in the world. They provide an observational baseline for future comparisons relating individual growth and population demographics to rising CO 2 levels, climate change, vegetation change, or changes in other biotic or abiotic factors.

Relationship between hydraulic conductance and citrus dwarfing by the Flying Dragon rootstock (Poncirus trifoliata L. Raft var. monstruosa) - B. Martínez-Alcántara; J. Rodriguez-Gamir; M. R. Martínez-Cuenca; D. J. Iglesias; E. Primo-Millo; M. A. Forner-Giner (Trees, 2013)

Evaluating Water Quality Failure Potential in Water Distribution Systems: A Fuzzy-TOPSIS-OWA-based Methodology - M. Shafiqul Islam; Rehan Sadiq; Manuel J. Rodriguez; Homayoun Najjaran; Alex Francisque; Mina Hoorfar (Water Resources Management, 2013)

Human–felid conflict as a further handicap to the conservation of the critically endangered Iberian lynx - Germán Garrote; Guillermo López; José M. Gil-Sánchez; Eva Rojas; Manuel Ruiz; José F. Bueno; Santiago de Lillo; Javier Rodriguez-Siles; José M. Martín; Joaquín Pérez; Maribel García-Tardío; Gerardo Valenzuela; et al. (European Journal of Wildlife Research, 2013)

Physically based evaluation of climate models over the Iberian Peninsula - Carmen Sánchez de Cos; Jose M. Sánchez-Laulhé; Carlos Jiménez-Alonso; Juan M. Sancho-Avila; Ernesto Rodriguez-Camino (Climate Dynamics, 2013)

Virtual Treatment of Basilar Aneurysms Using Shape Memory Polymer Foam - J. M. Ortega; J. Hartman; J. N. Rodriguez; D. J. Maitland (Annals of Biomedical Engineering, 2013)

One hundred and six years of population and community dynamics of Sonoran Desert Laboratory perennials - Susana Rodriguez-Buritica; Helen Raichle; Robert H. Webb; Raymond M. Turner; Larry Venable (Ecology, 2013)
This data set constitutes all information associated with the Spalding‐Shreve permanent vegetation plots from 1906 through 2012, which is the longest‐running plant monitoring program in the world. The program consists of detailed maps of all Sonoran Desert perennial plants in 30 permanent plots located on Tumamoc Hill, near Tucson, Arizona, USA. Most of these plots are 10 m × 10 m quadrats that were established by Volney Spalding and Forrest Shreve between 1906 and 1928. Analyses derived from these data have been pivotal in testing early theories on plant community succession, plant life history traits, plant longevity, and population dynamics. One of the major contributions of this data set is the species‐specific demographic traits that derived from estimating individual plant trajectories for more than 106 years. Further use of these data might shed light on spatially explicit population and community dynamics, as well as long‐term changes attributable to global change. Data presented here consist of digital versions of original maps created between 1906 and 1984 and digital data from recent censuses between 1993 and 2012. Attributes associated with these maps include location and coverage of all shrubs, and in some cases, plant height. In addition, we present plot‐specific summaries of plant cover and density for each census year and all other information collected, including seedling counts, grass coverage, and annual species enumerations. We reference the repeat photography of these plots, which began in 1906; these images are stored at the Desert Laboratory Collection of Repeat Photography in Tucson. Initial data collection consisted of grid‐mapping the plots manually on graph paper; starting in 1993, Total Stations (which allow a direct digitalization, and more accurate mapping) were used to survey root crowns and canopies.

A taxonomic and distributional study of the rhodolith-forming species Lithothamnion muelleri (Corallinales, Rhodophyta) in the Eastern Pacific Ocean - Nestor M. Robinson; G.I. Hansen; C. Fernandez-Garcia; R. Riosmena-Rodriguez (Algae, 2013)

Investigations into the differential reactivity of endogenous and exogenous mercury species in coastal sediments - S. Bouchet; P. Rodriguez-Gonzalez; R. Bridou; M. Monperrus; E. Tessier; P. Anschutz; R. Guyoneaud; D. Amouroux (Environmental Science and Pollution Research, 2013)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

Biodiversity and distribution patterns of planktonic cnidarians in S an M atías G ulf, P atagonia, A rgentina - Elena Guerrero; Josep‐María Gili; Carolina Rodriguez; Enilma M. Araujo; Antonio Canepa; Albert Calbet; Gabriel Genzano; Hermes W. Mianzan; Raúl A. González (Marine Ecology, 2013)
The special location (40–42°S in the S outhwestern A tlantic O cean) and the hydrodynamic regime (limited water exchange with open ocean) in S an M atías G ulf ( A rgentina) seem to produce a particular fauna of planktonic cnidarians whose their abundances are mainly shaped by the G ulf circulation. Four oceanographic cruises, covering 93 stations in three different seasons during 2007 and 2008 were carried out to quantify species richness and abundance, as well as to analyse the distribution of these cnidarians. We identified 20 species of hydromedusae and one siphonophore, increasing the total number of hydromedusae for the area to 23. This value is similar to the one found in the abutting A rgentine continental shelf (20), but with a different assemblage composition. Hydromedusae abundances found were low, except for a bloom of the L eptomedusa O belia spp. during the cold season. The only siphonophore found in the area, P yrostephos vanhoeffeni , has previously been thought to be endemic to A ntarctic and sub‐ A ntarctic waters, this being the first record for temperate waters of the S outhwest A tlantic O cean.

Cr(VI) Adsorption and Desorption on Soils and Biosorbents - M. T. Fernández-Pazos; B. Garrido-Rodriguez; J. C. Nóvoa-Muñoz; M. Arias-Estévez; M. J. Fernández-Sanjurjo; A. Núñez-Delgado; E. Álvarez (Water, Air, & Soil Pollution, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Compressive sensing scalp EEG signals: implementations and practical performance - Amir M. Abdulghani; Alexander J. Casson; Esther Rodriguez-Villegas (Medical & Biological Engineering & Computing, 2012)

Kinetics of biodegradation of diesel fuel by enriched microbial consortia from polluted soils - E. Moliterni; R. G. Jiménez-Tusset; M. Villar Rayo; L. Rodriguez; F. J. Fernández; J. Villaseñor (International Journal of Environmental Science and Technology, 2012)

Effect of stock type characteristics and time of planting on field performance of aspen (Populus tremuloides Michx.) seedlings on boreal reclamation sites - Simon M. Landhäusser; Javier Rodriguez-Alvarez; Eckehart H. Marenholtz; Victor J. Lieffers (New Forests, 2012)

Civil nuclear power at risk of tsunamis - Joaquin Rodriguez-Vidal; Jose M. Rodriguez-Llanes; Debarati Guha-Sapir (Natural Hazards, 2012)

Prevention of group B streptococcal neonatal disease revisited. The DEVANI European project - J. Rodriguez-Granger; J. C. Alvargonzalez; A. Berardi; R. Berner; M. Kunze; M. Hufnagel; P. Melin; A. Decheva; G. Orefici; C. Poyart; J. Telford; A. Efstratiou; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

A Common View of the Opportunities, Challenges, and Research Actions for Pongamia in Australia - Helen T. Murphy; Deborah A. O’Connell; Gary Seaton; R. John Raison; Luis C. Rodriguez; Andrew L. Braid; Darren J. Kriticos; Tom Jovanovic; Amir Abadi; Michael Betar; Heather Brodie; Malcolm Lamont; et al. (BioEnergy Research, 2012)

Zygomycosis Caused by Rhizopus microsporus and Rhizopus oryzae in Madhya Pradesh (M.P.) Central India: A Report of Two Cases - Shesh R. Nawange; S. M. Singh; J. Naidu; S. Jain; T. Nagpal; D. S. Behrani; E. Mellado; J. L. Rodriguez Tudela (Mycopathologia, 2012)

The Garzón Massif, Colombia-a new ultrahigh-temperature metamorphic complex in the Early Neoproterozoic of northern South America - U. Altenberger; D. M. Mejia Jimenez; C. Günter; G. I. Sierra Rodriguez; F. Scheffler; R. Oberhänsli (Mineralogy and Petrology, 2012)

Morphological variability of intertidal Eisenia arborea (Laminariales, Ochrophyta) at Punta Eugenia, Baja California Sur - Gloria M. Parada; Rafael Riosmena-Rodriguez; Enrique A. Martinez; Gustavo Hernandez-Carmona (Algae, 2012)

Towards the standardisation of the neuroblastoma (neuro-2a) cell-based assay for ciguatoxin-like toxicity detection in fish: application to fish caught in the Canary Islands - A. Caillaud; H. Eixarch; P. de la Iglesia; M. Rodriguez; L. Dominguez; K.B. Andree; J. Diogène (Food Additives & Contaminants: Part A, 2012)

Doubled haploids in tropical maize: II. Quantitative genetic parameters for testcross performance - Vanessa Prigge; Raman Babu; Biswanath Das; M. Hernández Rodriguez; Gary N. Atlin; Albrecht E. Melchinger (Euphytica, 2012)

Aberrant epigenetic regulation of bromodomain Brd4 in human colon cancer - R. M. Rodriguez; C. Huidobro; R. G. Urdinguio; C. Mangas; B. Soldevilla; G. Domínguez; F. Bonilla; A. F. Fernandez; M. F. Fraga (Journal of Molecular Medicine, 2012)

Emission of volatile compounds by Erwinia amylovora: biological activity in vitro and possible exploitation for bacterial identification - Francesco Spinelli; Antonio Cellini; Joel L. Vanneste; Maria T. Rodriguez-Estrada; Guglielmo Costa; Stefano Savioli; Frans J. M. Harren; Simona M. Cristescu (Trees, 2012)

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

Establishing a community partnership to optimize recruitment of African American pedigrees for a genetic epidemiology study - Heather M. Ochs-Balcom; Elisa M. Rodriguez; Deborah O. Erwin (Journal of Community Genetics, 2011)

Differences in atmospheric emissions of Poaceae pollen and Lol p 1 allergen - Delia Fernández-González; F. Javier Rodriguez Rajo; Zulima González Parrado; Rosa M. Valencia Barrera; Victoria Jato; Stella Moreno Grau (Aerobiologia, 2011)

Non-redox-active lipoate derivates disrupt cancer cell mitochondrial metabolism and are potent anticancer agents in vivo - Zuzana Zachar; James Marecek; Claudia Maturo; Sunita Gupta; Shawn D. Stuart; Katy Howell; Alexandra Schauble; Joanna Lem; Arin Piramzadian; Sameer Karnik; King Lee; Robert Rodriguez; et al. (Journal of Molecular Medicine, 2011)

Strategies for B-lymphocyte repertoire remodeling in transplantation tolerance - Kumar Vivek; Moiz M. Mustafa; Eduardo Rodriguez; Robert R. Redfield; Ronald F. Parsons; Susan Rostami; Thi-Sau Migone; Michael P. Cancro; Ali Naji; Hooman Noorchashm (Immunologic Research, 2011)

On the effects of the ionospheric disturbances on precise point positioning at equatorial latitudes - B. Moreno; S. Radicella; M. C. de Lacy; M. Herraiz; G. Rodriguez-Caderot (GPS Solutions, 2011)

Using disaster footprints, population databases and GIS to overcome persistent problems for human impact assessment in flood events - Debarati Guha-Sapir; Jose M. Rodriguez-Llanes; Thomas Jakubicka (Natural Hazards, 2011)

Phenotypic and molecular characterization of selected tomato recombinant inbred lines derived from the cross Solanum lycopersicum × S. pimpinellifolium - GUILLERMO R. PRATTA; GUSTAVO R. RODRIGUEZ; ROXANA ZORZOLI; ESTELA M. VALLE; LILIANA A. PICARDI (Journal of Genetics, 2011)

Shotgun Proteomic Analysis of Emiliania huxleyi, a Marine Phytoplankton Species of Major Biogeochemical Importance - Bethan M. Jones; Richard J. Edwards; Paul J. Skipp; C. David O’Connor; M. Debora Iglesias-Rodriguez (Marine Biotechnology, 2011)

Characterization of root-nodulating bacteria associated to Prosopis farcta growing in the arid regions of Tunisia - A. Fterich; M. Mahdhi; M. A. Caviedes; E. Pajuelo; R. Rivas; I. D. Rodriguez-Llorente; M. Mars (Archives of Microbiology, 2011)

Impact of administration of vancomycin or linezolid to critically ill patients with impaired renal function - O. Rodriguez Colomo; F. Álvarez Lerma; M.I. González Pérez; J-M. Sirvent; M. García Simón (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Proteomic Analysis of HIV-Infected Macrophages - Loyda M. Meléndez; Krystal Colon; Linda Rivera; Eillen Rodriguez-Franco; Dianedis Toro-Nieves (Journal of Neuroimmune Pharmacology, 2011)

Predisposition of cows to mastitis in non-infected mammary glands: effects of dietary-induced negative energy balance during mid-lactation on immune-related genes - Kasey M. Moyes; James K. Drackley; Dawn E. Morin; Sandra L. Rodriguez-Zas; Robin E. Everts; Harris A. Lewin; Juan J. Loor (Functional & Integrative Genomics, 2011)

Macromolecules in phloem exudates—a review - Craig A. Atkins; Penny M. C. Smith; Caren Rodriguez-Medina (Protoplasma, 2011)

Rapid identification of yeasts from positive blood culture bottles by pyrosequencing - I. Quiles-Melero; J. García-Rodriguez; M. P. Romero-Gómez; P. Gómez-Sánchez; J. Mingorance (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Effect of the Antimicrobial Peptide Tritrpticin on the In Vitro Viability and Growth of Trichomonas vaginalis - Veronica V. Infante; Alma D. Miranda-Olvera; Luis M. De Leon-Rodriguez; Fernando Anaya-Velazquez; Mayra C. Rodriguez; Eva E. Avila (Current Microbiology, 2011)

Differential Effect of Lactobacillus johnsonii BFE 6128 on Expression of Genes Related to TLR Pathways and Innate Immunity in Intestinal Epithelial Cells - Stephanie Seifert; Manuel Rodriguez Gómez; Bernhard Watzl; Wilhelm H. Holzapfel; Charles M. A. P. Franz; María G. Vizoso Pinto (Probiotics and Antimicrobial Proteins, 2010)

Communicating with Cancer Patients: What Areas do Physician Assistants Find Most Challenging? - Patricia A. Parker; Alicia C. Ross; Maura N. Polansky; J. Lynn Palmer; M. Alma Rodriguez; Walter F. Baile (Journal of Cancer Education, 2010)

Presence of Symbiodinium spp. in macroalgal microhabitats from the southern Great Barrier Reef - D. E. Venera-Ponton; G. Diaz-Pulido; M. Rodriguez-Lanetty; O. Hoegh-Guldberg (Coral Reefs, 2010)

Bond-based linear indices of the non-stochastic and stochastic edge-adjacency matrix. 1. Theory and modeling of ChemPhys properties of organic molecules - Yovani Marrero-Ponce; Eugenio R. Martínez-Albelo; Gerardo M. Casañola-Martín; Juan A. Castillo-Garit; Yunaimy Echevería-Díaz; Vicente Romero Zaldivar; Jan Tygat; José E. Rodriguez Borges; Ramón García-Domenech; Francisco Torrens; Facundo Pérez-Giménez (Molecular Diversity, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Molecular, Biochemical, and Organismal Analyses of Tomato Plants Simultaneously Attacked by Herbivores from Two Feeding Guilds - Cesar R. Rodriguez-Saona; Richard O. Musser; Heiko Vogel; Sue M. Hum-Musser; Jennifer S. Thaler (Journal of Chemical Ecology, 2010)

Coordinated and sequential activation of neutral and acidic DNases during interdigital cell death in the embryonic limb - J. A. Montero; C. I. Lorda-Diez; A. C. Certal; N. Moreno; J. Rodriguez-Leon; A. Torriglia; J. M. Hurle (Apoptosis, 2010)

Hepatitis A Virus: State of the Art - Rosa M. Pintó; M. Isabel Costafreda; Francisco J. Pérez-Rodriguez; Lucía D’Andrea; Albert Bosch (Food and Environmental Virology, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Characterization of three sect. Caulopterae species (Baccharis-Asteraceae) inferred from morphoanatomy, polypeptide profiles and spectrophotometry data - M. V. Rodriguez; M. L. Martínez; A. A. Cortadi; A. Bandoni; D. A. Giuliano; S. J. Gattuso; M. A. Gattuso (Plant Systematics and Evolution, 2010)

Nitrogen-Use Efficiency in Relation to Different Forms and Application Rates of Se in Lettuce Plants - Juan J. Ríos; Begoña Blasco; Luis M. Cervilla; Maria M. Rubio-Wilhelmi; Miguel A. Rosales; Eva Sanchez-Rodriguez; Luis Romero; Juan M. Ruiz (Journal of Plant Growth Regulation, 2010)

Metal–bipyridine complexes in DNA backbones and effects on thermal stability - Mildred M. Rodriguez-Ramos; Jonathan J. Wilker (JBIC Journal of Biological Inorganic Chemistry, 2010)

Zooplankton response to shading effects of free-floating plants in shallow warm temperate lakes: a field mesocosm experiment - M. S. Fontanarrosa; G. Chaparro; P. de Tezanos Pinto; P. Rodriguez; I. O’Farrell (Hydrobiologia, 2010)

Evaluating Lynch syndrome in very early onset colorectal cancer probands without apparent polyposis - Kory W. Jasperson; Thuy M. Vu; Angela L. Schwab; Deborah W. Neklason; Miguel A. Rodriguez-Bigas; Randall W. Burt; Jeffrey N. Weitzel (Familial Cancer, 2010)

Geomorphological reconstruction and morphometric modelling applied to past volcanism - A. Rodriguez-Gonzalez; J. L. Fernandez-Turiel; F. J. Perez-Torrado; D. Gimeno; M. Aulinas (International Journal of Earth Sciences, 2010)

Season and size effects: changes in the quality of gilthead sea bream (Sparus aurata L.) - R. RODRIGUEZ; E. FOUNTOULAKI; K. GRIGORAKIS; M. ALEXIS; R. FLOS (Mediterranean Marine Science, 2010)
The aim of this study was to investigate the potential effects of the harvesting season and fish size on the final quality of cage farmed gilthead sea bream (Sparus aurata). Morphometric analysis, fat stores estimation, fillet composition analysis, fillet fatty acids profile determination and sensory analysis were carried out on a commercially-sized cage farmed gilthead sea bream (Sparus aurata L.) population in April, June, July and November. Both season and size had a significant effect in morphometric characteristics. The most pronounced size effect was the change of fish shape, becoming rounder with fish growth, the increase of filleting yield and condition index. An increase of both peritoneal and perivisceral fat was observed in summer months. In general size had little effect on muscle composition. A significant size effect was observed in the fillet lipid content, which increased with it. Fillet lipid content was unexpected lower in the warm period (June-July). This can be possibly attributed to feeding restrictions that may have occurred, due to anoxic incidents related to high temperatures.Slight seasonal differentiations occurred in the muscle fatty acids. No significant differences were found in the organoleptic characteristics of the two size groups compared.

Ploidy levels of Dioscorea alata L. germplasm determined by flow cytometry - J. Obidiegwu; E. Rodriguez; E. Ene-Obong; J. Loureiro; C. Muoneke; C. Santos; M. Kolesnikova-Allen; R. Asiedu (Genetic Resources and Crop Evolution, 2010)

Dendritic vulnerability in neurodegenerative disease: insights from analyses of cortical pyramidal neurons in transgenic mouse models - Jennifer I. Luebke; Christina M. Weaver; Anne B. Rocher; Alfredo Rodriguez; Johanna L. Crimins; Dara L. Dickstein; Susan L. Wearne; Patrick R. Hof (Brain Structure and Function, 2010)

Density-dependence of functional development in spiking cortical networks grown in vitro - Michael I. Ham; Vadas Gintautas; Marko A. Rodriguez; Ryan A. Bennett; Cara L. Santa Maria; Luìs M. A. Bettencourt (Biological Cybernetics, 2010)

Ploidy level studies on the Dioscorea cayenensis/Dioscorea rotundata complex core set - J. Obidiegwu; J. Loureiro; E. Ene-Obong; E. Rodriguez; M. Kolesnikova-Allen; C. Santos; C. Muoneke; R. Asiedu (Euphytica, 2009)

Long‐term transpiration change with rainfall decline in a Mediterranean Quercus ilex forest - J. M. LIMOUSIN; S. RAMBAL; J. M. OURCIVAL; A. ROCHETEAU; R. JOFFRE; R. RODRIGUEZ‐CORTINA (Global Change Biology, 2009)
In the Mediterranean basin, precipitation is expected to decline as a consequence of climate change. The response of a Quercus ilex forest in southern France to such a decline in water availability was studied using a 4‐year throughfall exclusion experiment. Seasonal courses of sap flow and leaf water potential were obtained from 2004 to 2007 and used to characterize tree water relations in a control and a dry treatment. The experiment reduced the average precipitation input to the soil by 29%, and resulted in a 23% reduction in annual transpiration. Soil water potential was significantly lower in the dry treatment only during summer drought, but transpiration was reduced all year round even during well‐watered periods. Despite a tight stomatal control over transpiration, whole‐tree hydraulic conductance was found to be lower in the trees growing in the driest conditions. This reduction in water transport capacity was observed jointly with a reduction in leaf transpiring area. Canopy leaf area decreased by 18% in the dry treatment as a consequence of the throughfall exclusion, which was found to validate the ecohydrological equilibrium theory.

Association of matrix metalloproteinase-2 gene promoter polymorphism with myocardial infarction susceptibility in a Mexican population - Ivan Delgado-Enciso; Nelida A. Gonzalez-Hernandez; Luz M. Baltazar-Rodriguez; Rebeca O. Millan-Guerrero; Oscar Newton-Sanchez; Alfonso Bayardo-Noriega; Alfonso Aleman-Mireles; Irma G. Enriquez-Maldonado; Ma J. Anaya-Carrillo; Augusto Rojas-Martinez; Rocio Ortiz-Lopez (Journal of Genetics, 2009)

A Genomewide Assessment of Inbreeding Depression: Gene Number, Function, and Mode of Action - JULIEN F. AYROLES; KIMBERLY A. HUGHES; KEVIN C. ROWE; MELISSA M. REEDY; SANDRA L. RODRIGUEZ‐ZAS; JENNY M. DRNEVICH; CARLA E. CÁCERES; KEN N. PAIGE (Conservation Biology, 2009)
Although the genetic basis of inbreeding depression is still being debated, most fitness effects are thought to be the result of increased homozygosity for recessive or partially recessive deleterious alleles rather than the loss of overdominant genes. It is unknown how many loci are associated with inbreeding depression, the genes or gene pathways involved, or their mode of action. To uncover genes associated with variation in fitness following inbreeding, we generated a set of inbred lines of Drosophila melanogaster for which only the third chromosome varied among lines and measured male competitive reproductive success among these lines to estimate inbreeding depression. Male competitive reproductive success for different lines validated our prediction that equally inbred lines show variation in inbreeding depression. To begin to assess the molecular basis of inbreeding depression for male competitive reproductive success, we detected variation in whole‐genome gene expression across these inbred lines with commercially available high‐density oligonucleotide microarrays. A total of 567 genes were differentially expressed among these inbred lines, indicating that inbreeding directly or indirectly affects a large number of genes: genes that are disproportionately involved in metabolism, stress and defense responses. Subsequently, we generated a set of outbred lines by crossing the highest inbreeding depression lines to each other and contrasted gene expression between parental inbred lines and F 1 hybrids with transcript abundance as a quantitative phenotype to determine the mode of action of the genes associated with inbreeding depression. Although our results indicated that approximately 75% of all genes involved in inbreeding depression were additive, partially additive, or dominant, about 25% of all genes expressed patterns of overdominance. These results should be viewed with caution given that they may be confounded by issues of statistical inference or associative overdominance.

Shallow lake trophic status linked to late Holocene climate and human impacts - Matthew N. Waters; Michael F. Piehler; Antonio B. Rodriguez; Joseph M. Smoak; Thomas S. Bianchi (Journal of Paleolimnology, 2009)

Melatonin concentrations during larval and postlarval development of gilthead sea bream Sparus auratus : more than a time‐keeping molecule? - H. Kalamarz; M. Nietrzeba; J. Fuentes; G. Martinez‐Rodriguez; J.M. Mancera; E. Kulczykowska (Journal of Fish Biology, 2009)
In this study, melatonin (MEL) and thyroxine (T 4 ) concentrations were measured during larval and postlarval development of gilthead sea bream Sparus auratus Hormones were measured in whole bodies of larvae or the head and trunk of postlarvae after 67 days of exposure to constant light, 24L:0D, constant darkness, 0L:24D or 12L:12D and in the plasma of 6 month juveniles kept under the 12L:12D, 0L:24D and 24L:0D regimes. High MEL concentrations in larvae suggested a distinct role of MEL in early organogenesis and development of S. auratus . In larvae, the gastro‐intestinal tract seemed to be an important extrapineal and extraretinal source of MEL. No endogenous rhythm of MEL synthesis was demonstrated in 67 day larvae; however, in 6 month juveniles, it was evident. At early ontogenesis of S. auratus , the role of MEL is probably related mostly to the control of development and protection against free radicals, whereas its action as a time‐keeping molecule develops later. The increase in T 4 concentration during the S. auratus larva–juvenile transition, i.e . between 50 and 70 days post‐hatch, which was observed concurrently with the decrease of MEL concentration, may suggest an inverse relationship between T 4 and MEL.

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Molecular characterization of a foot-and-mouth disease virus containing a 57-nucleotide insertion in the 3′untranslated region - M. E. Piccone; S. Pauszek; J. Pacheco; E. Rieder; E. Kramer; L. L. Rodriguez (Archives of Virology, 2009)

Methamphetamine Enhances HIV-1 Infectivity in Monocyte Derived Dendritic Cells - Madhavan P. N. Nair; Zainulabedin M. Saiyed; Narayanan Nair; Nimisha H. Gandhi; Jose W. Rodriguez; Nawal Boukli; Elias Provencio-Vasquez; Robert M. Malow; Maria Jose Miguez-Burbano (Journal of Neuroimmune Pharmacology, 2009)

Sex Pheromone of the Scarab Beetle Phyllophaga (Phytalus) georgiana (Horn) - Paul S. Robbins; Satoshi Nojima; Sridhar Polavarapu; Albrecht M. Koppenhöfer; Cesar Rodriguez-Saona; Robert J. Holdcraft; Nancy H. Consolie; Daniel C. Peck; Wendell L. Roelofs (Journal of Chemical Ecology, 2009)

Biological characterization of young and aged embryogenic cultures of Pinus pinaster (Ait.) - K. Klimaszewska; C. Noceda; G. Pelletier; P. Label; R. Rodriguez; M. A. Lelu-Walter (In Vitro Cellular & Developmental Biology - Plant, 2009)

Morphological and genetic variation in Aegilops geniculata from Algeria - H. Bandou; M. Rodriguez-Quijano; J. M. Carrillo; G. Branlard; M. Zaharieva; P. Monneveux (Plant Systematics and Evolution, 2009)

The Mitochondrial ATP-Sensitive Potassium Channel Blocker 5-Hydroxydecanoate Inhibits Toxicity of 6-Hydroxydopamine on Dopaminergic Neurons - J. Rodriguez-Pallares; J. A. Parga; B. Joglar; M. J. Guerra; J. L. Labandeira-Garcia (Neurotoxicity Research, 2009)

Proteomic analyses of monocyte-derived macrophages infected with human immunodeficiency virus type 1 primary isolates from Hispanic women with and without cognitive impairment - Dm Toro-Nieves; Y Rodriguez; M Plaud; P Ciborowski; F Duan; J Pérez Laspiur; V Wojna; LM Meléndez (Journal of NeuroVirology, 2009)

Dehydrin gene expression provides an indicator of low temperature and drought stress: transcriptome-based analysis of Barley (Hordeum vulgare L.) - Livia Tommasini; Jan T. Svensson; Edmundo M. Rodriguez; Abdul Wahid; Marina Malatrasi; Kenji Kato; Steve Wanamaker; Josh Resnik; Timothy J. Close (Functional & Integrative Genomics, 2008)

Rineloricaria isaaci (Loricariidae: Loricariinae), a new species of loricariid catfish from the Uruguay River basin - M. Rodriguez; A. Miquelarena (Journal of Fish Biology, 2008)
Rineloricaria isaaci is described from tributaries of the Uruguay River basin in Argentina, Brazil and Uruguay. The new species is distinguished by having a long and wide area of naked skin at the snout tip, surpassing the anteriormost pore of the infraorbital ramus of the sensory canal, approximately in the middle of the third postrostral plate, and by its particular sexual dimorphism characterized by the long pectoral and pelvic fins of mature males.

Results of a short study of interactions of cetaceans and longline fisheries in Atlantic waters: environmental correlates of catches and depredation events - Gema Hernandez-Milian; Sabine Goetz; Catuxa Varela-Dopico; José Rodriguez-Gutierrez; Jorge Romón-Olea; José R. Fuertes-Gamundi; Edelmiro Ulloa-Alonso; Nick J. C. Tregenza; Andy Smerdon; Monserrat G. Otero; Vicente Tato; Jianjun Wang; et al. (Hydrobiologia, 2008)

Transcriptional activity and distribution of splicing machinery elements during Hyacinthus orientalis pollen tube growth - K. Zienkiewicz; A. Zienkiewicz; M. I. Rodriguez-Garcia; D. J. Smoliński; M. Świdziński; E. Bednarska (Protoplasma, 2008)

CIGB-300, a novel proapoptotic peptide that impairs the CK2 phosphorylation and exhibits anticancer properties both in vitro and in vivo - Silvio E. Perea; Osvaldo Reyes; Idania Baladron; Yasser Perera; Hernán Farina; Jeovanis Gil; Arielis Rodriguez; Dania Bacardi; Jose L. Marcelo; Karelia Cosme; Marisol Cruz; Carmen Valenzuela; et al. (Molecular and Cellular Biochemistry, 2008)

Role of Copper and Homocysteine in Pressure Overload Heart Failure - William M. Hughes; Walter E. Rodriguez; Dorothea Rosenberger; Jing Chen; Utpal Sen; Neetu Tyagi; Karni S. Moshal; Thomas Vacek; Y. James Kang; Suresh C. Tyagi (Cardiovascular Toxicology, 2008)

Prevalence of BRCA1 and BRCA2 mutations in breast cancer patients from Cuba - Rolando Comacho Rodriguez; Antonio Alejandro Esperon; Ramon Ropero; Maria Caridad Rubio; Ronald Rodriguez; Rosa M. Ortiz; Juan J. Lence Anta; Mario de los Rios; Deyanira Carnesolta; Maria C. del Olivera; Somalia Stiu Vansam; Robert Royer; et al. (Familial Cancer, 2008)

Expression of WUSCHEL in Coffea canephora causes ectopic morphogenesis and increases somatic embryogenesis - A. Arroyo-Herrera; A. Ku Gonzalez; R. Canche Moo; F. R. Quiroz-Figueroa; V. M. Loyola-Vargas; L. C. Rodriguez-Zapata; C. Burgeff D′Hondt; V. M. Suárez-Solís; E. Castaño (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Analysis of HLA class I expression in progressing and regressing metastatic melanoma lesions after immunotherapy - Rafael Carretero; José M. Romero; Francisco Ruiz-Cabello; Isabel Maleno; Felix Rodriguez; Francisco M. Camacho; Luis M. Real; Federico Garrido; Teresa Cabrera (Immunogenetics, 2008)

Developing UK farmers' institutional capacity to defend their water rights and effectively manage limited water resources - W. Leathes; J. W. Knox; M. G. Kay; P. Trawick; J. A. Rodriguez‐Diaz (Irrigation and Drainage, 2008)
Developing farmers' institutional capacity to defend their water rights is central to sustaining irrigation farming in the UK. Increasing demand and competition for water and the introduction of new water regulations have led many farmers to re‐evaluate the security of their water rights. As a consequence, some have formed water abstractors groups, a trend which is strongest in eastern England, where irrigation is most concentrated and water resources are most stressed. “Collective choice” theory attempts to explain how institutions evolve to share common resources and what key elements are needed for them to endure over the long term. This paper compares the characteristics of four existing water abstractors groups against those of “collective choice” theory. It concludes that it is applicable in the UK context and relevant when addressing a range of emerging water management challenges. The approach taken offers a means of analysing capacity at an institutional level and suggests a way of supporting the development of existing water abstractors groups as well as developing new ones. It is argued that this approach to developing institutional capacity could be used elsewhere where problems between resource availability, environmental protection and the sustainability of agricultural production are evident. Copyright © 2008 John Wiley & Sons, Ltd.

Reducing dissolved phosphorus loading to the Salton Sea with aluminum sulfate - I. R. Rodriguez; C. Amrhein; M. A. Anderson (Hydrobiologia, 2008)

Laboratory studies on the coprecipitation of phosphate with calcium carbonate in the Salton Sea, California - I. R. Rodriguez; C. Amrhein; M. A. Anderson (Hydrobiologia, 2008)

Could krill schools significantly bias 234Th‐based carbon flux models? - Alessia M. Rodriguez y Baena; Scott W. Fowler; Michel Warnau (Limnology and Oceanography, 2008)
To test the recent hypothesis that krill schools and their molting can hinder the accuracy of 234T h‐based particle flux models under specific conditions, radiotracer experiments were conducted with northern krill, Meganyctiphanes norvegica , to examine how 23 4Th uptake and release kinetics may affect residual 234 Th concentrations in seawater. Krill rapidly took up 234 Th from seawater, reaching a steady‐state concentration factor of ~180 in less than 1 week, and strongly retained the accumulated radionuclide until molting occurred. The nine molting events observed during the 18‐d experimental period indicated that ~50% of krill whole‐body 234 Th activity was associated with the cast exoskeleton, and that a corresponding amount was rapidly adsorbed postecdysis on the newly formed cuticle. In regions characterized by the occurrence of high planktonic crustacean biomass, failure to link the presence of organisms with their effects on 234 Th dynamics in the water column may induce significant biases (in some circumstances, up to one order of magnitude) in 234 Th‐derived particulate organic carbon flux estimations or sediment trap efficiency calculations based on this method. However, because of the patchy distribution of dense aggregations of krill, the overall likelihood of such dramatic modeling artifacts is estimated to be relatively low (≤5% per sampling time).

Paleoenvironmental evolution of the Pliocene Villarroya Lake, northern Spain, from stable isotopes and trace-element geochemistry of ostracods and molluscs - P. Anadón; R. Utrilla; A. Vázquez; M. Martín-Rubio; J. Rodriguez-Lázaro; F. Robles (Journal of Paleolimnology, 2008)

Characteristics of Streptococcus bovis endocarditis and its differences with Streptococcus viridans endocarditis - J. Corredoira; M. P. Alonso; A. Coira; E. Casariego; C. Arias; D. Alonso; J. Pita; A. Rodriguez; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Characterization of typo-, regio-, and stereo-selectivities of babaco latex lipase in aqueous and organic media - E. Cambon; J. A. Rodriguez; M. Pina; V. Arondel; F. Carriere; F. Turon; J. Ruales; P. Villeneuve (Biotechnology Letters, 2008)

Genetic characterization and molecular epidemiology of foot-and-mouth disease viruses isolated from Afghanistan in 2003–2005 - Kate R. Schumann; Nick J. Knowles; Paul R. Davies; Rebecca J. Midgley; Jean-Francois Valarcher; Abdul Quader Raoufi; Thomas S. McKenna; William Hurtle; James P. Burans; Barbara M. Martin; Luis L. Rodriguez; Tammy R. Beckham (Virus Genes, 2008)

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women - Luz M. Baltazar-Rodriguez; Aristoteles Anaya-Ventura; Maricela Andrade-Soto; Elisa A. Monrroy-Guizar; Jose R. Bautista-Lam; Gregorio Jonguitud-Olguin; Friedman R. Cepeda-Lopez; Veronica A. Centeno-Aguilar; Nelida A. Gonzalez-Hernandez; Alejandro D. Soriano-Hernández; Mario Ramirez-Flores; Angel Lugo-Trampe; et al. (Biochemical Genetics, 2008)

Simultaneous use of the X‐ and Y‐chromosome genes SMCX , SMCY , and DBY for sex determination in the Florida manatee ( Trichechus manatus latirostris ) - Michael D. Tringali; Michelle C. Davis; Marta A. Rodriguez‐lopez; Ellen E. Bolen; Jamie G. Sullivan; Elsa M. Haubold (Marine Mammal Science, 2008)

Nickel Exposure Enhances the Susceptibility of Lichens Usnea amblyoclada and Ramalina celastri to Urban Atmospheric Pollutants - J. H. Rodriguez; H. A. Carreras; M. L. Pignata; C. M. González (Archives of Environmental Contamination and Toxicology, 2007)

Ecotoxicity Assessment of River Sediments and a Critical Evaluation of Some of the Procedures Used in the Aquatic Oligochaete Tubifex tubifex Chronic Bioassay - Z. Maestre; M. Martinez-Madrid; P. Rodriguez; T. Reynoldson (Archives of Environmental Contamination and Toxicology, 2007)

In vitro activity of temocillin against prevalent extended-spectrum beta-lactamases producing Enterobacteriaceae from Belgian intensive care units - Y. Glupczynski; T.-D. Huang; C. Berhin; G. Claeys; M. Delmée; L. Ide; G. Ieven; D. Pierard; H. Rodriguez-Villalobos; M. Struelens; J. Vaneldere (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Diterpenoid alkaloids from Delphinium gracile - M. Reina; R. Mancha; A. Gonzalez-Coloma; M. Bailen; M. L. Rodriguez; R. A. Martinez-Diaz (Natural Product Research, 2007)

A marker-assisted backcross approach for developing submergence-tolerant rice cultivars - C. N. Neeraja; R. Maghirang-Rodriguez; A. Pamplona; S. Heuer; B. C. Y. Collard; E. M. Septiningsih; G. Vergara; D. Sanchez; K. Xu; A. M. Ismail; D. J. Mackill (Theoretical and Applied Genetics, 2007)

Economic and management characterization of dehesa farms: implications for their sustainability - P. Gaspar; F. J. Mesías; M. Escribano; A. Rodriguez de Ledesma; F. Pulido (Agroforestry Systems, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Molecular genetics of human growth hormone, insulin-like growth factors and their pathways in common disease - Santiago Rodriguez; Tom R. Gaunt; Ian N. M. Day (Human Genetics, 2007)

Identification of two meridianins from the crude extract of the tunicate Aplidium meridianum by tandem mass spectrometry - A. M. Seldes; M. F. Rodriguez Brasco; L. Hernandez Franco; J. A. Palermo (Natural Product Research, 2007)

Hydrodynamics, mass transfer and rheological studies of gibberellic acid production in an airlift bioreactor - M. C. Chavez-Parga; O. Gonzalez-Ortega; M. L. X. Negrete-Rodriguez; L. Medina-Torres; Eleazar M. Escamilla Silva (World Journal of Microbiology and Biotechnology, 2007)

Particulate organic carbon : natural radionuclide ratios in zooplankton and their freshly produced fecal pellets from the NW Mediterranean (MedFlux 2005) - Alessia M. Rodriguez y Baena; Scott W. Fowler; Juan Carlos Miquel (Limnology and Oceanography, 2007)
To discern controls on particulate organic carbon (POC) : natural radionuclide (RN) ratio variability in order to enhance the accuracy of water column radionuclide‐based carbon flux estimates, 234 Th, 210 Po, and POC were analyzed in seven size classes of mixed micro‐ and mesoplankton (1‐1,500‐µm size range), in larger zooplankton from different taxa (salps, euphausiids, copepods, pteropods), and in freshly produced feces from zooplankton collected during spring in the NW Mediterranean. POC:RN ratios in zooplankton ranged between 120 and 11,600 and between 89 and 9,200 µmol dpm −1 for 234 Th and 210 Po, respectively. In fecal pellets, POC:RN ratios were one to three orders of magnitude lower for 234 Th and 3‐fold to 30‐fold lower for 210 Po; the only exception was euthecosome pteropods, which had a higher POC: 210 Po ratio in their pellets than in their whole bodies. Significant increases in POC:RN ratios with organism size were best described by a power relationship for POC: 234 Th (p 210 Po (with a constant POC: 210 Po ratio above 70 µm; p 234 Th and food chain bioaccumulation for 210 Po. This inference is further supported by the observation that, for the >33‐µm size classes, 210 Po specific activity correlates negatively with the surface : volume ratio, while 234 Th correlates positively with it (p 234 Th flux; however, it could considerably bias similar measurements of 210 Po flux as well as those of POC:RN ratios.

Genetic mapping of the bean golden yellow mosaic geminivirus resistance gene bgm-1 and linkage with potyvirus resistance in common bean (Phaseolus vulgaris L.) - Matthew W. Blair; Lina M. Rodriguez; Fabio Pedraza; Francisco Morales; Stephen Beebe (Theoretical and Applied Genetics, 2006)

Nuclear DNA content of Vitis vinifera cultivars and ploidy level analyses of somatic embryo-derived plants obtained from anther culture - F. Leal; J. Loureiro; E. Rodriguez; M. S. Pais; C. Santos; O. Pinto-Carnide (Plant Cell Reports, 2006)

A Polymerase Chain Reaction Screening Method for Rapid Detection of Microsatellites in Bacterial Artificial Chromosomes - M. F. Rodriguez; S. A. Gahr; C. E. Rexroad; Y. Palti (Marine Biotechnology, 2006)

Changing trends in etiology of bacteremia in patients with cancer - A. Safdar; G. H. Rodriguez; M. Balakrishnan; J. J. Tarrand; K. V. I. Rolston (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Temporal and spatial infection dynamics indicate recognition events in the early hours of a dinoflagellate/coral symbiosis - Mauricio Rodriguez-Lanetty; Elisha M. Wood-Charlson; Lea L. Hollingsworth; Dave A. Krupp; Virginia M. Weis (Marine Biology, 2006)

Toxicity of Santander Bay Sediments to the Euryhaline Freshwater Oligochaete Limnodrilus hoffmeisteri - P. Rodriguez; J. Arrate; M. Martinez-Madrid; T. B. Reynoldson; V. Schumacher; J. Viguri (Hydrobiologia, 2006)

A Pooled Analysis of 12 Cohort Studies of Dietary Fat, Cholesterol and Egg Intake and Ovarian Cancer - Jeanine M. Genkinger; David J. Hunter; Donna Spiegelman; Kristin E. Anderson; W. Lawrence Beeson; Julie E. Buring; Graham A. Colditz; Gary E. Fraser; Jo L. Freudenheim; R. Alexandra Goldbohm; Susan E. Hankinson; Karen L. Koenig; et al. (Cancer Causes & Control, 2006)

The effect of headspace renewal in a Temporary Immersion Bioreactor on plantain (Musa AAB) shoot proliferation and quality - S. Roels; C. Noceda; M. Escalona; J. Sandoval; M.J. Canal; R. Rodriguez; P. Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

Field Performance of Pinus radiata D. Don Produced in Nursery with Different Types of Containers - U. Ortega; J. Majada; A. Mena-Petite; J. Sanchez-Zabala; N. Rodriguez-Iturrizar; K. Txarterina; J. Azpitarte; M. Duñabeitia (New Forests, 2006)

Surfactant-Enhanced Desorption of Atrazine and Linuron Residues as Affected by Aging of Herbicides in Soil - M. S. Rodriguez-Cruz; M. J. Sanchez-Martin; M. Sanchez-Camazano (Archives of Environmental Contamination and Toxicology, 2006)

Genome-wide SNP discovery and linkage analysis in barley based on genes responsive to abiotic stress - Nils Rostoks; Sharon Mudie; Linda Cardle; Joanne Russell; Luke Ramsay; Allan Booth; Jan T. Svensson; Steve I. Wanamaker; Harkamal Walia; Edmundo M. Rodriguez; Peter E. Hedley; Hui Liu; et al. (Molecular Genetics and Genomics, 2005)

Melatonin increases the survival time of animals with untreated mammary tumours: Neuroendocrine stabilization - M. C. Saez; C. Barriga; J. J. Garcia; A. B. Rodriguez; J. Masot; E. Duran; E. Ortega (Molecular and Cellular Biochemistry, 2005)

ATM Polymorphism and hereditary nonpolyposis colorectal cancer (HNPCC) ageof onset (United States) - J. Shawn Jones; Xiangjun Gu; Patrick M. Lynch; Miguel Rodriguez-Bigas; Christopher I. Amos; Marsha L. Frazier (Cancer Causes & Control, 2005)

Characterization of Toll-like receptor 3 gene in rainbow trout (Oncorhynchus mykiss) - M. F. Rodriguez; G. D. Wiens; M. K. Purcell; Y. Palti (Immunogenetics, 2005)

Optimization of plantain (Musa AAB) micropropagation by temporary immersion system - S. Roels; M. Escalona; I. Cejas; C. Noceda; R. Rodriguez; M. J. Canal; J. Sandoval; P. Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Cellular cardiomyoplasty: development of a technique to culture human myoblasts for clinical transplantation - M. Esther Rendal Vázquez; M. Rodriguez Cabarcos; T. Diaz Román; A. Juffé Stein; N. Doménech Garcia; B. Adrio Nazar; M.J. Sánchez Dopico; C. Andión Núñez; F.J. Blanco Garcia (Cell and Tissue Banking, 2005)

Clinical characteristics and significance of Streptococcus salivarius bacteremia and Streptococcus bovis bacteremia: a prospective 16-year study - J. C. Corredoira; M. P. Alonso; J. F. García; E. Casariego; A. Coira; A. Rodriguez; J. Pita; C. Louzao; B. Pombo; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Vocal dialects, sex‐biased dispersal, and microsatellite population structure in the parrot Amazona auropalliata - TIMOTHY F. WRIGHT; ANGELICA M. RODRIGUEZ; ROBERT C. FLEISCHER (Molecular Ecology, 2005)
Geographic variation in microsatellite allele frequencies was assessed at nine sites in two regional vocal dialects of the parrot Amazona auropalliata (yellow‐naped amazon) to test for correspondence between dialects and population structure. There was no relationship between the genetic distances between individuals and their dialect membership. High rates of gene flow were estimated between vocal dialects based on genetic differentiation. In addition, 5.5% of pairs of individuals compared across the dialect boundary were estimated to be related at the level of half siblings, indicating that dispersal is ongoing. The number of effective migrants per generation between dialects estimated with the microsatellite data was roughly one‐seventh the number estimated with mitochondrial control region sequence data from the same individuals, suggesting that gene flow may be female‐biased. Together, these results suggest that the observed mosaic pattern of geographic variation in vocalizations is maintained by learning of local call types by immigrant birds after dispersal. We found no evidence that ongoing habitat fragmentation has contributed to cryptic population structure.

Dengue virus type 2 in Cuba, 1997: conservation of E gene sequence in isolates obtained at different times during the epidemic - R. Rodriguez-Roche; M. Alvarez; T. Gritsun; D. Rosario; S. Halstead; G. Kouri; E. A. Gould; M. G. Guzman (Archives of Virology, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Environmental Education as a Component of Multidisciplinary Conservation Programs: Lessons from Conservation Initiatives for Critically Endangered Fruit Bats in the Western Indian Ocean - W. J. TREWHELLA; K. M. RODRIGUEZ‐CLARK; N. CORP; A. ENTWISTLE; S. R. T. GARRETT; E. GRANEK; K. L. LENGEL; M. J. RABOUDE; P. F. REASON; B. J. SEWALL (Conservation Biology, 2005)
Pteropus livingstonii , P. voeltzkowi , and P. rodricensis are three critically endangered fruit bats from western Indian Ocean islands for which multidisciplinary conservation programs have been established that include environmental education programs (EEPs). We describe these EEPs in terms of the strategies used to achieve them and evaluate the educational and conservation outcomes and impacts of the programs. Educational outputs (including posters, stickers, videos, lesson plans, and workshops), primarily linking human needs to the ecosystem services provided by bats, were delivered to schools and community groups, and local environmental educators were trained to further develop the EEPs. Outcomes included increased local awareness about the bats and their conservation, training of environmental educators, inclusion of bat conservation and environmental issues in the school curricula, and establishment of community‐based environmental nongovernmental organizations (NGOs). Extensive prior planning, presentations in local languages, distribution of outputs through existing networks of educators, training of local educators, establishment of local environmental NGOs, and local capacity‐building were all associated with these EEPs achieving their goals in the under‐resourced island locations where these bats are found. The EEPs were also important in the development of other components of their respective conservation programs, such as population monitoring programs. Although long‐term conservation impacts, particularly tackling habitat loss, are slow to materialize and social and economic issues need to be addressed, these EEPs have already had important outcomes and have established the foundation for future conservation actions.

Isolation and cultivation of Walsby's square archaeon - Henk Bolhuis; Evelien M. te Poele; Francisco Rodriguez‐Valera (Environmental Microbiology, 2004)
Summary In 1980, A. E. Walsby described a square halophilic archaeon. This archaeon is of specific interest because of its unique shape and its abundance in hypersaline ecosystems, which suggests an important ecophysiological role. Ever since its discovery, the isolation and cultivation of ‘Walsby's square archaeon’ has been a holy grail for many microbiologists working on halophiles. Despite their abundance and easy recognition by microscopy, all cultivation attempts have failed up to now, marking the organism as one of the unculturables. Cultivation of the square archaeon is essential to understand their ecophysiological role and the nature of their unique morphologically features. Here, we report the isolation and cultivation of the enigmatic square archaeon that we propose to name Haloquadratum walsbyi . Pure cultures are easily maintained in simple artificial hypersaline media. Initial growth experiments revealed a tolerance to high concentrations of MgCl 2 (>2 M) in the presence of 3.3 M NaCl. Fresh cultures contained extraordinary large cells (>40 × 40 µm) without any visible division structures, ranking them among the largest prokaryotes known to date. The genome was estimated to contain approximately three million basepairs.

Transcripts of MYB-like genes respond to phosphorous and nitrogen deprivation in Arabidopsis - Christopher D. Todd; Peiyu Zeng; Alicia M. Rodriguez Huete; Mary Elizabeth Hoyos; Joe C. Polacco (Planta, 2004)

The Role of Fungal Symbioses in the Adaptation of Plants to High Stress Environments - Russell J. Rodriguez; Regina S. Redman; Joan M. Henson (Mitigation and Adaptation Strategies for Global Change, 2004)

High-resolution Numerical Simulation of Flow Through a Highly Sinuous River Reach - José F. Rodriguez; Fabián A. Bombardelli; Marcelo H. García; Kelly M. Frothingham; Bruce L. Rhoads; Jorge D. Abad (Water Resources Management, 2004)

Decline in Assayable Progesterone in Bovine Serum under Different Storage Conditions - T. de Castro; L. Valdez; M. Rodriguez; N. Benquet; E. Rubianes (Tropical Animal Health and Production, 2004)

Haemophilus parainfluenzae : an Underdiagnosed Pathogen of Biliary Tract Infections? - J. Frankard; H. Rodriguez-Villalobos; M. J. Struelens; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Experimental Study of the Formation of Chlorination By-Products in Potable Water of Quebec City, Canada - M. J. Rodriguez; M. Huard; J.-B. Srodes (Bulletin of Environmental Contamination and Toxicology, 2004)

Specificity of two temperate dinoflagellate?anthozoan associations from the north-western Pacific Ocean - M. Rodriguez-Lanetty; Soo-Jung Chang; Jun-Im Song (Marine Biology, 2003)

Spatial and Seasonal Variations of Water Quality in a Mediterranean Catchment: The Llobregat River (NE Spain) - J.L. Fernández-Turiel; D. Gimeno; J.J. Rodriguez; M. Carnicero; F. Valero (Environmental Geochemistry and Health, 2003)

Symbiont diversity within the widespread scleractinian coral Plesiastrea versipora , across the northwestern Pacific - M. Rodriguez-Lanetty; O. Hoegh-Guldberg (Marine Biology, 2003)

A comparative study of the expression of monoamine oxidase-A and -B mRNA and protein in non-CNS human tissues - S. D. Sivasubramaniam; C. C. Finch; M. J. Rodriguez; N. Mahy; E. E. Billett (Cell and Tissue Research, 2003)

The Effect of perturbations on phytoplankton assemblages in a deep reservoir (Vouglans, France) - M. Leitão; S.M. Morata; S. Rodriguez; J.P. Vergon (Hydrobiologia, 2003)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Comparative analysis of superfamilies of NBS-encoding disease resistance gene analogs in cultivated and wild apple species - S.-Y. Lee; J.-S. Seo; M. Rodriguez-Lanetty; D.-H. Lee (Molecular Genetics and Genomics, 2003)

An Evolutionary Approach to Understanding the Biology of Invasions: Local Adaptation and General‐Purpose Genotypes in the Weed Verbascum thapsus - Ingrid M. Parker; Joseph Rodriguez; Michael E. Loik (Conservation Biology, 2003)
The role of evolution in the invasion of non‐native species has important implications for conservation, weed science, risk assessment, and policy. In this paper we first discuss why an evolutionary perspective can be helpful and outline a range of potentially useful approaches from population biology and ecological genetics. As a case study, we then ask how adaptation and genetic structure may promote or constrain the expansion of an invasive weed, Verbascum thapsus , into high elevations in the Sierra Nevada of California. We used growth‐chamber and common‐garden experiments to assay a range of morphological and physiological traits that could influence plant fitness at high elevation. There was a significant relationship between elevation and leaf size and reflectance above 800 m, although we found no relationship between elevation and most other traits ( growth rate in warm or cool temperatures, freezing tolerance when grown in warm or cool temperatures, leaf number, rosette morphology, plant height ). We did see marked genetic differentiation among populations, possibly reflecting founder effects and a history of genetic drift. When we partitioned the phenotypic variance, there was almost no variation among maternal families within populations, limiting the potential for selection to act. The majority of the variance for all traits was among individuals within families, suggesting that environmental conditions strongly influenced the phenotype. Overall, the increasing success of V. thapsus at high elevations appears to conform more to Baker's concept of a general‐purpose genotype than to invasion by rapid adaptation.

Assessment of storage protein variation in relation to some morphological characters in a sample of Spanish landraces of common wheat (Triticum aestivum L. ssp. aestivum) - Magdalena Ruiz; E.V. Metakovsky; M. Rodriguez-Quijano; J.F. Vazquez; J.M. Carrillo (Genetic Resources and Crop Evolution, 2002)

The phylogeography and connectivity of the latitudinally widespread scleractinian coral Plesiastrea versipora in the Western Pacific - M. Rodriguez‐Lanetty; O. Hoegh‐Guldberg (Molecular Ecology, 2002)
Whereas terrestrial animal populations might show genetic connectivity within a continent, marine species, such as hermatypic corals, may have connectivity stretching to all corners of the planet. We quantified the genetic variability within and among populations of the widespread scleractinian coral, Plesiastrea versipora along the eastern Australian seaboard (4145 km) and the Ryukyu Archipelago (Japan, 681 km) using sequences of internal transcribed spacers (ITS1‐2) from ribosomal DNA. Geographic patterns in genetic variability were deduced from a nested clade analysis (NCA) performed on a parsimony network haplotype. This analysis allowed the establishment of geographical associations in the distribution of haplotypes within the network cladogram, therefore allowing us to deduce phylogeographical patterns based under models of restricted gene flow, fragmentation and range expansion. No significant structure was found among Ryukyu Archipelago populations. The lack of an association between the positions of haplotypes in the cladogram with geographical location of these populations may be accounted for by a high level of gene flow of P. versipora within this region, probably due to the strong Kuroshio Current. In contrast, strong geographical associations were apparent among populations of P. versipora along the south‐east coast of Australia. This pattern of restricted genetic connectivity among populations of P. versipora on the eastern seaboard of Australia seems to be associated with the present surface ocean current (the East Australian Current) on this side of the south‐western Pacific Ocean.

Sex Specificity in Methadone Analgesia in the Rat: A Population Pharmacokinetic and Pharmacodynamic Approach - Monica Rodriguez; M. Angeles Carlos; Ignacio Ortega; Elena Suarez; Rosario Calvo; John C. Lukas (Pharmaceutical Research, 2002)

A Framework for Assessment and Monitoring of Small Mammals in a Lowland Tropical Forest - Sergio Solari; Juan José Rodriguez; Elena Vivar; Paul M. Velazco (Environmental Monitoring and Assessment, 2002)

Body mass index, height, and postmenopausal breast cancer mortality in a prospective cohort of US women - Jennifer M. Petrelli; Eugenia E. Calle; Carmen Rodriguez; Michael J. Thun (Cancer Causes & Control, 2002)

The Bayesian approach applied to GPS ambiguity resolution. A mixture model for the discrete-real ambiguities alternative - M. C. de Lacy; F. Sansò; G. Rodriguez-Caderot; A. J. Gil (Journal of Geodesy, 2002)

Cross Reaction Between a Pan-Candida Genus Probe and Fusarium Spp. in a Fatal Case of Fusarium oxysporum Pneumonia - H. Rodriguez-Villalobos; M. Aoun; C. Heymans; J. De Bruyne; V. Duchateau; J. Verdebout; F. Crokaert (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

ICAM-1 is crucial for protection from TMEV-induced neuronal damage but not demyelination - Kristen M Drescher; Laurie J Zoecklein; Moses Rodriguez (Journal of NeuroVirology, 2002)

The Application of IUCN Red List Criteria at Regional Levels - Ulf Gardenfors; Craig Hilton-Taylor; Georgina M. Mace; Jon Paul Rodriguez (Conservation Biology, 2001)

Influence of cobalt and other microelements on the production of betalains and the growth of suspension cultures of Beta vulgaris - G. Trejo-Tapia; A. Jimenez-Aparicio; M. Rodriguez-Monroy; A. De Jesus-Sanchez; G. Gutierrez-Lopez (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

Short‐term storage of ova of common carp and tench in extenders - O. Linhart; D. Gela; M. Rodina; M. Rodriguez Gutierrez (Journal of Fish Biology, 2001)
In a study of the effect of short‐term storage on the hatching rate of common carp Cyprinus carpio and tench Tinca tinca ova in vitro in various extenders at 21° C under aerobic conditions, the best extender for 30 min storage for common carp appeared to be Dettlaff 1. This gave the same hatching rate as controls without extender (55% v. 56%). For 60 min storage of ova, the best extenders were Dettlaff 2 (24% hatching rate) and Dettlaff 3 (30%), but hatching was significantly lower than in the control (58%). In carp ovarian artificial fluid (CAF) extender, the hatching rate of common carp ova was also high after 10 min, but decreased to 12% after 30 min. In tench, the hatching rate of ova increased after 10 min storage in Dettlaff 5 extender (44%) compared to the control (41%) without extender. However, it was significantly lower after storage in Dettlaff 1, 2, 3, 4, 5 and CAF extenders for 20, 30 and 60 min, compared to controls. Malformations (10–50%) were observed in the tench second control groups without extender after 10, 20 and 30 min storage of ova.

Post-translational phosphorylation of the slow/β myosin heavy chain isoform in adult rabbit masseter muscle - Marlyanne M. Pol-Rodriguez; Gaila A. Schwartz; Arthur W. English (Journal of Muscle Research and Cell Motility, 2001)

Somatic embryogenesis in Citrus SPP.: Carbohydrate stimulation and histodifferentiation - Márcio L. Tomaz; Beatriz M. Januzzi Mendes; francisco De Assis A. Mourão Filho; Clarice G. B. Demétrio; Naratip Jansakul; Adriana P. Martinelli Rodriguez (In Vitro Cellular & Developmental Biology - Plant, 2001)

Attempts at oral pharmacological treatment of Ichthyophthirius multifiliis in rainbow trout, Oncorhynchus mykiss (Walbaum) - J L Tojo Rodriguez; M T Santamarina Fernandez (Journal of Fish Diseases, 2001)

In vitro morphogenesis of Cucumis melo var. inodorus - Liliane C. Liborio Stipp; Beatriz M. Januzzi Mendes; Sonia M. D. Stefano Piedade; Adriana P. Martinelli Rodriguez (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

The reliability of immunohistochemistry as a prescreening method for the diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) – Results of an international collaborative study - Wolfram Müller; Lawrence J. Burgart; Ruth Krause-Paulus; Stephen N. Thibodeau; M. Almeida; T. Brocker Edmonston; C. R. Boland; C. Sutter; J. R. Jass; A. Lindblom; J. Lubinski; K. MacDermot; et al. (Familial Cancer, 2001)

Molecular linkage mapping in rye (Secale cereale L.) - X.-F. Ma; M. K. Wanous; K. Houchins; M. A. Rodriguez Milla; P. G. Goicoechea; Z. Wang; M. Xie; J. P. Gustafson (Theoretical and Applied Genetics, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Tubal sterilization and risk of breast cancer mortality in US women - Eugenia E. Calle; Carmen Rodriguez; Kimberly A. Walker; Phyllis A. Wingo; Jennifer M. Petrelli; Michael J. Thun (Cancer Causes & Control, 2001)

A novel approach for the definition of the inorganic medium components for micropropagation of yellow passionfruit (Passiflora edulis sims. F. Flavicarpa Deg.) - A. C. B. de A. Monteiro; E. N. Higashi; A. N. Gonçalves; A. P. M. Rodriguez (In Vitro Cellular & Developmental Biology - Plant, 2000)

Development of an algorithm identifying maximally diverse core collections - Jane M. Marita; Julie M. Rodriguez; James Nienhuis (Genetic Resources and Crop Evolution, 2000)

Linkage mapping and QTL analysis in coconut (Cocos nucifera L.) - A. Herrán; L. Estioko; D. Becker; M. J. B. Rodriguez; W. Rohde; E. Ritter (Theoretical and Applied Genetics, 2000)

Bean germplasm evaluation for anthracnose resistance and characterization of agronomic traits: A new physiological strain of Colletotrichum lindemuthianum infecting Phaseolus vulgaris L. in Spain - Ma.T. Fernández; M. Fernández; A. Casares; R. Rodriguez; M. Fueyo (Euphytica, 2000)

Transformation of floral organs with GFP in Medicago truncatula - K. Kamaté; I. D. Rodriguez-Llorente; M. Scholte; P. Durand; P. Ratet; E. Kondorosi; A. Kondorosi; T. H. Trinh (Plant Cell Reports, 2000)

El Niño influence on streamflow forecasting - J. Kelman; A. de M. Vieira; J. E. Rodriguez-Amaya (Stochastic Environmental Research and Risk Assessment, 2000)

Behavior of Brick Samples in Aggressive Environments - G. Cultrone; M. J. De la Torre; E. M. Sebastian; O. Cazalla; C. Rodriguez-Navarro (Water, Air, & Soil Pollution, 2000)

Reaction of common bean callus to culture filtrate of Colletotrichum lindemuthianum: Differences in the composition and toxic activity of fungal culture filtrates - M . T. Fernández; M. Fernández; M. L. Centeno; M . J. Cañal; R. Rodriguez (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

A fragile X case with an amplification/deletion mosaic pattern - D. García Arocena; Y. de Diego; B.A. Oostra; R. Willemsen; M. Mirta Rodriguez (Human Genetics, 2000)

Immunoglobulin kappa light-chain V , J , and C gene sequences of the owl monkey Aotus nancymaae - O. L. Diaz; C. A. Daubenberger; R. Rodriguez; M. Naegeli; A. Moreno; M. E. Patarroyo; G. Pluschke (Immunogenetics, 2000)

A fragile X case with an amplification/deletion mosaic pattern - D. García Arocena; Y. de Diego; B.A. Oostra; R. Willemsen; M. Mirta Rodriguez (Human Genetics, 2000)

Response of Parasitoids Dendrosoter protuberans and Cheiropachus quadrum to Attractants of Phloeotribus scarabaeoides in an Olfactometer - Carlos Lozano; Emilio Gonzalez; Aranzazu Peña; Mercedes Campos; M. Teresa Plaza; Miguel Rodriguez; Isidoro Izquierdo; Juan Tamayo (Journal of Chemical Ecology, 2000)

The correlation of the gene csoS2 of the carboxysome operon with two polypeptides of the carboxysome in Thiobacillus neapolitanus - S. H. Baker; S. C. Lorbach; M. Rodriguez-Buey; Donna S. Williams; Henry C. Aldrich; J. M. Shively (Archives of Microbiology, 1999)

A statistical approach to study the dynamics of micropropagation rates, using banana ( Musa spp.) as an example - B. M. J. Mendes; S. B. Filippi; C. G. B. Demétrio; A. P. M. Rodriguez (Plant Cell Reports, 1999)

Nitrogen and Sulfur Deposition and Forest Nutrient Status in the Valley of Mexico - M. E. Fenn; L. I. de Bauer; A. Quevedo-Nolasco; C. Rodriguez-Frausto (Water, Air, & Soil Pollution, 1999)

Variation among and within Capsicum species revealed by RAPD markers - J. M. Rodriguez; T. Berke; L. Engle; J. Nienhuis (Theoretical and Applied Genetics, 1999)

Structure and function of the stalk, a putative regulatory element of the yeast ribosome. Role of stalk protein phosphorylation - M. A. Rodriguez-Gabriel; G. Bou; E. Briones; R. Zambrano; M. Remacha; J. P. G. Ballesta (Folia Microbiologica, 1999)

Sediment Toxicity Bioassays for Assessment of Contaminated Sites in the Nervion River (Northern Spain). 1. Three-Brood Sediment Chronic Bioassay of Daphnia Magna Straus - M. Martinez-Madrid; P. Rodriguez; J. I. Perez-Iglesias (Ecotoxicology, 1999)

Relative and combined effects of ethanol and protein deficiency on strontium and barium bone content and fecal and urinary excretion - E. Gonzalez-Reimers; F. Rodriguez-Moreno; A. Martinez-Riera; A. Mas-Pascual; E. Delgado-Ureta; L. Galindo-Martin; M. Arnay-de La Rosa; F. Santolaria-Fernandez (Biological Trace Element Research, 1999)

Monthly mean pressure reconstructions for Europe for the 1780–1995 period - P.D. Jones; T.D. Davies; D.H. Lister; V. Slonosky; T. Jónsson; L. Bärring; P. Jönsson; P. Maheras; F. Kolyva‐Machera; M. Barriendos; J. Martin‐Vide; R. Rodriguez; et al. (International Journal of Climatology, 1999)

Regulation by members of the transforming growth factor beta superfamily of the digital and interdigital fates of the autopodial limb mesoderm - Domingo Macias; Yolanda Gañan; Joaquin Rodriguez-Leon; Ramon Merino; J. M. Hurle (Cell and Tissue Research, 1999)

Infertility and risk of fatal ovarian cancer in a prospective cohort of US women - Carmen Rodriguez; Lilith M. Tatham; Eugenia E. Calle; Michael J. Thun; Eric J. Jacobs; Clark W. Heath (Cancer Causes & Control, 1998)

A novel germline mutation in exon 5 of the multiple endocrine neoplasia type 1 gene - A. Chico; Luis Gallart; Eugenia Mato; Carmen Mayoral; Jesus M. Martin-Campos; Lluís Catasús; Jose Rodriguez-Espinosa; Xavier Matías-Guiu; Francisco Blanco-Vaca; Alberto de Leiva (Journal of Molecular Medicine, 1998)

Controlling nitrous oxide emissions from grassland livestock production systems - O. Oenema; G. Gebauer; M. Rodriguez; A. Sapek; S.C. Jarvis; W.J. Corré; S. Yamulki (Nutrient Cycling in Agroecosystems, 1998)

Multiple Analysis of a Foodborne Outbreak caused by Infant Formula Contaminated by an Atypical Salmonella virchow Strain - M. A. Usera; A. Rodriguez; A. Echeita; R. Cano (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Phylogeography of the West Indian manatee ( Trichechus manatus ): how many populations and how many taxa? - A. I. GARCIA‐RODRIGUEZ; B. W. BOWEN; D. DOMNING; A. A. MIGNUCCI‐GIANNONI; M. MARMONTEL; R. A. MONTOYA‐OSPINA; B. MORALES‐VELA; M. RUDIN; R. K. BONDE; P. M. McGUIRE (Molecular Ecology, 1998)
To resolve the population genetic structure and phylogeography of the West Indian manatee ( Trichechus manatus ), mitochondrial (mt) DNA control region sequences were compared among eight locations across the western Atlantic region. Fifteen haplotypes were identified among 86 individuals from Florida, Puerto Rico, the Dominican Republic, Mexico, Colombia, Venezuela, Guyana and Brazil. Despite the manatee’s ability to move thousands of kilometres along continental margins, strong population separations between most locations were demonstrated with significant haplotype frequency shifts. These findings are consistent with tagging studies which indicate that stretches of open water and unsuitable coastal habitats constitute substantial barriers to gene flow and colonization. Low levels of genetic diversity within Florida and Brazilian samples might be explained by recent colonization into high latitudes or bottleneck effects. Three distinctive mtDNA lineages were observed in an intraspecific phylogeny of T. manatus , corresponding approximately to: (i) Florida and the West Indies; (ii) the Gulf of Mexico to the Caribbean rivers of South America; and (iii) the northeast Atlantic coast of South America. These lineages, which are not concordant with previous subspecies designations, are separated by sequence divergence estimates of d = 0.04–0.07, approximately the same level of divergence observed between T. manatus and the Amazonian manatee ( T. inunguis , n = 16). Three individuals from Guyana, identified as T. manatus , had mtDNA haplotypes which are affiliated with the endemic Amazon form T. inunguis . The three primary T. manatus lineages and the T. inunguis lineage may represent relatively deep phylogeographic partitions which have been bridged recently due to changes in habitat availability (after the Wisconsin glacial period, 10 000 BP ), natural colonization, and human‐mediated transplantation.

Effects of ? 2 -microglobulin mutations on the alpha-1 helical region of H2-L d - Carla S. Schultz; Rafael A. Rodriguez; Eleanor A. Chew; M. C. Nieto; Christian Dimaano; Fung-Mee Li; Marjorie D. Santos (Immunogenetics, 1998)

Letters - Timothy D. Male; Reed F. Noss; Timothy M. Crowe; Jon Paul Rodriguez; Gary K. Meffe (Conservation Biology, 1998)

Multiple analysis of a foodborne outbreak caused by infant formula contaminated by an atypicalSalmonella virchow strain - M. A. Usera; A. Rodriguez; A. Echeita; R. Cano (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

The corticostriatal system mediates the "paradoxical" contraversive rotation but not the striatal hyperexpression of Fos induced by amphetamine early after 6-hydroxydopamine lesion of the nigrostriatal pathway - E. Lopez-Martin; G. Rozas; J. Rodriguez; M. J. Guerra; J. L. Labandeira-Garcia (Experimental Brain Research, 1998)

A morphological and histological comparison of the initiation and development of pecan (Carya illinoinensis) somatic embryogenic cultures induced with naphthaleneacetic acid or 2,4-dichlorophenoxyacetic acid - Adriana P. M. Rodriguez; Hazel Y. Wetzstein (Protoplasma, 1998)

Semi-mass culture of the dinoflagellate Gymnodinium splendens as a live food source for the initial feeding of marine finfish larvae - Eduard M. Rodriguez; Kazutsugu Hirayama (Hydrobiologia, 1997)

Embryogenesis induction in petals of Araujia sericifera - J. M. Torné; P. Rodriguez; A. Manich; I. Claparols; M. A. Santos (Plant Cell, Tissue and Organ Culture (PCTOC), 1997)

A comparison between laddermill and treadmill maximal oxygen consumption - M. A. Montoliu; V. Gonzalez; B. Rodriguez; L. Palenciano (European Journal of Applied Physiology, 1997)

Isolation by distance in Germany - I. Barrai; C. Scapoli; M. Beretta; C. Nesti; E. Mamolini; A. Rodriguez-Larralde (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Natural Co-Occurence of Fusarium Species (Section Liseola) and Apergillus flavus Group Species, Fumonisin and Aflatoxin in Argentinian Corn - A. Torres; M. L. Ramirez; M. M. Reynoso; M. Y. Rodriguez; S. Chulze (Cereal Research Communications, 1997)

Fusarium and Fumonisins in Corn at Harvest Time: Effect of Fertilization and Planting Area - M. L. Ramirez; A. Torres; M. Rodriguez; C. Castillo; S. Chulze (Cereal Research Communications, 1997)

Factors affecting mortality of crossbred and exotic chickens kept under backyard systems in Yucatan, Mexico - J. C. Rodriguez; J. C. Segura; A. Alzina; M. A. Gutierrez (Tropical Animal Health and Production, 1997)

A molecular genetic map of cassava (Manihot esculenta Crantz) - M. Fregene; F. Angel; R. Gomez; F. Rodriguez; P. Chavarriaga; W. Roca; J. Tohme; M. Bonierbale (Theoretical and Applied Genetics, 1997)

Redox modulation of the response of NADH oxidase activity of rat liver plasma membranes to cyclic AMP plus ATP - D. James Morré; Juan Carlos Rodriguez-Aguilera; Placido Navas; Dorothy M. Morré (Molecular and Cellular Biochemistry, 1997)

Body fluid homeostasis and cardiovascular adjustments during submaximal exercise: influence of chewing coca leaves - Hilde Spielvogel; Armando Rodriguez; Brigitte Sempore; Esperanza Caceres; J.-M. Cottet-Emard; Laurent Guillon; R. Favier (European Journal of Applied Physiology, 1997)

Differential effects of ventilatory stimulation by sex hormones and almitrine on hypoxic erythrocytosis - R. Favier; H. Spielvogel; E. Caceres; A. Rodriguez; B. Sempore; J. Pequignot; J. M. Pequignot (Pflügers Archiv - European Journal of Physiology, 1997)

Rapid identification ofClostridium botulinum and botulinal toxin in food - A. Rodriguez; M. Dezfulian (Folia Microbiologica, 1997)

Influence of gender and endogenous sex steroids on catecholaminergic structures involved in physiological adaptation to hypoxia - J. M. Pequignot; H. Spielvogel; E. Caceres; A. Rodriguez; B. Semporé; J. Pequignot; R. Favier (Pflügers Archiv - European Journal of Physiology, 1997)

Inhibition of Various Cholinesterases with the Enantiomers of Malaoxon - O. P. Rodriguez; G. W. Muth; C. E. Berkman; K. Kim; C. M. Thompson (Bulletin of Environmental Contamination and Toxicology, 1997)

Oral immunization of rabbits with VP60 particles confers protection against rabbit hemorrhagic disease - J. Plana-Duran; M. Bastons; M. J. Rodriguez; I. Climent; E. Cortés; C. Vela; I. Casal (Archives of Virology, 1996)

Analysis of sites of foot and mouth disease virus persistence in carrier cattle via the polymerase chain reaction - M. L. Prato Murphy; R. F. Meyer; C. Mebus; A. A. Schudel; M. Rodriguez (Archives of Virology, 1994)

Book reviews - Jon F. Hunter; J. G. Llaurado; Jean O'Connor Dorsi; William M. Chilian; Harcharan Singh Ranu; David J. Pogue; Carlos A. Rodriguez-Garcia (Annals of Biomedical Engineering, 1990)

Inhibition of the yeast-mycelial transition and the phorogenesis of Mucorales by diamino butanone - M. Martinez-Pacheco; G. Rodriguez; G. Reyna; C. Calvo-Mendez; J. Ruiz-Herrera (Archives of Microbiology, 1988)

Morphology of bacterial leaching patterns by Thiobacillus ferrooxidans on synthetic pyrite - M. Rodriguez-Leiva; H. Tributsch (Archives of Microbiology, 1988)

Lipopolysaccharides of Thiobacillus species containing lipid A with 2,3-diamino-2,3-dideoxyglucose - A. Yokota; M. Rodriguez; Y. Yamada; K. Imai; D. Borowiak; H. Mayer (Archives of Microbiology, 1987)

Studies on the mechanism of entry of vaccinia virus in animal cells - R. A. Janeczko; J. F. Rodriguez; M. Esteban (Archives of Virology, 1987)

Antibiotic susceptibility of clinical isolates of Pseudomonas aeruginosa - C. Cervantes-Vega; J. Chavez; M. G. Rodriguez (Antonie van Leeuwenhoek, 1986)

Human cytomegalovirus persists in cells treated with interferon - J. E. Rodriguez; T. R. Loepfe; M. F. Stinski (Archives of Virology, 1983)

Imide derivatives of 3-nitro-1.8-naphthalic acid: Their inhibitory activity against DNA viruses - A. Garca Gancedo; C. Gil-Fernndez; P. Vilas; S. Perez; E. Paez; F. Rodriguez; M. F. Braa; C. M. Roldn (Archives of Virology, 1982)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)

Formation of protoplasts ofFusarium culmorum by strepzyme - M. J. Rodriguez Aguirre; Isabel Garcia Acha; J. R. Villanueva (Antonie van Leeuwenhoek, 1964)